Proton transfer reinforced by rare earth oxides enables highly efficient methanogenesis during biochar-mediated direct interspecies electron transfer - Yu-Hong Qiu; Zhi-Biao Chen; Zu-Liang Chen; Zhi-Man Yang (Bioresource Technology, 2027)

Functional characterization of CnAGAL2, a key α-galactosidase involved in postharvest endosperm thickening of coconut (Cocos nucifera L.) - Jian Wang; Fan-jing Zhang; Fang Liu; Yu-ping Man; Shi-biao Liu; Yan-chang Wang; Dong-dong Li (Postharvest Biology and Technology, 2026)

Recent progress on biological control of Fusarium wilt in vegetable crops - Feng Xiong; Mingfeng Guo; Yawen Liu; Xiaochen Liu; Jiahui Fu; JunZhu Gao; Man Yang; Rui Ma; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Crop Protection, 2026)

Deposition characteristics and spraying path planning method of sprayed ultra-high performance concrete - Huai-Na Wu; Jia Wen; Tao Chen; Man Yu; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Biocontrol potential of Bacillus velezensis lut-Y1: Antifungal lipopeptides against postharvest fungi Alternaria alternata and Penicillium expansum - Hui-Jun Yuan; Yan-Sen Li; Wen-Jin Ma; Tian-Kun Zhao; Zhen-Dong Wang; Miao-Miao He; Shi-Man Yu; Yan-Ying Xu (Physiological and Molecular Plant Pathology, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Bacillus subtilis is crucial for the normal growth of mycelium for Stropharia rugosoannulata - Yu Tian; Man Cui; Suyue Zheng; Nuolin Yang; Qinghao Fan; Jinwei Zhang; Gaige Shao; Ruiying Zhang (Fungal Biology, 2026)

Corncob biorefinery: XOS via extrusion–microwave hydrolysis and carbon/MoS2 catalysts from residue - Jiakang Liang; Jingyi Han; Ziwei Zhu; Xingyu Fan; Yagoub Abu El-Gasim A; Man Zhou; Haoxin Li; Li Chen; Xiaojie Yu; Cunshan Zhou (Biomass and Bioenergy, 2026)

Low-cost, energy-efficient sap flow system reveals multi-year transpiration dynamics in a subtropical mixed-species plantation - Ignacio Ruiz de la Cuesta Vela; Tomonori Kume; Cheng-Wei Lai; Man-Shun Hsu; Chieh-Yu Hong; Shin-Min Chong; Shih-Chieh Chang (Agricultural and Forest Meteorology, 2026)

A synergistic probiotic delivery strategy: Pectin-protein-hyaluronic acid hydrogel microcapsules enhance the protective efficacy of Lacticaseibacillus rhamnosus JY027 against DSS-induced colitis - Yue Meng; Fangfang Su; Yuhan Cui; Hanying Yang; Qian Guo; Wei Zhang; Ling Guo; Yujun Jiang; Chaoxin Man; Yu Zhang (Food Bioscience, 2026)

Towards sustainable multi-bed hospital wards: numerical evaluation of infection control, thermal comfort, and energy savings under real-world ventilation strategies - Mei Yan Chong; Hui An; Brenda Sze Peng Ang; Chew Beng Soh; Szu-Cheng Chien; Peng Cheng Wang; Simon Ching Man Yu (Energy and Buildings, 2026)

Structurally decoupled strongly hydrophobic biocathode enables high-performance flexible enzymatic biofuel cells for self-powered sensing - Jie Gao; Ang Xu; Jia Wu; Jinlong He; Ping Wang; Ying Liu; Qiang Wang; Bo Xu; Yuanyuan Yu; Man Zhou (Chemical Engineering Journal, 2026)

Humification and greenhouse gas emissions divergently regulated during black soldier fly manure composting system by biochar, humic acid, and tea residue - Nanyi Wang; Ben Zhang; Wenjuan He; Hongmei Yin; Man Yu; Binghua Yan; Liuqin He; Lin Luo; Xi He; Lihua Zhang; Xichen Zhao; Xing Peng; et al. (Bioresource Technology, 2026)

Effect of oxygen vacancy-rich cerium dioxide on anaerobic digestion of phytoremediated biomass from rare earth mining areas - Yu-Hong Qiu; Ke-Xin Xu; Zhi-Biao Chen; Zu-Liang Chen; Zhi-Man Yang (Biomass and Bioenergy, 2026)

Colorimetric detection of leucine aminopeptidase based on p-aminophenol-mediated redox cycling between Fe3+-ferrozine and tris(2-carboxyethyl)phosphine - Congkui Tian; Xiaoning Chu; Changsen Man; Yaqian Zhang; Zhihao Dang; Zhuo Liu; Baoping Qi; Yu Liu (Analytica Chimica Acta, 2026)

Interface-enhanced label-free FeOOH-mesoporous TiO2 nanocomposite biosensor for highly sensitive quantitative exosome detection to assist cancer screening - Bokai Zhou; Shuyan Liu; Xu Yin; Jie Feng; Mengyu Ding; Caiwei Hu; Guanghai Piao; Ji Man Kim; Junjie Piao; Yu Bai; Mingshi Jin (Analytica Chimica Acta, 2026)

Rapid Electrochemical Synthesis of HOF-PFC-1 for Efficient Sulfamethoxazole Sequestration: Performance, Speciation-Dependent Mechanisms, and Ecotoxicological Evaluation - Azumah Ayamah; Ruijie Peng; Yu Bon Man; Songtao Jing; Xiaoxun Xu; Zhanbiao Yang; Xin Qi; Junzhuo Cai; Zhang Cheng (Journal of Environmental Chemical Engineering, 2026)

Molecular crosstalk of probiotics in gut health: A chemical perspective on metabolite-mediated pathways - Juan Zhang; Xiang Li; Yitong Wang; Chong Yu; Wenyue Xiao; Man Zhang; Zerong Liu; Haifeng Wang (Food Chemistry, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

PDE4B-associated regulation of placental HSD11B2 in fetal growth restriction in a prenatal caffeine exposure model - Xinrui Cao; Ping Jiang; Luting Yu; Man Fang; Xiuping Jin; Hui Wang (Chemico-Biological Interactions, 2026)

Direct interspecies electron transfer was not the sole mechanism contributing to enhanced methanogenesis in biochar-mediated high-solid anaerobic digestion of kitchen waste - Ke-Xin Xu; Yu-Hong Qiu; Zhi-Man Yang (Bioresource Technology, 2026)

The size of paddocks and groups jointly modify diet selectivity of grazing livestock: Divergent response in co-grazing cattle and sheep - Yu Zhang; Man Xu; Hui Zheng; Tong Guo; Yuxuan Du; Yue Huang; Ling Wang (Agriculture, Ecosystems & Environment, 2026)

An Identification Framework for Mesoscopic Shear Deformation Stages of Rock Joints Based on Integration of Multi-source Monitoring Techniques - Hanqian Weng; Zhigang Tao; Chenjie Hong; Jianguo Wang; Hong Wei; Haijun Yu; Man Huang (Rock Mechanics and Rock Engineering, 2026)

An LLM-based framework to evaluate the suitability and accessibility of campsites: A case study of Changsha, China - Yu Man; Yan Shi; Ying Zeng; Minghui Li; Jingsha Han (Sustainable Cities and Society, 2026)

Divergent impacts of additives on biological risks associated with antibiotic resistance genes during black soldier fly manure composting: A comparative study of biochar, humic acid, and tea residue amendments - Nanyi Wang; Tingzhen Xu; Wenjuan He; Genyi Wu; Xinping Li; Xiaomei Yang; Hongmei Yin; Lin Luo; Lihua Zhang; Liuqin He; Anwei Chen; Man Yu; et al. (Journal of Hazardous Materials, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

Deciphering Qu-aroma in Nongxiangxing baijiu via a customized aroma base solution - Sheng-Bing Yang; Zhen-Ming Lu; Jia-Nan Hu; Ting-Yao Tu; Man-Si Niu; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; et al. (Food Research International, 2026)

A novel Camellia oil microemulsion significantly enhances the bioaccessibility and antioxidant activity of curcumin: a comparative study with macroemulsion - Jingyi Chen; Jiayi Zou; Yuting Yang; Wei Li; Qihui Shui; Man Tian; Yu Zhou; Xingfa Han; Tao Chen; Lijun Zhou (Food Chemistry, 2026)

Energy transfer in hydrogen-bonded glassy phosphors enables wide-gamut delayed luminescence - Jiaxuan Meng; Man Zheng; Yiying Liu; Yu Zhou; Tiantian Wang; Yimeng Liang; Dongzhi Liu; Ruihong Liu; Min Wu; Tianyang Wang; Wenbing Jiang (Chemical Engineering Journal, 2026)

Hydrocarbon ionomer catalyst layer engineering for high-performance all-hydrocarbon-based proton exchange membrane water electrolysis - Jaehun Choi; Hwan Yeop Jeong; Yi Sak Noh; Sang Jun Yoon; Keun-Hwan Oh; Hong Suk Kang; Soonyong So; Duk Man Yu (Chemical Engineering Journal, 2026)

Bet-hedging strategies in gall-inducing insects: Daphnephila gall midges (Diptera: Cecidomyiidae) exhibit quadrimodal adult emergence through two types of polymodality in Taiwan - Liang-Yu Pan; Man-Miao Yang (Applied Entomology and Zoology, 2026)
Daphnephila gall midges (Diptera: Cecidomyiidae) inhabiting subtropical evergreen forests in Taiwan exhibit complex temporal diversification in their life histories. We conducted a 7-year field study (2004–2011) tracking four leaf-galling Daphnephila species on 105 Machilus thunbergii trees in northern Taiwan, integrating host phenology, gall development, adult emergence, and parasitism. The host tree displays bimodal bud flushing, producing winter and spring leaf cohorts that provide extended oviposition windows. Correspondingly, Daphnephila populations exhibit quadrimodal adult emergence generated by two forms of polymodality. Within a single generation, individuals display intraseasonal polymodality (Type A sensu Waldbauer 1978), emerging in both winter and spring. In addition, a proportion of larvae undergo extended diapause exceeding 1 year, corresponding to interannual polymodality (Type C). Offspring from the same female frequently diverged into univoltine and semivoltine pathways, demonstrating flexible life-history expression. Parasitism rates were significantly lower in winter-emergent individuals and in semivoltine cohorts, supporting enemy avoidance as a major driver of temporal diversification. This study represents the first explicit documentation of Type A polymodality in Cecidomyiidae and reveals a multi-layered bet-hedging strategy operating across seasonal and interannual scales in a subtropical gall-inducing insect system.

Insular divergence and host-associated diversification in ovoid-gall Daphnephila (Diptera: Cecidomyiidae) from Taiwan, with description of a new species - Sheng-Feng Lin; Tung-Chuan Chiang; Hsuan Chang; Yu-Chu Weng; Man-Miao Yang (Applied Entomology and Zoology, 2026)
The Old World cecidomyiid genus Daphnephila is primarily associated with Machilus (Lauraceae) plants and exhibits exceptionally high gall diversity in Taiwan. At present, six described species correspond to only seven of 40 known Daphnephila gall morphospecies on the island. In this study, we clarified the species identities of Taiwanese Daphnephila inducing long ovoid-galls and ovoid-galls on the leaves of five Machilus plants, and explored their diversification using molecular evidence. Accordingly, two species, D. yukawai sp. n. and D. taiwanensis , were recognized based on morphological characteristics and species delimitation method (Assemble Species by Automatic Partitioning). The former species utilizes only the endemic M . mushaensis , primarily inducing ovoid-galls along the major leaf vein, whereas the latter species associates with five Machilus species and induces two gall types on various leaf parts. Notably, when sympatric with D. yukawai sp. n., D. taiwanensis exhibits character displacement of galling habit, forming long ovoid-galls along the minor leaf veins. Furthermore, the COI-based IQ tree supported: (1) a single origin of East Asian ovoid-gall Daphnephila species, (2) the sister-group relationship between the Taiwanese lineage and a Chinese species, and (3) the role of M. mushaensis as the probable ancestral host of the Taiwanese lineage, including D. taiwanensis. These results suggest that D. taiwanensis colonized additional Machilus hosts after diverging from D. yukawai sp. n. Taken together, our findings indicate that novel plant associations and shifts in galling sites may have facilitated diversification in Daphnephila cecidomyiids, contributing to the remarkable richness of Daphnephila galls in Taiwan.

Degranulated Eosinophilia: An Unexpected Clue in Diagnosis of Ectopic Paragonimiasis - Man Luo; Chao Yu; Tao Kong; Hairu Wang; Peixia Yu (Acta Parasitologica, 2026)

New ecdysteroids with anticomplementary activity from roots of Leuzea uniflora (L.) holub - Wen-qing Du; Can Liu; Ruo-mei Li; Ning-ning Shi; Yan-nan Ji; Jin-long Qi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Climate-Driven Decadal Trends of Particulate Organic Carbon in the Agulhas Current System - Qiwei Hu; Changyuan Zhu; Feifei Peng; Yaoyao Chen; Shujie Yu; Zishuo Man; Haojie Luo (Journal of Marine Science and Engineering, 2026)
The Agulhas Current system, the strongest western boundary current in the Southern Hemisphere, plays a key role in regulating carbon cycling in the southwestern Indian Ocean. However, the variability of particulate organic carbon (POC) and its response to climate forcing remain poorly understood. Using multi-source satellite observations and reanalysis data from 1998–2025, we investigated the spatial, seasonal, interannual, and decadal variability of POC, chlorophyll-a (Chl-a), and POC:Chl-a in the Agulhas Current system. Our results show that Chl-a and POC concentrations are consistently higher in the Agulhas Retroflection than in the Return Current region, reflecting enhanced mesoscale activity and nutrient supply. Seasonally, Chl-a and POC peaked during austral spring–summer and declined during autumn–winter, whereas POC:Chl-a exhibited an opposite cycle driven by variations in light availability and mixed-layer depth. At interannual timescales, ENSO exerted a pronounced influence on POC variability. El Niño events increased Chl-a and POC by up to 0.3 mg m−3 and 30 mg m−3, respectively, while reducing POC:Chl-a by up to 60 g g−1 through enhanced eddy activity and improved light conditions; the opposing anomalies occurred during La Niña events. Positive Southern Annular Mode (SAM), phases increased Chl-a and POC in the Return Current region by strengthening vertical mixing and nutrient entrainment. On multi-decadal timescales, contrasting regional trends resulted in a persistent increase in the POC:Chl—a ratio across both regions, suggesting a structural shift in the particulate carbon pool and an increasing decoupling between particulate organic carbon and phytoplankton biomass. These results highlight the combined roles of stratification, mesoscale dynamics, and climate modes in regulating regional carbon cycling and carbon-sink variability.

Co-regulation of vegetation and sediment on trace-metal risk in deltaic tidal wetlands: Evidence from the Yellow River Estuary - Kezi Zhao; Yuying Qiao; Man Yu; Jiarui Zhang; Shenliang Chen (Marine Pollution Bulletin, 2026)

Hemispheric-Scale assessment of urban morphology effects on NO₂ dynamics via LSTM-Based counterfactuals and structural equation modeling - Shu Wang; Xinyu Yu; Coco Yin Tung Kwok; Mei-Po Kwan; Chun-Ho Liu; Man Sing Wong (Sustainable Cities and Society, 2026)

A versatile colorimetric array sensor based on FeCu-based prussian blue analogue heterostructures for efficient discrimination of tetracycline antibiotics and rapid identification of urinary tract infection pathogens - Dan Wu; Xin-Yu Cheng; Chao-Man Wang; Ya-Nan Kong; Shu-Chang Zhao; Rui-Lin Liu (Journal of Hazardous Materials, 2026)

Cessation of nitrogen addition maintains higher soil organic carbon stability in a subtropical forest acid soil - Quan Li; Tingting Cao; Shuangbo Bi; Mianhai Zheng; Qiqian Wu; Wenjuan Yu; Man Shi; Zhikang Wang; Yuchen Lin; Yakov Kuzyakov; Xinzhang Song (CATENA, 2026)

Nitrogen-Phosphorus Co-Doped Biochar for Persulfate Activation in Sulfadiazine Degradation: Degradation Performance, Mechanism and Toxicity Assessment - Weiwei Yu; Rongqi Liu; Ting Ai; Yufeng Mao; Jiajie Li; Lu Lv; Dan Liu; Yan Luo; Wang Xin; Man Luo; Boyu Liu (Water, Air, & Soil Pollution, 2026)

Integrated inactivation of Microcystis aeruginosa by allelochemicals and a flow-through copper ionization cell: performance insights and mechanisms - Yuewen Zhang; Chen Wang; Yu Hong; Man Liang; Yujia Gao; Xing Xie (ENGINEERING Environment, 2026)

Estimating multi-scale ventilation corridors in complex 3D urban space: A graph-based least-cost path model - Yifan Luo; Xinyu Yu; Majid Nazeer; Man Sing Wong; Jinxin Yang; Rui Zhu (Urban Climate, 2026)

Ferrocene-MOF derived nanoporous carbon for magnetic solid-phase extraction of p‑phenylenediamine antioxidants and quinone-derivatives in various environmental water samples - Jia-Qi Zhao; Bing-Dan Wang; Ao-Ran Wang; Yu-Tian Cai; Shou-Fang Jiang; Hai-Jie Li; Yu He; Man-Man Wang (Journal of Hazardous Materials, 2026)

Metal oxide micro/nanomaterials for gaseous pollutants treatment: Morphology control, performance, and perspectives - Rongrong Jin; Man Zhang; Jie Mi; Jiancheng Wang; Yu Feng (Journal of Environmental Chemical Engineering, 2026)

White peroxidase-mimicking Mn-MOF enabled smartphone-assisted colorimetric sensor for on-site visual detection of perfluorooctane sulfonate in water samples - Shao-Hua Wen; Jun Zhan; Hao Wu; Yule Ji; Qingpeng Zhao; Ziqi Yuan; Junping Ma; Sha Yu; Yuanzhen Zhou; Man Ge (Journal of Environmental Chemical Engineering, 2026)

Contagion in global clean energy markets: Evidence from multilateral and unilateral policy episodes - Cody Yu-Ling Hsiao; Pengyang Li; Chin Man Chui; Xin Zheng (Energy Policy, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

Correction to: The analgesic effect of electroacupuncture in alleviating paclitaxel-induced peripheral neuropathic pain and its possible mechanism relates to TLR4/P2X7-NLRP3 signaling pathway - Yuan-xi Zhou; Man-ni Wang; Juan-juan Xin; Jing-wei Tan; Xiao Sang; Yu-xue Zhao (Purinergic Signalling, 2026)

The analgesic effect of electroacupuncture in alleviating paclitaxel-induced peripheral neuropathic pain and its possible mechanism relates to TLR4/P2X7-NLRP3 signaling pathway - Yuan-xi Zhou; Man-ni Wang; Juan-juan Xin; Jing-wei Tan; Xiao Sang; Yu-xue Zhao (Purinergic Signalling, 2026)

Platelet-rich plasma-primed bone marrow mesenchymal stem cell-derived exosomes inhibit neuronal apoptosis and autophagy, and promote nerve regeneration via the miR-29a-3p/PTEN/PI3K/Akt/mTOR axis after spinal cord injury - Yao Yu; Man Fang; Cailiang Shen (Journal of Molecular Histology, 2026)

Sediment-associated Rare Earth Elements in an Urban River: Bioavailability and Ecological Risks to Aquatic Biota - Ruijie Peng; Pingping Wu; Zhilin Chen; Junzhuo Cai; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Environmental Processes, 2026)

Asymmetric Fe3 +/Fe3⁻δ interfaces engineering in MOFs via boronic acid ligand substitution for targeted bioaerosol capture and inactivation - Shiqi Peng; Zhenyu Wang; Mingyu Xiong; Yongfang Rao; Yulei Zhao; Liu Jiang; Man Lei; dandan Zhu; Jiaquan Zhang; Yu Huang (Journal of Hazardous Materials, 2026)

Casein-liposome complex loading basil essential oil: Preparation, antibacterial effect, and preservative effect on braised beef - Yunshuang Man; Hui Tang; Yudi Wang; Rongrong Yang; Dongling Yan; Qianqian Yu; Lang Zhang; Lin Mei; Jun Qi; Lele Shao (Food Chemistry, 2026)

Synthesis of ZIF-8 derived porous carbon via morphology-controlled electrodeposited ZnO thin films for in-plane micro-supercapacitors - Jun-Yan Lin; Ramasamy Velmurugan; Jing-Jie Lin; Zhi-Ting Huang; Man-Ning Lu; Martin Hulman; Chien-Kuo Hsieh; Jeng-Yu Lin (Chemical Engineering Journal, 2026)

Contagion and network effects of climate policy on stock markets: evidence from carbon-neutral industry chain sectors - Rui Yang; Cody Yu-Ling Hsiao; Yi-Bin Chiu; Chin Man Chui (Climatic Change, 2026)

Cumulative macro-microscopic fatigue damage of hard rock under three-dimensional cyclic impact loading - Yunfeng Wu; Changhong Li; Peng Li; Yu Wang; Dan Ma; Erhui Zhang; Changkun Sun; Prabhat Man Singh Basnet (Bulletin of Engineering Geology and the Environment, 2026)

New nor-tirucallane triterpenoid with antitumor activity from Ailanthus altissima (mill.) swingle - Can Liu; Jun-ling Guo; Shuo-yu Zhao; Ning-ning Shi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Asperhydrindane A, a new hydrindane derivate isolated from a mangrove-derived fungi Aspergillus terreus GXIMD 03158 - Yue Jiang; Fan An; Yu-Man Gan; Kai Liu; Yong-Hong Liu; Cheng-Hai Gao; Pei Cao; Xiang-Xi Yi; Meng Bai (Natural Product Research, 2026)

Dietary trimethylamine N-oxide (TMAO) reduces hepatic lipid deposition and increases flesh hardness through enhancing l-carnitine synthesis and myofiber proliferation in largemouth bass (Micropterus salmoides) - Yu-Yang Liang; Ying-Man Yu; Chen-Chen Wu; Samwel M. Limbu; Meng-Ting Liu; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du; Yuan Luo (Aquaculture, 2026)

Advances in high-performance alginate hydrogels: properties, performance enhancement strategies, and their applications in the food industry - Jiabo Wang; Yuanpu Liu; Chuanwu Han; Zhihui Liu; Yumeng Yue; Zhiyuan Yu; Meng Ma; Qingjie Sun; Fengwei Xie; Man Li (Trends in Food Science & Technology, 2026)

The F-box protein ZmFBK1 facilitates autophagy-mediated degradation of maize NLR protein Rp1-D21 to suppress the hypersensitive response - Chang-Xiao Tang; Shi-Jun Ma; Qi-Dong Ge; Yang Sun; Tong-Tong Liu; Man Yang; Zi-Xuan Kang; Yu-Chen Dai; Xuan Zhang; Xueman Liu; Yanyong Cao; Guan-Feng Wang (Molecular Plant, 2026)

Enhanced chalcopyrite bioleaching performance through CO2-driven process intensification - Ajuan Liu; Yancu Wang; Kai Yang; Meilian Man; Runlan Yu; Jin Huang; Guanzhou Qiu; Weimin Zeng (Journal of Cleaner Production, 2026)

Natural sugar substitute Rebaudioside M: Efficient and cost-effective biosynthesis via host engineering, cascade biocatalysis, and substrate feeding - Xiang Luo; Yang Wang; Man Zhou; Qiaolan Sun; Xue Wang; Xiaojie Yu; Li Chen; Hua Yang; Cunshan Zhou (Food Chemistry, 2026)

Modulation of highland barley noodles quality by water-soluble polyphenols epigallocatechin gallate and ferulic acid - Mengting Wang; Yulin Wu; Zichu Wang; Yu Jiang; Yanfei Wang; Chuanwu Han; Yang Li; Jichun Tian; Meng Ma; Qingjie Sun; Fengwei Xie; Man Li (Food Chemistry, 2026)

Mechanisms underlying differential utilization of carbohydrates from diverse structures and sources in Nile tilapia (Oreochromis niloticus): Insights from glycolipid metabolism, protein deposition and liver health - Meng-Ting Liu; Chen-Chen Wu; Si-Miao Pan; Samwel Mchele Limbu; Yu-Yang Liang; Ying-Man Yu; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du; Yuan Luo (Fish & Shellfish Immunology, 2026)

Tuning d-f hybridization to mimic haloperoxidase for microneedle-assisted targeted therapy of drug-resistant infections - Zhichao Yu; Fengrui Gao; Minglang Zou; Man Xu; Sufang Liu; Da Huang; Zuquan Weng; Yongyi Zeng; Dianping Tang; Xiaolong Liu (Chemical Engineering Journal, 2026)

Enhancement of infrared radiation and heat dissipation functionality of MnSe2 2D magnet via lattice engineering - Man Wang; Xiaolei Nie; Tonglu Huang; Wanting Zhu; Yu Zhang; Mingrui Liu; Zhixin Tang; Wenyu Zhao (Chemical Engineering Journal, 2026)

Coupling 1D-2D hydrodynamic model for urban flooding simulation based on multi-faceted data in Hong Kong - Man Hong Chiu; Xinyu Yu; Huan-Feng Duan; Man Sing Wong; Onyx Wing Hong Wai; PW Chan; Yifan Luo (Natural Hazards, 2026)
Flooding has intensified due to climate change and rapid urbanisation. Extensive studies have been conducted to simulate flooding of outdoor environment. However, limited studies have been conducted inintegrating outdoor and indoor flooding risk assessment. Therefore, this study adopted Infowork ICM model and integrated multi-facted data, including open-sourced drainage networks, 3D visualisation maps, territory habitat maps, raingauge data and minute-interval Kai Tak river level data from monitoring stations provided by the Drainage Service Department to examine and identify risky outdoor and indoor areas under extreme rainfall based on simulated scenarios. The study area is the part of the Kowloon East Area. Specifically, two rainfall scenarios, with different return periods and durations (the index quantifying the severity of rainfall), have been designed and analysed. The RMSE is 45 mm. The simulated result reveals that 15.0%, 25.1% and 27.2% of the study area suffered flooding higher than 100 mm in rainfall events with return periods of 2, 200 and 1000 years respectively. 18.6%, 27% and 28.2% of the study area suffered flooding higher than 250 mm in rainfall events with duration of 60, 180 and 300 min respectively. Moreover, results indicate that flooding is centralised in Kowloon Bay Area, Lung Cheong Road, Kai Yip Estate and Choi Hung Estate. The simulation-based flooding assessment framework provided a basis for investigating spatial-temporal patterns and conducting risk assessment of frequent flooding.

PRRSV nucleocapsid and nonstructural proteins dual-regulate CD40 expression via ATF-2 and AP-1 pathways - Chaolun Fu; Hongyan Gao; Yingchao Li; Chang Liu; Yuzhong Zhao; Youbo Li; Zhong Liu; Man Lu; Yang Shen; Yajing Xing; Yu Wang; Xiaotong Wu; et al. (Veterinary Microbiology, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Ultrasound-assisted breathing revives floated anammox granules by reconnecting intra‑granular metabolic interactions - Min-Nan Song; Hai-Tian Xu; Shi-Man Liang; Shu-Yang Fang; Yu Zhang; Zheng-Zhe Zhang; Ren-Cun Jin (Bioresource Technology, 2026)

Source apportionment of fine and coarse particulate matter in Hong Kong and its implications to PM10 air quality management - Yee Ka Wong; Kin Man Liu; Claisen Yeung; Kenneth K.M. Leung; Jian Zhen Yu (Atmospheric Environment, 2026)

PRDX6 as a Ferroptosis-Related Hub Gene in the Entorhinal Cortex of Alzheimer’s Disease: A Multidimensional Bioinformatics and Experimental Validation Study - Xiaolin Li; Ziteng Man; Tiantian Cheng; Juan Song; Yanan Bao; Yu Lin; Hongyan Yang (Journal of Molecular Neuroscience, 2026)

Inhaled polystyrene nanoparticles may cause fibrotic lesions via immune dysregulation and energy metabolism disturbance - Wonkyun Jung; Man S. Kim; Beom-Geon Kim; Sung-Min Hong; Sanghyeon Yu; Kanghyun Kwon; Mi-Jin Yang; Min Beom Heo; Ik Hwan Kwon; Seong-Jin Choi; Hyosun Choi; Ji Ae Lee; et al. (Toxicology and Applied Pharmacology, 2026)

A histone methylation reader suppresses both disease resistance and tillering by facilitating H3K9me1-mediated gene silencing in rice - Fengfeng Fan; Manman Liu; Huanran Yuan; Nannan Li; Mingxing Cheng; Xiong Luo; Yu Guo; Ayaz Ahmad; Meng Cai; Fengfeng Si; Zihan Yang; Man Wang; et al. (Molecular Plant, 2026)

Selective separation mechanism of a metal inhibitor complex for scheelite and calcite: The structural stability of Fe3+-pyrogallol complex - Wenxin Hua; Jingzhong Kuang; Zheyu Huang; Lei Wang; Man Chen; Chenyang Zhang; Mingming Yu; Lingguo Meng (Minerals Engineering, 2026)

Perspectives on the role of postbiotics in meat and meat products: Current status and future trends - Du-xin Jin; Gui-peng Zou; Rui Liu; Man-gang Wu; Qing-feng Ge; Hai Yu (Meat Science, 2026)

Petrology, geochemistry and geochronology of the Kekeya ash (SW Tarim Basin): Implications for its origin and provenance - Jia-Jun Mo; Yu-Ting Zhong; Man Wang; Le Zhang; Qiong Wu; Qiang Ma; He Wang; Jahandar Ramezani; Xiao-Long Huang; Fu-Yuan Wu; Yi-Gang Xu (Lithos, 2026)

Performance and mechanism of low-temperature domestic sewage treatment by innovative composite ceramsite enhanced biological aerated filter - Xu Wang; Xiao-man Wang; Qing-miao Yu; Ze-tong Shen; Jin-ju Geng (Journal of Water Process Engineering, 2026)

Overlooked role of soil microbial-derived carbon in promoting neurotoxic methylmercury production - Man Yang; Zhi-Cheng Hu; Hui-Wen Liu; Wen Zhang; Yun-Yun Hao; Qin Liu; Jia-Xuan Meng; Bo Meng; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2026)

Unravelling methylmercury formation in high-altitude Tibetan thermokarst lakes - Xia Lu; Xiaosha Liu; Zhixia Yang; Liang Li; Man Yang; Yu-Rong Liu; Baohua Gu; Cuicui Mu (Journal of Hazardous Materials, 2026)

Insight into effects of rare earth oxide modified biochar in modulating direct interspecies electron transfer and accelerating methanogenesis during anaerobic digestion process - Zhi-Man Yang; Ke-Xin Xu; Yu-Hong Qiu; Zhi-Biao Chen; Zu-Liang Chen (Journal of Environmental Chemical Engineering, 2026)

DES-assisted Cu-loaded bagasse-derived carbon as a dual-functional platform for synergistic enzymatic-electrocatalytic depolymerization of lignin - Jiakang Liang; Jingyi Han; Man Zhou; Xiaojie Yu; Li Chen; Hua Yang; Cunshan Zhou (Chemical Engineering Journal, 2026)

Auditory-perception-based tuneable noise control approach for improving acoustic comfort and behaviour of autistic individuals in indoor/outdoor environments - Tak Chun Kwong; Steve Wai Yin Mung; Huan-Ling Yuan; Henry Kar Hang Chu; Yuen Yi Cynthia Lai; Chetwyn Che Hin Chan; Ho Man Yu; Yat Sze Choy (Building and Environment, 2026)

Cadophorin C, a new cyclic heptapeptide isolated from a mangrove-derived fungus Penicillium sp. GXIMD 03101 - Jia-Li He; Xiao-Dong Jiang; Yu-Man Gan; Xin-Jian Qu; Xiang-Xi Yi; Yong-Hong Liu; Cheng-Hai Gao; Meng Bai (Natural Product Research, 2026)

Integrative network pharmacology and experimental validation of multi-target synergy against multidrug-resistant klebsiella pneumoniae via PI3K/AKT-MAPK pathway disruption - Tian Man; Huiyong Yu; Lei Li; Weicheng Nie; Chengxiang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Deep Learning-Based Object Detection of Electromagnetic Interference Echoes from Weather Radar Data - Man Yao; Muyun Du; Rong Yu; Xianling Jiang; Hedi Ma; Guoying Tang; Peiting Liu (Journal of Meteorological Research, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Feed-driven transfer and bioaccumulation of phthalate esters in aquaculture pond ecosystems - Chengyi Huang; Kairui Zhang; Songtao Jing; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Environmental Monitoring and Assessment, 2026)

Transcriptional responses and nutrient cycling dynamics in sea anemone Exaiptasia pallida under thermal stress and nitrogen pollution - Yifei Yu; Wenyan Nong; Ho Wen Lo; Nga Man Chung; Ho Yin Yip; Apple Pui Yi Chui; Benoit Thibodeau; Jerome Ho Lam Hui (Marine Pollution Bulletin, 2026)

Intermittent glycerol feeding shapes a glycogen-storing phenotype for enhanced nitrite accumulation via sequential denitrification - Shi-Man Liang; Jia-Qi Zhou; Hai-Tian Xu; Shu-Yang Fang; Yu Zhang; Zheng-Zhe Zhang; Ren-Cun Jin (Water Research, 2026)

Unravelling the street thermal features network and spatial visual thermal inertia: A study in Hong Kong - Kang Zou; Man Sing Wong; Majid Nazeer; Xinyu Yu; Gangyi Tan; Huiying (Cynthia) Hou; Jinxin Yang; Pak Wai Chan (Sustainable Cities and Society, 2026)

Environmental DNA as a tool for detecting ocean outfall impacts and environmental gradients in coastal ecosystems - Jodie Gibb; Megan Huggett; Margaret Platell; Geoff MacFarlane; Richard Man Kit Yu; Craig Evans; Megan Andrew-Priestley; Michael Stat (Science of The Total Environment, 2026)

Networked predictive tracking control for the underactuated USV subject to communication constraints and external disturbances - Tao Lei; Yuanqiao Wen; Yi Yu; Xin Xiong; Man Zhu (Ocean Engineering, 2026)

A quinone intermediate-mediated novel cascade catalytic-antimicrobial strategy: Regulation of superoxide radicals by low-temperature thermocatalysis of MnBi3Ox for targeted conversion of phenols to quinones - Shuyun Wang; Aijia Wang; Man Wang; Zihan Chen; Zhonghao Yu; Shengyuan Deng; Fang Jiang; Huan Chen (Journal of Hazardous Materials, 2026)

A compatibility-guided GT-SuSy cascade and two-step fed-batch strategy enable scalable and cost-effective biosynthesis of Rebaudioside M - Yang Wang; Xiang Luo; Man Zhou; Xiaojie Yu; Hafida Wahia; Xiaonan Lu; Cunshan Zhou (Innovative Food Science & Emerging Technologies, 2026)

Construction of carboxymethyl chitosan/oxidized Astragalus polysaccharide cross-linked gel microspheres in alginate system: Improving the tolerance and functional characteristics of Lactobacillus paracasei - Yilin Sun; Man Zhu; Zimu Li; Xinyan Yang; Wei Zhang; Ling Guo; Yujun Jiang; Yu Zhang (Food Research International, 2026)

Coalescent 2D heterostructure for high-efficient surface-enhanced Raman scattering and electrochemical sensing - Muhammad H. Nawaz; S. Santhoshkumar; Thi H. Ho; Balamurugan Arumugam; Mohamed Gamal Mohamed; Tuan V. Vu; Yousra.M. Nabil; Mohammed G. Kotp; Li-Wei Tu; Hung-Duen Yang; Ahmed F.M. EL-Mahdy; Shiu-Ming Huang; et al. (Chemical Engineering Journal, 2026)

Deciphering the role and mechanism of biochar dosage and inoculum-to-substrate ratio in modulating interspecies electron transfer and alleviating acid inhibition - Yu-Hong Qiu; Zi-Fan Wu; Jia-Bing Li; Zhi-Man Yang (Biomass and Bioenergy, 2026)

Deformation-Fracture Behavior and Permeability Evolution of Coal Under In Situ True Triaxial Stress–Pore Pressure Unloading - Beichen Yu; Dongming Zhang; Yingke Liu; Changbao Jiang; Yubing Liu; Chao Liu; Man Yuan (Rock Mechanics and Rock Engineering, 2026)

Research on the damage laws and failure characteristics of sandstone in coal seam roofs under different rich-water conditions - Yu Chen; Man Wang; Dongming Zhang; Beichen Yu; Ziyang Xiong; Wenzhuo Li (Bulletin of Engineering Geology and the Environment, 2026)

Subtleties of the synergistic inhibition of Microcystis aeruginosa by L-lysine and a flow-through copper ionization cell: Insights from physiology and transcriptomics - Yuewen Zhang; Yujia Gao; Yu Hong; Man Liang; Xing Xie (Algal Research, 2026)

SREBP2 confers ferroptosis resistance by targeting GPX4 in colorectal cancer - Huage Zhong; Ruiqi Chen; Tianyu Chen; Min Lin; Siqi Wen; Man Zhang; Dejun Liu; Junfeng Yu; Jinchi Chen; Bei Yi; Rong Liang; Wei Jiang; et al. (Apoptosis, 2026)

Tassel counting of individual ridge from UAV RGB imagery based on YOLOv8m with deep SORT and double-step Otsu thresholding algorithm by filtering abnormal IDs for maize breeding - Man Xia; Leilei He; Yu Gu; Xiaojuan Liu; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Yan Long; Anastasia Grecheneva; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

New insights for microplastic degradation: Synergistic degradation mechanisms of microplastics and atrazine in sediments - Cheng Yang; Jinjiang Duan; Jianhao Song; Yu Xiang; Ruxin Yang; Xiangtian Man; Yuanyuan Feng; Dongdong Gao; Mengli Chen; Qingping Zou; Meikun Fan; Han Zhang (Water Research, 2025)

Point-of-use water treatment: energy-autonomous synergistic solar photothermal-piezocatalysis on MXene/Bi2WO6 membranes for distributed removal of sulfonamide antibiotics - Junzhuo Cai; Jiaxin Liu; Yu Bon Man; Jixiang Chen; Luting Li; Xiaoxun Xu; Chengyi Huang; Changlian Xu; Guochun Lv; Xin Qi; Zhanbiao Yang; Guiying Wang; et al. (Water Research, 2025)

Dermal bioaccessibility of organophosphate esters in indoor dust: Influencing factors, release kinetics, and health risk assessment - Zijia Hong; Yu Bon Man; Yue Li; Linying Xiao; Shitong Han; Zhuoyao Chen; Bingyan Lan; Xiaomin Yan; Jiwen Luo; Lixuan Zeng; Yuan Kang (Journal of Hazardous Materials, 2025)

Extracellular protein extraction and role during chalcopyrite bioleaching by S. thermosulfidooxidans - Ajuan Liu; Kai Yang; Meilian Man; Runlan Yu; Guanzhou Qiu; Weimin Zeng (Journal of Environmental Chemical Engineering, 2025)

Comparative structural and functional characterization of Chlamydomonas reinhardtii proteins extracted by alkaline and ultrasound-assisted enzymatic methods - Man Zhou; Wenxin Liu; Ruixian Chen; Jie Yu; Yushuang Ma; Anjun Chen; Hejun Wu; Shutao Yin; Qiang Cui (Food Hydrocolloids, 2025)

Bilayer Bifidobacterium animalis/xylooligosaccharides film enables long-term maintenance of probiotics activity and prolongs strawberry shelf life - Haoxin Li; Xingyu Fan; Man Zhou; Li Chen; Xiaojie Yu; Cunshan Zhou; Haile Ma (Food Packaging and Shelf Life, 2025)

Long-term effects of the hydrophilic and electrophilic modified magnetic carriers on partial nitrification at low temperatures: Enhancing nitrite supply by stimulating major enzyme gene expression - Fang Man; Yi Xue; Yuexin Yu; Chengyu Gu; Sijia Ma; Yuan Lin; Hongqiang Ren; Ke Xu (Environmental Research, 2025)

Lipid metabolism homeostasis and low-level glycogen metabolism in the Harderian gland of hibernating Daurian ground squirrels - Lu-Fan Li; Yu-Jing Yan; Yi-Man Liu; Qing-Ying Wang; Ming-Di Wang; Jin-Hui Xu; Zhe Wang (Cryobiology, 2025)

Biphasic system and benign polymerization enable full utilization of biomass components - Jiakang Liang; Jingyi Han; Man Zhou; Xiaojie Yu; Li Chen; Cunshan Zhou (Biomass and Bioenergy, 2025)

Effects of Heat-Killed Probiotic Strains on Biofilm Formation, Transcription of Virulence-Associated Genes, and Prevention of UTIs in Mice - Yueh-Ying Chen; Zhen-Shu Liu; Bo-Yuan Chen; Hon-Man-Herman Tam; Wei-Yau Shia; Hsin-Hsuan Yu; Po-Wen Chen (Probiotics and Antimicrobial Proteins, 2025)

Thymus serpyllum extract exerts anticancer activities against colorectal cancer by modulating metastasis, cell cycle arrest, and apoptosis - Chao-Yuan Yao; Kai-Fu Chang; Ju-Huei Chien; Xiao-Fan Huang; Yu-Chi Chen; Ming-Chang Hsieh; Nu-Man Tsai (Molecular Biology Reports, 2025)

Silencing aquaporin 1 inhibits autophagy to exert anti-rheumatoid arthritis effects in TNF-α-induced fibroblast-like synoviocytes and adjuvant-induced arthritis rats - Man-yu Zhang; Meng-qing Wang; Yan Huang; Sheng-long Gu; Meng-yuan Zhou; Ze-shan Xu; Ling-ling Li; Min Lv; Li Cai; Rong Li (Inflammation Research, 2025)

Cadmium-induced nucleus pulposus derived mesenchymal stem cells apoptosis via MAPK signaling pathway contributes to IVD degeneration - Man Hu; Yu Zhang; Wen-jie Zhao; Xin Liu; Yan-feng Zhang; Da-xu Liu; Xin-min Feng; Liang Zhang (In Vitro Cellular & Developmental Biology - Animal, 2025)

Control of post-harvest soft rot (Rhizopus stolonifer) on sweet cherry using volatile organic compounds produced by Bacillus velezensis Q-84 - Jian-Yu Wang; Min-Xin Mao; Chun-Yan Xu; Man Zou; Wen-Ting Bao; Yi-Ning Zhou; Shun-Qing Hu; Ke-Xin Jiao; Qing-Kun Lu; Peng Zhao; Kun-Peng Zhang; Yi-Lun Chen; et al. (BioControl, 2025)

Targeting MAPK10 with gga-miR-222b-5p suppresses apoptosis in DF-1 cells infected with the avian reticuloendotheliosis virus strain SNV(REV-SNV) - Qing Zhang; Yubo Zhao; Saisai Zhao; Xinhong Man; Shumin Yu; Youxiang Diao; Yi Tang; Jingdong Hu (Veterinary Microbiology, 2025)

Nrf2-mediated inhibition of ferroptosis contributes to the amelioration of atherosclerosis by polydatin - Yu Qiu Wu; Ruo Man Wu; Yi Zeng; Xiao Le Xu (Toxicology and Applied Pharmacology, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Discovery of milk-derived antimicrobial peptides in human milk by DeepMAMP based on peptidomics technology and deep learning method - Wenhao Yu; Xinchen Zhang; Yang Yu; Dengcai Zhao; Sufang Duan; Ignatius Man-Yau Szeto; Jian He; Li Liu; Yan Jin (Food Chemistry, 2025)

Safety, health, and sustainable production of natural sugar substitutes: emerging mechanistic insights - Yang Wang; Xiang Luo; Cunshan Zhou; Man Zhou; Li Chen; Yabin Feng; Zhenfeng Yang; Xiaojie Yu (Food Bioscience, 2025)

Liposome-delivered natural antimicrobials in foods: Antibacterial efficacy and mechanisms - Dongling Yan; Yudi Wang; Rongrong Yang; Yunshuang Man; Hui Tang; Qianqian Yu; Lele Shao (Food Bioscience, 2025)

Mechanism of high intensity ultrasonic treatment combined with β-glucan affecting the structure of highland barley protein to improve the stability of highland barley milk - Hongwei Cao; Xiaotong Zhuang; Haojie Liu; Man Wang; Kai Huang; Hongdong Song; Sen Li; Yu Zhang; Zhenliang Sun; Xiao Guan (Food Hydrocolloids, 2025)

Hierarchically plasticized intrinsically stretchable fully π-conjugated polymer films for flexible and large-area printed RGB light-emitting diodes - Ningning Yu; Zhiqiang Zhuo; Yingying Zheng; Mingjian Ni; Wenyu Chen; Jiabin Liu; Dunliang He; Jingyao Ma; Man Xu; Xiang An; Lubing Bai; Jinyi Lin; et al. (Chemical Engineering Journal, 2025)

High-efficiency SrTiO₃@SiC catalytic ceramic membrane with photocatalytic self-cleaning for enhanced tetracycline degradation and fouling resistance in wastewater treatment - Rongqi Xu; Dandan Tang; Yu Tian; Yichuan Xu; Kexin Hu; Xiaolei Wang; Zhengqian Wen; Jiayou Ji; Changlian Chen; Shulin Wang; Li Zhu; Man Xu (Chemical Engineering Journal, 2025)

Marangoni microjet–photonic sintering synergy enables robust piezoresistive interfaces on methylated polysiloxanes for closed-loop proprioceptive exoskeletons - Ke-Yu Yao; Bryan Pak-Hei So; Ethan Shiu Wang Cheng; Ye-Jiao Mao; Patrick Yiu-Man Yip; Duo Wai-Chi Wong; Bingyang Dai; Xin Zhao; Cheng Dong; Siu Hong Dexter Wong; James Chung-Wai Cheung (Chemical Engineering Journal, 2025)

Synergistic effects of biochar-microbial inoculants on greenhouse gas mitigation in paddy ecosystems: organic substitution and enzyme driven emission reduction - Kun Zhou; Keqi Zhao; Xiaobing Zhang; Jiachao Zhang; Man Yu; Liuqin He; Lin Luo; Fangying Yu; Lihua Zhang; Xichen Zhao (Biocatalysis and Agricultural Biotechnology, 2025)

Genetic deficiency of CCL5 exhibits the phenotypes of HFpEF and aggravates apoptotic cardiomyopathy in HFD-induced diabetic mice - Jiung-Pang Huang; Kuan-Hsing Chen; Po-Shiuan Hsieh; Chao-Yu Kuo; Chao-Lan Yu; Li-Man Hung (Journal of Molecular Medicine, 2025)

Online detection of broken and impurity rates in half-feed peanut combine harvesters based on improved YOLOv8-Seg - Man Gu; Haiyang Shen; Jie Ling; Zhaoyang Yu; Weiwen Luo; Feng Wu; Fengwei Gu; Zhichao Hu (Computers and Electronics in Agriculture, 2025)

Hierarchical fractal surface patterns for enhanced gypsum scaling resistance in membrane distillation: A computational fluid dynamics analysis - Balsam Swaidan; Immanuvel Paul; Simon Ching Man Yu (Journal of Water Process Engineering, 2025)

Effect of oleic acid iodine value on the flotation performance of oleic acid-based collectors for spodumene - Ying Zhang; Ning Sun; Yuhua Wang; Liu Luo; Man Cui; Yu Li (Journal of Environmental Chemical Engineering, 2025)

Insights into pollution characteristics of phthalate esters in soil-crop systems and associated responses of soil microbial communities: The case study of Pengzhou, China - Xin Qi; Yu-Hao Zhao; Yu-Bon Man; Ming-Hung Wong; Zhan-Biao Yang; Xiao-Xun Xu; Guo-Chun Lv; Gun-Yin Wang; Chang-Lian Xu; Jun-Zhuo Cai; Zhang Cheng (Journal of Environmental Chemical Engineering, 2025)

Rational construction and reaction mechanism of bimetal oxides/carbon nanofibers sorbent for H2S removal at high temperature - Xiaojun Xue; Zidan Li; Ying Yue; Man Zhang; Yangjie Sun; Jie Mi; Jiancheng Wang; Ajay Mishra; Jasur Shodmanov; Yu Feng (Journal of Environmental Chemical Engineering, 2025)

Immunosuppressive role of benzo[a]pyrene exposure in prostate cancer progression - Zhijin Zhang; Wentao Zhang; Huan Wang; Haotian Chen; Hong Wang; Yang Yu; Danjing Shen; Man Pi; Yang Wu; Ming Luo; Yanyan He; Shiyu Mao; et al. (Journal of Environmental Sciences, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Enhancing the formation rate and level of oat globulin fibrils by microwave heating: Elucidation of potential mechanisms - Mengdi Cai; Hongwei Cao; Sen Li; Hongdong Song; Yu Zhang; Kai Huang; Man Wang; Zhenliang Sun; Xiao Guan (Food Hydrocolloids, 2025)

Screening and prediction of potential androgen receptor agonists in indoor dust - Zhi Hao Guo; Yu Bon Man; Yuan Kang (Environmental Pollution, 2025)

Centennial-scale evolution, source apportionment, and ecological risks of heavy metals in Daya Bay, South China sea - Xiangtian Man; Jian Sun; Yu Xiang; Hong Su; Honghui Huang; Yangguang Gu; Han Zhang; Richard W. Jordan; Shijun Jiang (Environmental Pollution, 2025)

Excellent durability and multifunctional textiles with dual-mode evaporative and radiative cooling enabled by in-situ growth of SiO2 and electrostatic network coating - Luxuan Zhang; Bo Xu; Man Zhou; Ying Liu; Ying Zhang; Li Cui; Ping Wang; Qiang Wang; Yuanyuan Yu (Chemical Engineering Journal, 2025)

Biofilm-enhanced PFAS removal in constructed wetlands: Sewage sludge biochar drives adsorption and microbial synergy - Fuhao Zhang; Cheng Shen; Yaqian Zhao; Lingwei Kong; Feng Ju; Bin Ji; Yu Bon Man; Shengdao Shan; Yuliang Li; Jin Zhang (Chemical Engineering Journal, 2025)

A novel strategy of magnetic-dielectric synergistic metamaterials based on multifunctional anisotropic aerogels for superior electromagnetic wave absorption - Chen Li; Yu Gao; Xiao He; Yongkang Lai; Yajie Xie; Weiwei Qi; Qikui Man; Baogen Shen (Chemical Engineering Journal, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Cadmium and Benzo[a]pyrene Co-exposure Synergistically Induces Apoptosis in Bronchial Epithelium: Mechanistic Insights and Predictive Risk Modeling for Indoor Dust - Junbo Liu; Linxi Yang; Jixiang Chen; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Biological Trace Element Research, 2025)

Fate and health implications of polycyclic aromatic hydrocarbons in a sustainable food waste recycling system using housefly maggots and Nile tilapia - Chao Zheng; Zhang Cheng; Zhi-Lin Chen; Yu Bon Man; Qiao Liu; Liu-Lan Zhao; Song Yang; Ming Hung Wong (Aquaculture, 2025)

The causal effect of monthly pass programs on public transportation and carbon emissions - Yu-You Liou; Man-Keun Kim; Hung-Hao Chang; Ruey-Wan Liou (Transportation Research Part D: Transport and Environment, 2025)

Enhanced East Asian summer monsoon circulation during the Early to Middle Bronze Age - Jiawei Jiang; Yancheng Zhang; Deming Kong; Hongxuan Lu; Huanye Wang; Yu Liang; Charlotte Wing Man Lee; Hongwei Liu; Bowen Meng; Zhouqing Xie; Hong Yan; Weiguo Liu; et al. (Quaternary Science Reviews, 2025)

Impact of cationic reagent structure on the performance of combined collectors in spodumene-feldspar flotation system - Ying Zhang; Yuhua Wang; Ning Sun; Haiqiang Feng; Yu Li; Man Cui (Minerals Engineering, 2025)

Acetamiprid mediates cognitive dysfunction through the gut-brain axis: Synaptic damage and immune-mediated blood-brain barrier dysfunction - Bing Wu; Xue-yan Tian; Wen-si Ni; Hao-Xuan Gao; Yu-wen Wang; Ling-he Zhang; Yu-bin Li; Yan-ling Lv; Ya-nan Song; Yu-cheng Yan; Xiao-zhe Geng; Yi-man Li; et al. (Journal of Hazardous Materials, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Electric vehicle attributed future air pollution alleviation: A case study in Guangdong province, China - Xinyu Yu; Man Sing Wong; Kai Qin; Rui Zhu; Linlin You; Jing Wei (Journal of Environmental Management, 2025)

Influencing the retrogradation properties of potato mash through multi-scale structural modifications mediated by enzymatic hydrolysis forms - Hongwei Cao; Mengting Huang; Zhenhao Liu; Kai Huang; Man Wang; Hongdong Song; Sen Li; Yu Zhang; Zhenliang Sun; Xiao Guan (Food Chemistry, 2025)

Ultra-sensitive detection of Cu2+ in water and infant formula using a carbon dot-embedded MIL-53 electrochemiluminescence sensor - Xiaofeng Wei; Yu Su; Man Jiang; Hongfei Ji; Ruizhong Zhang; Daqian Song; Lan Ding; Yanhua Chen (Food Chemistry, 2025)

Algae biofilm produces less microbe-derived dissolved organic nitrogen under higher C/N ratio conditions - Yuexin Yu; Yuan Lin; Chengyu Gu; Fang Man; Sijia Ma; Yi Xue; Hongqiang Ren; Ke Xu (Environmental Research, 2025)

Simulation and exposure assessment of hourly traffic noise in Hong Kong using a minimal error iterative model based on diversion strategies - Kang Zou; Xinyu Yu; Coco Yin Tung Kwok; Man Sing Wong; Mei-Po Kwan; Huiying (Cynthia) Hou (Computers, Environment and Urban Systems, 2025)

Role and mechanism of combination of biochar and electroactive microbial consortium in facilitating methanogenesis - Kai-Zhao Wang; Zi-Fan Wu; Yu-Hong Qiu; Zhi-Man Yang (Chemical Engineering Journal, 2025)

Biosensing meets photoelectrochemistry: A promising analytical tool to be integrated with microfluidic device for on-site food safety analysis - Xinna Xie; Danqing Zhu; Yu Zhang; Xinyan Yang; Chaoxin Man; Yujun Jiang; Wei Zhang; Xianlong Zhang (Chemical Engineering Journal, 2025)

MOFs-induced robust interphase enriched in Li2O boosting Li plating/stripping coulombic efficiency of lithium metal anode in commercial carbonate electrolyte - Ke Wang; Ji Qian; Yi Chen; Tianyang Yu; Man Zhang; Xinhui Pan; Renjie Chen (Chemical Engineering Journal, 2025)

Full-scale studies are closer to reality than lab-scale ones: Tertiary treatment constructed wetlands maintain robust removal capability for pharmaceuticals and personal care products in cold weather conditions - Jiaxi Wang; Beibei Ye; Xia Yu; Ruiqi Yan; Hui Lin; Ying Man; Qian Sui (Bioresource Technology, 2025)

Climate change aggravates the Spatiotemporal imbalance of water resources in the Rice-Wheat rotation region of the middle and lower Yangtze river - Hao He; Man Li; Lin Zhao; Jinge Yu; Qi Li; Zhenghua Hu; Xuesong Zhang (Theoretical and Applied Climatology, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

Electrical Detection of Shale Gas Layers Based on Wide-Field Electromagnetic Method - Li-Xin Man; Zhang-Kun Tan; Jian-Chao Jia; Zhi-Wen Gu; Chang-Heng Yu; Xue-Bo Yin (Applied Geophysics, 2025)

More Than a Decade of Moderate Grazing: No Impact on Soil Organic Carbon Stocks and Enhancement of Mineral‐Associated Organic Carbon via Livestock Diversification - Yipeng Zhou; Man Xu; Shuai Ren; Yuxuan Du; Yonghuan Yue; Haoran Yu; Yu Zhang; Shicheng Jiang; Tongtong Xu; Ling Wang (Global Change Biology, 2025)
Managed grassland soils represent a large reservoir of soil organic carbon (SOC), playing a crucial role in climate regulation. While optimal herbivore grazing is presumed to be nondetrimental and may even increase soil carbon sequestration, there is a limit to long‐term experimental studies to validate this effect, especially those that incorporate multiple herbivore species and their combinations to assess impacts on SOC stocks. Here, we conducted a 14‐year controlled grazing experiment with moderate intensity, incorporating common herbivore species (sheep, cattle or both) in a temperate grassland. The results showed that more than a decade of moderate grazing did not alter total SOC stocks and also particulate organic carbon (POC) regardless of livestock assemblages, while diversified livestock grazing by cattle and sheep increased the mineral‐associated organic carbon (MAOC) content and its proportion of bulk soil carbon. This effect of grazing on soil MAOC is primarily attributed to an increase in soil microbial carbon inputs, driven directly by diversified livestock grazing and indirectly by improved plant diversity and soil conditions. Our study indicates that moderate grazing had a strong effect on MAOC, a key indicator of long‐term soil carbon stability, but had little influence on total SOC. We further suggest that improving grassland soil carbon sequestration requires not only optimizing grazing intensity but also incorporating diverse herbivore assemblages that mimic natural grazing systems, with diversified moderate grazing emerging as an effective management strategy for promoting carbon storage and contributing to climate change mitigation.

A new strategy for removing insecticide etoxazole from soil using a combination of a novel Paracoccus versutus Y4 and a fungal mycelium carrier - Man Xu; Xue Luo; Xin-Li Yan; Xiao-Yu Cai; Lin-Lin Wang; Feng Ge; Hong-Wei Wang (Journal of Hazardous Materials, 2025)

Deep CO2 photoreduction by synergy of K+ doping and defective modulation over TiO2@K2Ti6O13 nanoribbon heterojunctions - Leiping Wang; Shuai Liu; Zun Man; Xiaorong Dai; Guangsuo Yu; Honglei Zhang; Hang Xiao; Yang Meng (Journal of Environmental Chemical Engineering, 2025)

Cation defective 2D NH2-MIL-125 enhances charge carrier dynamics for boosted photo-assisted lithium-oxygen batteries - Ningxuan Zhu; Shipeng Wan; Hongjin Shi; Ximei Lv; Fujiao Song; Yanbing Zhou; Yingchun Yu; Yuhui Chen; Man Ou (Chemical Engineering Journal, 2025)

Analysis and Control Techniques of Ultra-Shallow Buried Tunnels in Rain-Affected Backfill Soil - Peng-cheng Wang; Li-yang Su; Shu-jie Shang; Xiang-yu Jia; Wei-teng Li; Feng-chuan Jiang; Chun-qing Liu; Xin-jie Man (Geotechnical and Geological Engineering, 2025)

Two new acorane-type sesquiterpenoids from an endophytic Trichoderma harzianum associated with Paeonia lactiflora Pall - Yun-Peng Sun; Man-Li Zhang; Yang Yu; Ran Sun; Si-Rui Wang; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Dietary polysaccharides as gut health regulators: Structural characteristics and regulatory mechanism - Xinhong Wang; Chong Yu; Yunhan Li; Man Zhang; Juan Zhang; Haifeng Wang (Trends in Food Science & Technology, 2025)

Inhibition of placental 11β-HSD2 expression through cAMP/PKA signaling pathway induces intrauterine growth retardation - Caiyun Ge; Luting Yu; Man Fang; Xinrui Cao; Huijun Chen; Hui Wang (Toxicology Letters, 2025)

Rice bran protein fibril and chitin nanofiber complexes as a new material for fat substitution and saltiness enhancement - Yao Feng; Yu Zhang; Kai Huang; Sen Li; Hongwei Cao; Pengxiao Zhang; Man Wang; Zhenliang Sun; Xiao Guan (Food Chemistry, 2025)

Comprehensive insights into the mechanism of flavor formation in mandarin fish (Siniperca chuatsi) with inoculated fermentation - Ke-Xun Guo; Bin Hu; Yi Jiang; Zeng-Yong Li; Jun Qi; Man-Man Yu (Food Chemistry, 2025)

Assessment of in vitro digestion properties and prebiotic potential of chayote (Sechium edule) pectin - Qing Guo; Xiaoxue Wang; Chun Yang; Jie Yu; Qiang Cui; Xiaoyan Hou; Guanghui Shen; Man Zhou; Hong Liu; Anjun Chen; Zhiqing Zhang (Food Bioscience, 2025)

Bioactive ion engineered 3D printed TCP scaffolds promote vascularized bone regeneration in diabetic bone defects by restoring mitochondrial homeostasis - Yue He; Man Shu; Zhimin Li; Yun Liu; Ziyang Xu; Kelie Wang; Yu Zhang; Teliang Lu (Chemical Engineering Journal, 2025)

Altitude-induced shifts in bacterial communities involved in soil organic phosphorus cycling on Taibai mountain - Lianhao Zhou; Quan Zhou; Yanan Chen; Quanchao Zeng; Jun Li; Man Hu; Baohong Yu; Ruifeng Chen (CATENA, 2025)

Soil water regulates plant diversity response to gradual and step nitrogen addition - Jiu-Ying Pei; Yang Zheng; Yan Yu; Josep Peñuelas; Jordi Sardans; Man-Qiong Liu; Chao Fang; Wen-Bin Ke; Jian-Sheng Ye (Plant and Soil, 2025)

A TDCP-assisted partial ambiguity resolution method for GNSS Real-time kinematic positioning in challenging environment - Xiaosan Man; Wujiao Dai; Wenkun Yu; Yunxiang Jiang; Lan Li; Yong Liu (GPS Solutions, 2025)

Effectively mitigated eutrophication risk by strong biological carbon pump (BCP) effect in karst reservoirs - Wenke Zhang; Wanfa Wang; Sen Xu; Qingqing Sun; Wenhong Shi; Jiayi Man; Shengde Yu; Yujing Yang; Wenxin Wu; Xia Hu; Qixin Wu; Pan Wu; et al. (Water Research, 2025)

Government-involved urban meteorological networks (UMNs): A global review - Carmen Hau Man Wong; Yu Ting Kwok; Yueyang He; Edward Ng (Urban Climate, 2025)

Ligand-rich oxygen evolution electrocatalysts reconstructed from metal-organic frameworks for anion-exchange membrane water electrolysis - Shiqi Li; Weiwei Liu; Yi Shi; Tang Wang; Tianyang Liu; Xiang Xue; Rui Li; Man Qiao; Zhen-Yu Wu; Wang Zhang (Science Bulletin, 2025)

Ground-based MAX-DOAS observations of formaldehyde and glyoxal in Xishuangbanna, China - Yu Zhang; Xingwei Man; Sanbao Zhang; Li Liu; Fanhao Kong; Tao Feng; Rui Liu (Journal of Environmental Sciences, 2025)

Lipopeptide of Bacillus velezensis incorporated with silver nanoparticles into a functional coating for sweet cherry preservation - Minxin Mao; Jianyu Wang; Shunqing Hu; Man Zou; Yu Meng; Wenting Bao; Qian Zhang; Chifang Peng (Food Packaging and Shelf Life, 2025)

Dual-window emissive radiative cooling textiles with a PTFE/SiO2 bilayer coating for enhanced thermal management - Luxuan Zhang; Qinting Zhu; Yuting Zhou; Bo Xu; Man Zhou; Ping Wang; Qiang Wang; Yuanyuan Yu (Chemical Engineering Journal, 2025)

Roseateles cavernae sp. nov., a Bacterium Isolated from Freshwater of the Old Huanglong Cave in Yunnan Province, South-West China - Yu-Man Zhang; Qian Jiang; Mu-Yao Li; Qing-Yu Miao; Yi-Qing Li; Min Yin; Cui-Ping Miao; Shu-Kun Tang (Current Microbiology, 2025)

Plant diversity expands dietary niche breadth but facilitates dietary niche partitioning of co-occurring cattle and sheep - Man Xu; Yueqing Song; Yizhen Wang; Yonghuan Yue; Haoran Yu; Huixian Meng; Ling Wang (Agriculture, Ecosystems & Environment, 2025)

Corrigendum to “Probabilistic prediction of ship destinations based on traffic pattern awareness in maritime networks” [Ocean Eng. 316 (15 January 2025), 119933] - Liang Huang; Jiaci Wang; Yamin Huang; Man Zhu; Yuanqiao Wen; Yu Zhou (Ocean Engineering, 2025)

Antioxidant and antimicrobial PSE-like chicken protein isolate films loaded with oregano essential oil nanoemulsion for pork preservation - Chen-Yan Zhu; Ke Li; Yu Wang; Man-Ting Du; Bo Chen; Yun-Tao Wang; Yan-Fang Zhou; Yan-Hong Bai (Food Chemistry, 2025)

Microwave-assisted in-situ growth and performance promotion via the synergistic effect of ZnCoY tri-metal oxides (Y = Fe, Cu, Ni)/carbon nanofibers sorbent for H2S removal - Man Zhang; Xiaojun Xue; Yangjie Sun; Rongrong Jin; Jie Mi; Jiancheng Wang; Yu Feng (Chemical Engineering Journal, 2025)

Deciphering the role of extracellular polymeric substances in the adsorption of perfluorooctanoic acid during sludge alkaline fermentation: Experimental study and molecular dynamics simulation - Chengyu Gu; Sijia Ma; Fang Man; Yuexin Yu; Yuan Lin; Yi Xue; Yanru Wang; Hongqiang Ren; Ke Xu (Chemical Engineering Journal, 2025)

Identification of Dufulin photolysis and hydrolysis products in water using a 13C stable isotope assisted HPLC-HRMS strategy - Bochi Yu; Yanli Man; Gabriel Sigmund; Pingping Wang; Jun Xie; Wei Wang; Lan Zhang; Liangang Mao; Lizhen Zhu; Chi Wu; Xingang Liu (Water Research, 2025)

Similarity design method for soil–structure–water models in centrifugal shaking table tests - Yu Chen; Yan-Man Liu; Kun Wu; Xin Huang (Soil Dynamics and Earthquake Engineering, 2025)

Exogenous iron mitigates photo-facilitation of soil organic matter - Yongli Wen; Jiali Wu; Xueting Wen; Zhuoyue Zhang; Jian Wang; Guanghui Yu; Xinhua He; Maohong Xu; Man Cheng; Wenjuan Liu; Jian Xiao (Geochimica et Cosmochimica Acta, 2025)

Non-noble CeO2/CdS/NiS heterojunction for photoredox-catalyzed plastic waste selective synthesis and hydrogen production from natural seawater - Ziwen Wang; Qiuyu Wang; Zhe Yin; Man Zhang; Guoping Yu; Qingcheng Luo; Huanyu Chen; Binglin Tang; Kangzheng Li; Zhichao Zhang; Bo Lv (Fuel, 2025)

Extraction and immobilization of potato esterase and its application in the detection of potato glycoalkaloids - Qing Guo; Jing Li; Jie Yu; Qiang Cui; Xiaoyan Hou; Hong Liu; Man Zhou; Guanghui Shen; Zhiqing Zhang (Food Bioscience, 2025)

High-Voltage aqueous supercapacitors based on l-lysine pH Self-Buffering Coating-modified carbon cloth electrode - Ang Xu; Jie Gao; Huan Li; Xiyu Song; Bo Xu; Ying Liu; Yuanyuan Yu; Ping Wang; Qiang Wang; Man Zhou (Chemical Engineering Journal, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Regional abnormalities of white and gray matter in youths with conduct problems - Man Dong; Xiaodong Cheng; Yage Li; Shanling Ji; Hao Yu; Liangliang Ping; Chuanxin Liu; Cong Zhou (Brain Imaging and Behavior, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Quantifying the impact of land use changes on surface runoff in the Loess Plateau area of Northwest China by SWAT - Ai Wang; Jiangyu Wang; Benjie Luan; Man Zhang; Xu Wang; Ping Yu (Journal of Environmental Management, 2025)

Peroxiredoxin 6 is essential for the posttranslational activation of xanthine dehydrogenase in the uric acid synthesis of Bombyx mori - Tsuguru Fujii; Masato Hino; Toshiaki Fujimoto; Kohei Kakino; Yu Kaneko; Hiroaki Abe; Jae Man Lee; Takahiro Kusakabe; Toru Shimada (Insect Biochemistry and Molecular Biology, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Effect of metal–organic framework on hydrogen volume fraction in the oxygen-rich anode catalyst layer of proton exchange membrane water electrolyzer - Inku Kang; Sojin Lee; Won-Jong Choi; Siyeon Lee; Soonyong So; Duk Man Yu; Sang Jun Yoon; Dong-Won Kim; Kwan Woo Nam; Keun-Hwan Oh (Chemical Engineering Journal, 2025)

Dual functional Zn doped chitosan fibers restrain the challenge of anode and cathode in lithium-sulfur batteries - Dong Wang; Xianrui Bai; Jianzong Man; Hua Yang; Gaohui Du; Zhaoyang Wang; Pengfang Zhang; Lingyang Liu; Yu Gu (Chemical Engineering Journal, 2025)

MMCPT: A high-efficiency multiplexed metabolomics approach for rapid differential metabolite discovery using enzymatically cleavable chemoselective probe and TMT labeling - Lu Ye; Xue-Man Dong; Pei-Ran Miao; Yu-Xin Xu; Pu Wu; Ji-Lei Zhao; Hua-Min Zhang; Bing-Jun Zhou; Hui Zhang; Yuanyuan Lin; Jian-Liang Zhou (Chemical Engineering Journal, 2025)

Sequential adsorption-oxidation pulses for alternating electrochemical advanced pretreatment of wastewater containing tetracyclines - Junzhuo Cai; Shuhong Liu; Yu Bon Man; Xiaoxun Xu; Zhanbiao Yang; Changlian Xu; Guiyin Wang; Chengyi Huang; Gang Yang; Guochun Lv; Xin Qi; Ming Hung Wong; et al. (Chemical Engineering Journal, 2025)

Preparation, characterization and antibacterial investigation of water-soluble curcumin-chitooligosaccharide complexes - Xingchen Zhai; Yu Guo; Man Shang; Ziyan Guo; Difeng Ren; A.M. Abd El-Aty (Carbohydrate Polymers, 2025)

Accelerating repair of infected bone defects through post-reinforced injectable hydrogel mediated antibacterial/immunoregulatory microenvironment at bone-hydrogel interface - Zheng Wang; Ying Chu; Jingyi Du; Yan Hu; Huimin Wang; Hanghang Liu; Changying Yang; Man Wang; Jiabing Ran; Aixi Yu (Carbohydrate Polymers, 2025)

Diagnostic accuracy of Xpert MTB/RIF Ultra for detecting pulmonary tuberculosis and rifampicin resistance: a systematic review and meta-analysis - Man-Qing Wang; Ya-Fang Zheng; Yu-Qi Hu; Jin-Xia Huang; Zi-Xin Yuan; Zu-Yan Wu; Lu-Fang Huang; Chu-Ting Tang; Feng-Yi Zhang; Yan Chen; Jin-Ke He; Xu-Guang Guo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Correction: Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2025)

Composition, structure and comprehensive utilization of abalone shell: A review - Man-Yu Li; Yan-Chao Wu; Li Huang; Pi-Xian Gong; Hui-Jing Li (Sustainable Chemistry and Pharmacy, 2025)

Half-day (daytime and nighttime) precipitation extremes in China: Changes and attribution from 1981 to 2022 - Jiahao Han; Shibo Fang; Xiaomao Lin; Zhanhao Zhang; Man Li; Yanru Yu; Wen Zhuo; Xinyu Wang (Global and Planetary Change, 2025)

Deciphering the role and mechanism of rare earth element-rich biochar during anaerobic digestion of Dicranopteris pedata biomass - Ke-Xin Xu; Yu-Hong Qiu; Zhi-Biao Chen; Zu-Liang Chen; Peng Xiu; Zhi-Man Yang (Fuel, 2025)

Integrated transcriptomics and metabolomics reveal changes during Streptococcus thermophilus JM66 fermentation in milk: Fermentation characteristics, flavor profile, and metabolic mechanism - Shasha Cheng; Wenyan Li; Hanying Yang; Baochao Hou; Weilian Hung; Jian He; Chao Liang; Baolei Li; Yujun Jiang; Yu Zhang; Chaoxin Man (Food Research International, 2025)

Exploring the influence of lysine incorporation on the physicochemical properties of quinoa protein gels formed under microwave versus conventional heating conditions - Hongwei Cao; Xiaoxue Wang; Weibin Wu; Man Wang; Yu Zhang; Kai Huang; Hongdong Song; Zhenliang Sun; Xiao Guan (Food Research International, 2025)

Efficient lithium-oxygen batteries with low charge overpotential via solid-state design and thermal catalyst activation - Xing Tang; Yu Wang; Xiangyu Wen; Yuanguo Wu; Zining Man; Weiting Qi; Jiaqi Wang; Zhe Lü; Xingbao Zhu; Yugui Yao (Chemical Engineering Journal, 2025)

Multiscale modelling and infection probability of SARS-CoV-2 transmission in a typical lecture theatre - Mei Yan Chong; Hui An; Peng Cheng Wang; Chew Beng Soh; Szu-Cheng Chien; Edward Reuben Roch; Jun Jie Koh; Simon Ching Man Yu (Building and Environment, 2025)

Uncovering the mechanisms of diosmin in treating obesity-related kidney injury based on network pharmacology, molecular docking, and in vitro validation - Jun-Xing Zhu; Fan Chu; Wen-Man Zhao; Rui Shi; Zhi-Juan Wang; Xun-Liang Li; Yu-Yu Zhu; De-Guang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Evaluating overhanging slope failure mechanisms and rockfall trajectories through integrated UAV imagery and discrete element modeling - Meng-Chia Weng; Geng-Man Zhang; Yu-Yao Fu; Hoang-Khanh Le; Yu-Hui Kao (Landslides, 2025)
To evaluate the threat of rockfall from an overhanging slope above a bridge, this study proposes a comprehensive analysis procedure to assess the failure mechanisms of the slope and the associated rockfall trajectories. The analysis utilizes high-resolution point cloud data obtained through integrated UAV-based imagery technology, enabling a detailed evaluation of joint configurations and slope stability. The geometric reconstruction of unstable rock blocks, combined with stereographic projections, provides an in-depth analysis of potential failure modes. Discrete element modeling (DEM) is employed to simulate the failure processes and predict rockfall trajectories, with particular emphasis on the potential risks to the underlying bridge. The results indicate that rockfall events near the bridge are primarily driven by wedge-shaped failures, a finding confirmed by both the proposed inverted three-dimensional projection method and DEM simulations. The analysis identifies critical rock blocks near the bridge, underscoring the need for targeted mitigation strategies. This case study demonstrates the effectiveness of integrating UAV-derived data with DEM for assessing overhanging slope failures and managing rockfall risks in similar geological settings.

Tidal currents and atmospheric inorganic nitrogen contribute to diurnal variation of dissolved nutrients and chlorophyll a concentrations in Mirs Bay, Hong Kong - Ho Wen Lo; Xu Yu; Hanzhe Chen; Wai Ching Chu; Nga Man Chung; Sze Wing Lau; Jinjian Li; Shumin Liang; Kezheng Liao; Henry Charles James Thomas; Ziyan Wang; Zijing Zhang; et al. (Regional Studies in Marine Science, 2025)

Probabilistic prediction of ship destinations based on traffic pattern awareness in maritime networks - Liang Huang; Jiaci Wang; Yamin Huang; Man Zhu; Yuanqiao Wen; Yu Zhou (Ocean Engineering, 2025)

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

Predicting the efficiency of arsenic immobilization in soils by biochar using machine learning - Jin-Man Cao; Yu-Qian Liu; Yan-Qing Liu; Shu-Dan Xue; Hai-Hong Xiong; Chong-Lin Xu; Qi Xu; Gui-Lan Duan (Journal of Environmental Sciences, 2025)

Lactobacillus paracasei JY062 with its exopolysaccharide ameliorates intestinal inflammation on DSS-induced experimental colitis through TLR4/MyD88/NF-κB signaling pathway - Yue Su; Zhengying Cui; Chen Chen; Xinyan Yang; Yujun Jiang; Wei Zhang; Yu Zhang; Chaoxin Man (Food Bioscience, 2025)

Sound velocities and thermal equation of state of fcc-iron-nickel alloys at high pressure and high temperature: Implications for the cores of Moon and several planets - Siheng Wang; Sibo Chen; Man Xu; Tony Yu; Yanbin Wang; Baosheng Li (Earth and Planetary Science Letters, 2025)

Electronic modulation induced by doping V to accelerate the kinetics of oxygen electrocatalysis in direct methanol fuel cell - Man Guo; Fei Chen; Shuyan Yu; Quan Zhou; Chong Zhang; Shiquan Guo; Congju Li (Chemical Engineering Journal, 2025)

Nanodelivery of arsenic trioxide induces macrophage-governed cGAS-STING signaling to remodel immune microenvironment in hepatocellular carcinoma - Yuyao Li; Jia Shi; Shihan Yu; Xiaona Lu; Yue Li; Wenlan Zheng; Xuemei Zhang; Wurong Du; Chaoqun Zhao; Lingying Huang; Xiaojun Zhu; Man Li; et al. (Chemical Engineering Journal, 2025)

A Machine Learning-Enabled Real-Time temperature response system based on Polymer-Filler interactions for conductive network assembly - Yaqi Geng; Jialiang Zhou; Man Liu; Zexu Hu; Liping Zhu; Le Wang; Senlong Yu; Hengxue Xiang; Meifang Zhu (Chemical Engineering Journal, 2025)

Exosome-anchored scholzite conversion coating on titanium with long-term stability and immunomodulatory ability to enhance osteogenesis - Shimin Dai; Benzhao Huang; Peng Wang; Xiaoqing Lu; Shishuo Li; Zhibo Zhao; Xiao Li; Ningbo Li; Jiahui Yu; Zhentao Man; Wei Li; Bing Liu (Chemical Engineering Journal, 2025)

Structural characterization of two novel heteropolysaccharides from Catharanthus roseus and the evaluation of their immunological activities - Man Zhang; Jiapei Liao; Zhang Zhang; Hui Shi; Jixu Wu; Weijuan Huang; Chunlei Li; Liyan Song; Rongmin Yu; Jianhua Zhu (Carbohydrate Polymers, 2025)

Determinants of soundscape quality of communal open space in Hong Kong - Minqi LIN; Chi Kwan CHAU; Shiu Keung TANG; Wai Kit CHUNG; Ho Man YU (Building and Environment, 2025)

Effect of Post-transplant Dietary Restriction on Hematopoietic Reconstitution and Maintenance of Reconstitution Capacity of Hematopoietic Stem Cells - Si Tao; Xingxing Qiu; Yiting Wang; Rongrong Qiu; Chenghui Yu; Man Sun; Lulu Liu; Zhendong Tao; Liu Zhang; Duozhuang Tang (Stem Cell Reviews and Reports, 2025)
Hematopoietic cell transplantation (HCT) is an important therapy for many hematological malignancies as well as some non-malignant diseases. Post-transplant hematopoiesis is affected by multiple factors, and the mechanisms of delayed post-transplant hematopoiesis remain poorly understood. Patients undergoing HCT often suffer from significantly reduced food intake due to complications induced by preconditioning treatments. Here, we used a dietary restriction (DR) mouse model to study the effect of post-transplant dietary reduction on hematopoiesis and hematopoietic stem cells (HSCs). We found that post-transplant DR significantly inhibited both lymphopoiesis and myelopoiesis in the primary recipient mice. However, when bone marrow cells (BMCs) from the primary recipient mice were serially transplanted into secondary and tertiary recipient mice, the HSCs derived from the primary recipient mice, which were exposed to post-transplant DR, exhibited a much higher reconstitution capacity. Transplantation experiments with purified HSCs showed that post-transplant DR greatly inhibited hematopoietic stem cell (HSC) expansion. Additionally, post-transplant DR reshaped the gut microbiotas of the recipient mice, which inhibited inflammatory responses and thus may have contributed to maintaining HSC function. Our findings may have important implications for clinical work because reduced food intake and problems with digestion and absorption are common in patients undergoing HCT. Graphical Abstract

Manufacturing and characterisation of 3D-printed sustained-release Timolol implants for glaucoma treatment - Fathima Paleel; Mengqi Qin; Aristides D. Tagalakis; Cynthia Yu-Wai-Man; Dimitrios A. Lamprou (Drug Delivery and Translational Research, 2025)
Timolol maleate (TML) is a beta-blocker drug that is commonly used to lower the intraocular pressure in glaucoma. This study focused on using a 3D printing (3DP) method for the manufacturing of an ocular, implantable, sustained-release drug delivery system (DDS). Polycaprolactone (PCL), and PCL with 5 or 10% TML implants were manufactured using a one-step 3DP process. Their physicochemical characteristics were analysed using light microscopy, scanning electronic microscopy (SEM), differential scanning calorimetry (DSC) / thermal gravimetric analysis (TGA), and Fourier-transform infrared spectroscopy (FTIR). The in vitro drug release was evaluated by UV-spectrophotometry. Finally, the effect of the implants on cell viability in human trabecular meshwork cells was assessed. All the implants showed a smooth surface. Thermal analysis demonstrated that the implants remained thermally stable at the temperatures used for the printing, and FTIR studies showed that there were no significant interactions between PCL and TML. Both concentrations (5 & 10%) of TML achieved sustained release from the implants over the 8-week study period. All implants were non-cytotoxic to human trabecular cells. This study shows proof of concept that 3DP can be used to print biocompatible and personalised ocular implantable sustained-release DDSs for the treatment of glaucoma. Graphical Abstract

Altered spontaneous brain activity in patients with progressive-stage and end-stage chronic kidney disease: insights from dALFF analysis - Rujin Li; Mengchen Liu; Bin Xia; Ning Yang; Yanying Chen; Yi Yin; Kanghui Yu; Zichao Chen; Man Liang; Jiejing Li; Yunfan Wu (Metabolic Brain Disease, 2024)

Exploring the spatiotemporal evolution patterns of Urban Heat Island with a network-based approach - Kang Zou; Xinyu Yu; Man Sing Wong; Kai Qin; Rui Zhu; Songyang Li (Sustainable Cities and Society, 2024)

Screening of metal-modified biochars for practical phosphorus recovery - Man Li; Qian Xie; Fangxi Xu; Yan Zhang; Zechao Zhuang; Jiawei Xu; Hai Xiang; Yongfu Li; Yanjiang Cai; Zuliang Chen; Bing Yu (Science of The Total Environment, 2024)

Employing facile molten-salt strategy towards erbium ornamentation over CuInS2 for upgrading visible-light-driven hydrogen production and Cr(VI) reduction - Fulin Wang; Yanming Yang; Xiangwei Li; Weiya Huang; Kangqiang Lu; Shaobo Ouyang; Wentao Xiang; Chensheng Zhou; Changlin Yu; Man Zhou; Kai Yang (Journal of Environmental Chemical Engineering, 2024)

Lactobacillus paracasei JY062 and its exopolysaccharide enhance the intestinal barrier through macrophage polarization and Th17/Treg cell balance - Yue Su; Zhengying Cui; Xinyan Yang; Yujun Jiang; Wei Zhang; Yu Zhang; Chaoxin Man (Food Research International, 2024)

Enhanced detection of 4-nitrophenol in drinking water: ECL sensor utilizing velvet-like graphitic carbon nitride and molecular imprinting - Rui Xu; Yu Su; Hongfei Ji; Man Jiang; Ruizhong Zhang; Lan Ding; Yanhua Chen; Daqian Song (Food Chemistry, 2024)

Changes in whey protein produced by different sterilization processes and lactose content: Effects on glycosylation degree and whey protein structure - Jiaxin Zhang; Wen Tu; Yu Shen; Huabing Wang; Jiayue Yang; Ming Ma; Chaoxin Man; Wei Zhang; Qianyu Zhao; Yujun Jiang (Food Bioscience, 2024)

Visualization of strain rate based on mechanoluminescence tailing - Man Wang; Jianqiang Xiao; Jian Zhang; Lei Zhao; Yingdan Song; Zhichao Liu; Ting Wang; Xuhui Xu; Jie Yu (Chemical Engineering Journal, 2024)

Cavity-modulated visualization of dual magnetic coupling behavior for multifunctional Co/DMAOP composites - Man Li; Xiao Li; Jieyan Zhang; Haowei Zhou; Zhenfa Yu; Chao Li; Moustafa Adel Darwish; Tao Zhou; Shi-Kuan Sun; Di Zhou (Chemical Engineering Journal, 2024)

Optimizing food waste bioconversion with sodium selenite-enhanced Lucilia sericata maggots: a sustainable approach for chicken feed production and heavy metal mitigation - Chao Zheng; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Environmental Geochemistry and Health, 2024)

A Review of Life Cycle Assessment of Soil Remediation Technology: Method Applications and Technological Characteristics - Ning Ding; Xianhao Meng; Zhan Zhang; Jin Ma; Yongping Shan; Zhong Zhong; Haibo Yu; Man Li; Wentao Jiao (Reviews of Environmental Contamination and Toxicology, 2024)

SiC nanoparticles promote CO2 fixation and biomass production of Chlorella sorokiniana via expanding the abilities of capturing and transmitting photons - Kang Yang; Jin-lan Xia; Yu-xin Chen; Ren-man Zhu; Yang Jian; Chi Xiang; Zhen-yuan Nie; Hong-chang Liu (Algal Research, 2024)

Research progress and hotspot analysis of allergic rhinitis of pollen sensitisation - Yu Li; Hui Zhang; Man Yin; Xi Chen; Jianfeng Zhang; Xinrong Li (Aerobiologia, 2024)

New insights into the remediation of chromium-contaminated industrial electroplating wastewater by an innovative nano-modified biochar derived from spent mushroom substrate: Mechanisms, batch study, stability and application - Jingyi Wang; Yongduo Guan; Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Xuesheng Liu; Wei Wang; Yu Jin; Juanjuan Qu (Chemosphere, 2024)

In-field grading and sorting technology of apples: A state-of-the-art review - Jiangfan Yu; Zhao Zhang; Yifei Li; Wanjia Hua; Xinyu Wei; C. Igathinathane; Mustafa Mhamed; Wenqiang Zhang; Xiaoqiang Jiao; Liling Yang; Man Zhang; Han Li (Computers and Electronics in Agriculture, 2024)

Sensitivity analysis of building material, ground material, and tree parameters in microclimate simulations - Anh-Vu Le; Oi-Man Hip; Shun-Yu Yang; Ying-Chieh Chan (Urban Climate, 2024)

Recognition and acquisition of FakB2-loaded exogenous fatty acid (eFA) by a streptococcal FakA kinase - Haiyi Chen; Yu Shi; Man Huang; Ting Lu; Huimin Zhang; Chun Zhou; Tingjun Hou; Youjun Feng (Science Bulletin, 2024)

Urban tree health assessment using multifaceted remote sensing datasets: A case study in Hong Kong - Majid Nazeer; Man Sing Wong; Xinyu Yu; Coco Yin Tung Kwok; Qian Peng; YanShuai Dai (Remote Sensing Applications: Society and Environment, 2024)

Transcriptome analysis identified a transcriptional repressor, BES1-INTERACTING MYC-LIKE1 regulating rapid postharvest fruit softening of Actinidia arguta - Jian Wang; Xue-mei Lu; Mei-mei Kuang; Yuan-qiang Zhang; Yu-ping Man; Wen-qiu Wang; Yan-chang Wang (Postharvest Biology and Technology, 2024)

Corrigendum to “Association of urban green space with metabolic syndrome and the role of air pollution” [Landsc. Urban Plann. 248 (2024) 105100] - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Efficient chromium remediation using eco-innovative biochar in a novel two-stage upflow fixed bed system - Jingyi Wang; Yongduo Guan; Jiahui Fu; Xiaochen Liu; Mingfeng Guo; Junzhu Gao; Man Yang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Journal of Water Process Engineering, 2024)

Screening of saline-alkali tolerant microorganisms and their promoting effects on rice growth under saline-alkali stress - Jiahui Fu; Yawen Liu; Xiaochen Liu; Mingfeng Guo; Junzhu Gao; Man Yang; Xuesheng Liu; Wei Wang; Yu Jin; Juanjuan Qu (Journal of Cleaner Production, 2024)

Microwave heating intensified in-situ preparation of ZnO-based desulfurization sorbent with multi-stage structure and promoted performance - Yangjie Sun; Wenjian Feng; Man Zhang; Ying Yue; Jie Mi; Liping Chang; Jiancheng Wang; Yu Feng (Journal of Cleaner Production, 2024)

Foraging selectivity of co-grazing cattle and sheep varies differently with plant diversity - Man Xu; Yu Zhang; Yipeng Zhou; Shengnan Wang; Yingli Xiao; Xinyue Feng; Ling Wang (Journal of Environmental Management, 2024)

Enhancing Bone-Titanium integration through hydrogel coating mediated sequential M1/M2 polarization of interfacial macrophages - Zheng Wang; Honghan Yan; Man Wang; Yan Hu; Hao Zeng; Hanghang Liu; Huimin Wang; Changying Yang; Jin Liu; Aixi Yu; Jiabing Ran (Chemical Engineering Journal, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

Simulation of Rock Crack Propagation and Failure Behavior Based on a Mixed Failure Model with SPH - Man Hu; Qiuting Tan; Dianlei Feng; Yi Ren; Yu Huang (Rock Mechanics and Rock Engineering, 2024)

Excitotoxic Storms of Ischemic Stroke: A Non-neuronal Perspective - Xiao-man Yang; Hao Yu; Jia-xin Li; Na Li; Chong Li; Dong-han Xu; Hao Zhang; Tian-he Fang; Shi-jun Wang; Pei-yu Yan; Bing-bing Han (Molecular Neurobiology, 2024)

Photoelectron-transfer-effect grafting: Validation of a generalized strategy for fluorescence and photoelectrochemical dual-mode detection of hydrogen sulfide - Xiao-Jie Yu; Xiao-Yan Wan; Yu-Ting Shen; Deng-Bao Zhang; Xian-Jing Zhou; De-Man Han; Feng-Zao Chen (Analytica Chimica Acta, 2024)

Incorporation of laser-induced graphene with hierarchical NiCo layered double hydroxide nanosheets for electrochemical determination of glucose in food and serum - Man Huang; Lei Ye; Liwen Yu; Yuanyuan Zhang; Ting Zeng; Juan Yang; Fan Tian; Zhen Wu; Xiuhua Zhang; Chengguo Hu; Nianjun Yang (Analytica Chimica Acta, 2024)

Postglacial ocean methane release from the northern South China Sea - Mengyuan Wang; Xinyi Chen; Yu Liao; Lina Qin; Meiling Man; Guodong Jia; Ming Su (Quaternary Science Reviews, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Metabolism and transcriptional response mechanisms insight into the Lacticaseibacillus paracasei under the intervention of milk powder storage by-products - Yu Shen; Renyi Geng; Jian He; Baochao Hou; Weilian Hung; Xiaoyan Pei; Xu Wang; Chaoxin Man; Qianyu Zhao; Yujun Jiang (Food Bioscience, 2024)

Exploring Jiangshui-originated probiotic lactic acid bacteria as starter cultures: Functional properties and fermentation performances in pear juice - Du-xin Jin; Yu-xuan Jin; Wei Zhang; Wei Cao; Rui Liu; Man-gang Wu; Qing-feng Ge; Hai Yu (Food Bioscience, 2024)

Mechanism of Lacticaseibacillus rhamnosus JY027 alleviating hyperuricemia in mice through gut-kidney axis - Chao Miao; Kai Dong; Yu Shen; Yilin Sun; Wenyan Li; Chaoxin Man; Yu Zhang; Qianyu Zhao; Yujun Jiang (Food Bioscience, 2024)

Probing trace of intracellularly-originated hydrogen peroxide based Pt–Cd bimetallic nanozyme on an enzyme-free electrochemical sensor - Man Xu; Zhichao Yu; Qiaohua Wei; Dianping Tang (Analytica Chimica Acta, 2024)

Automatic maize seeding machine watering spray angle determination by using a novel index - Jiangfan Yu; Zhao Zhang; Xiaohang Liu; Kuifan Chen; Yunxia Li; Cannayen Igathinathane; Xiqing Wang; Man Zhang; Han Li; Tuan Ha (Computers and Electronics in Agriculture, 2024)

Mechanistic insights into the changes of biological activity and physicochemical characteristics in Lacticaseibacillus paracasei fortified milk powder during storage - Yu Shen; Chao Miao; Ming Ma; Zizhu Zhen; Jian He; Xiaoyan Pei; Yu Zhang; Chaoxin Man; Qianyu Zhao; Yujun Jiang (Food Chemistry, 2024)

Mechanical properties of prestressed tendon-planted glulam beam-column connections under cyclic loading - Man Xu; Yu Zhang; Shan Gao; Nan Guo (Engineering Structures, 2024)

OPA1 dominant optic atrophy – from disease mechanisms to novel therapies - Patrick Yu-Wai-Man (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Disruption of early embryonic development in mice by polymethylmethacrylate nanoplastics in an oxidative stress mechanism - Hyeong-Ju You; Yu-Jin Jo; Gyuri Kim; Jeongwoo Kwon; Seung-Bin Yoon; Changsic Youn; Yejin Kim; Man-Jong Kang; Wan-Seob Cho; Ji-Su Kim (Chemosphere, 2024)

Association of urban green space with metabolic syndrome and the role of air pollution - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Intergenerational toxicity of 17α-ethinylestradiol (EE2): Effects of parental exposure on early larval development and transcriptomic profiles in the Sydney rock oyster, Saccostrea glomerata - Rafiquel Islam; Richard Man Kit Yu; Wayne A. O’Connor; Xiao Lin; Keng Po Lai; Frederic D.L. Leusch; Geoff R. MacFarlane (Journal of Hazardous Materials, 2024)

Integration of engineering microbial consortium and boosting extracellular amylase of B. amyloliquefaciens for intensifying bioconversion of food waste into lipopeptides - Jia-Xuan He; Zheng-Jie Hou; Bin Qiao; Ming-Zhu Ding; Chun-Yang Cao; Yu-Miao Zhang; Qiu-Man Xu; Jing-Sheng Cheng (Journal of Environmental Chemical Engineering, 2024)

Removal of radioactive iodine by Cu2O prepared with PVP as an active agent: Role of crystal facets and oxygen vacancy in adsorption mechanisms - Xiao-Jun Dai; Kai-Wei Chen; Man-Li He; Kai Chen; Xin-Yu Zhou; Yi-Ting Chen; Chun-Hui Gong; Peng Wang; Ping Mao; Yi Yang (Chemical Engineering Journal, 2024)

Solvent-regulated synthesis of full-color fluorescent nitrogen/sulfur co-doped carbon quantum dots for anti-counterfeiting textiles - Yun Yuan; Xueming Bao; Leilei Wu; Man Zhou; Yuanyuan Yu; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Serum LDL Promotes Microglial Activation and Exacerbates Demyelinating Injury in Neuromyelitis Optica Spectrum Disorder - Man Chen; Yun-Hui Chu; Wen-Xiang Yu; Yun-Fan You; Yue Tang; Xiao-Wei Pang; Hang Zhang; Ke Shang; Gang Deng; Luo-Qi Zhou; Sheng Yang; Wei Wang; et al. (Neuroscience Bulletin, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune inflammatory demyelinating disease of the central nervous system (CNS) accompanied by blood-brain barrier (BBB) disruption. Dysfunction in microglial lipid metabolism is believed to be closely associated with the neuropathology of NMOSD. However, there is limited evidence on the functional relevance of circulating lipids in CNS demyelination, cellular metabolism, and microglial function. Here, we found that serum low-density lipoprotein (LDL) was positively correlated with markers of neurological damage in NMOSD patients. In addition, we demonstrated in a mouse model of NMOSD that LDL penetrates the CNS through the leaky BBB, directly activating microglia. This activation leads to excessive phagocytosis of myelin debris, inhibition of lipid metabolism, and increased glycolysis, ultimately exacerbating myelin damage. We also found that therapeutic interventions aimed at reducing circulating LDL effectively reversed the lipid metabolic dysfunction in microglia and mitigated the demyelinating injury in NMOSD. These findings shed light on the molecular and cellular mechanisms underlying the positive correlation between serum LDL and neurological damage, highlighting the potential therapeutic target for lowering circulating lipids to alleviate the acute demyelinating injury in NMOSD.

Probing rotaxane dynamics with 19F NMR/MRI: Unveiling the roles of mechanical bond and steric hindrance - Yu Li; Man Luo; Mou Jiang; Rui Zhou; Wanrong Yang; Shenhui Li; Fang Wang; Lijun Zhu; Pei He; Minghui Yang; Xin Zhou; Zhong-Xing Jiang; et al. (Analytica Chimica Acta, 2024)

Isophorone-based crystallization-induced-emission sensors detect proteome aggregation in live cells and tissues with breast cancer - Xiaomeng Jia; Di Shen; Jintai Deng; Kainan Wang; Xueqing Wang; Yijin Guo; Lu Sun; Hao Jin; Qiuxuan Xia; Huan Feng; Biao Jing; Jialu Sun; et al. (Analytica Chimica Acta, 2024)

Angiotensin-Converting Enzyme Insertion/Deletion Polymorphism and the Risk of Leukoaraiosis in a South Chinese Han Population: A Case–Control Study - Dong-can Mo; Xiao-ju Wu; Xiao-ling Li; Liu-yu Liu; Yi-ying Jiang; Guo-qiu Zhou; Li-jie Chen; Jiao-xing Li; Man Luo (Biochemical Genetics, 2024)

Analysis of phytochemical components of Tibetan medicine Pedicularis flava and Pedicularis muscicola by GC-MS and UHPLC-TOF-MS - Wentao Yu; Man Luo; Huan Wu; Yayun Yu; Junmao Li; Minzhen He; Yunlin Feng; Shilin Yang; Wugang Zhang; Min Yao (Natural Product Research, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Natural polysaccharide-dominated synthesis of MnO2 nanoparticles as textile coating for efficiently removing indoor bacteria and air pollutants - Xueming Bao; Yun Yuan; Zirong Li; Yuanyuan Yu; Li Cui; Man Zhou; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Chronic Fluoride Exposure Induces Ovarian Dysfunction and Potential Association with Premature Ovarian Failure in Female Rats - Xiaoke Tang; Hongjuan Li; Yali Wang; Li Zeng; Ling Long; Yajun Qu; Hui Yang; Xiaolin Zhang; Yanmin Li; Yanni Yu; Qi Zhou; Man Luo (Biological Trace Element Research, 2024)

Nucleic acid amplification-based strategy to detect foodborne pathogens in milk: a review - Lidong Pang; Xiaowen Pi; Xinyan Yang; Danliangmin Song; Xue Qin; Lihan Wang; Chaoxin Man; Yu Zhang; Yujun Jiang (Critical Reviews in Food Science and Nutrition, 2024)

AhR agonists screening and identification in indoor dust based on non-target chemical analysis by GC-Q-TOFMS and biological effect evaluation referring to ToxCast/Tox21 database - Chaoli Yuan; Yuqi Zeng; Xiaomin Yan; Jiwen Luo; Lixuan Zeng; Yu Bon Man; Bingyan Lan; Yuan Kang (Chemosphere, 2024)

Advances in apple’s automated orchard equipment: A comprehensive research - Mustafa Mhamed; Zhao Zhang; Jiangfan Yu; Yifei Li; Man Zhang (Computers and Electronics in Agriculture, 2024)

Applications of charcoal, activated charcoal, and biochar in aquaculture – A review - Chun Fung Wong; Uddin Md Saif; Ka Lai Chow; James Tsz Fung Wong; Xun Wen Chen; Yan Liang; Zhang Cheng; Yiu Fai Tsang; Ming Hung Wong; Yu Bon Man (Science of The Total Environment, 2024)

A new strategy based on a cascade amplification strategy biosensor for on-site eDNA detection and outbreak warning of crown-of-thorns starfish - Zongwu Wei; Xuzhe Zhang; Yingzhan Chen; Hongjie Liu; Shaopeng Wang; Man Zhang; Honglin Ma; Kefu Yu; Liwei Wang (Science of The Total Environment, 2024)

Two new pregnane glycosides from the flower buds of Dregea volubilis - Xiao-Dong Zhang; Bin Qiu; Jie Yu; Ni-Man Bao (Phytochemistry Letters, 2024)

Metabolic signatures of two scleractinian corals from the northern South China sea in response to extreme high temperature events - Shan Huang; Li Luo; Beihua Wen; Xurui Liu; Kefu Yu; Man Zhang (Marine Environmental Research, 2024)

Synthesis of carbon quantum dots via electrochemically-induced carbon dioxide nanobubbles exfoliation of graphite for heavy metal detection in wastewater - Yu Dong Yat; Henry Chee Yew Foo; Inn Shi Tan; Man Kee Lam; Pau Loke Show; Bryant Wei Liang Ng (Journal of Environmental Chemical Engineering, 2024)

Huge redshift of absorption edge in a novel Z-type Bi2Sn2O7/α-Bi2O3 junction for highly efficiently visible light degradation of norfloxacin and bisphenol AF - Man Yu; Kaitian Zuo; Bangfu Ding; Shukai Zheng; Lei Zhang; Liang Mao; Junying Zhang (Journal of Environmental Chemical Engineering, 2024)

Recent advances in the bovine β-casein gene mutants on functional characteristics and nutritional health of dairy products: Status, challenges, and prospects - Yilin Sun; Yixin Ding; Biqi Liu; Jinfeng Guo; Yue Su; Xinyan Yang; Chaoxin Man; Yu Zhang; Yujun Jiang (Food Chemistry, 2024)

Effect of complex prebiotics on Lactobacillus gasseri JM1 fermented soymilk: Physicochemical, flavor characteristics, and metabolites - Yaping Zheng; Wenfang Wu; Man Zhu; Yilin Sun; Dong Hu; Yujun Jiang; Yu Zhang; Chaoxin Man (Food Bioscience, 2024)

High-spatial resolution ground-level ozone in Yunnan, China: A spatiotemporal estimation based on comparative analyses of machine learning models - Xingwei Man; Rui Liu; Yu Zhang; Weiqiang Yu; Fanhao Kong; Li Liu; Yan Luo; Tao Feng (Environmental Research, 2024)

Hydrogen-bond tuned conjugated architectures for nitric oxide sensing in single-benzene framework: Advances and mechanistic insights - Feng-Zao Chen; Cun-Bin Du; Yi-Chao Wang; Jie Zhu; Ge Cheng; Kai-Bin Li; De-Man Han; Xiao-Yu Wu (Analytica Chimica Acta, 2024)

Berberine improves cognitive impairment by alleviating brain atrophy and promoting white matter reorganization in diabetic db/db mice: a magnetic resonance imaging-based study - Xin-yu Yang; Chun-jing Yang; Xiao-fang Wang; Lei Zhang; Zheng-yuan Shi; De-chun Jiang; Man-zhong Li (Metabolic Brain Disease, 2024)

Improving salt-tolerant artificial consortium of Bacillus amyloliquefaciens for bioconverting food waste to lipopeptides - Yu-Miao Zhang; Bin Qiao; Wei Shang; Ming-Zhu Ding; Qiu-Man Xu; Tian-Xu Duan; Jing-Sheng Cheng (Waste Management, 2024)

BDNF mimetics recover palmitic acid-induced injury in cardiomyocytes by ameliorating Akt-dependent mitochondrial impairments - Man-Ru Zhang; Bang-Yun Zuo; Yu-Chen Song; Dan-Dan Guo; Qing-Liu Li; Jin-Xiu Lyu; Hua Zhu; Jing Zhao; Peng-Zhou Hang (Toxicology and Applied Pharmacology, 2024)

Subtypes of Blastocystis in Tibetan Antelope (Pantholops hodgsonii) - Wei-Lan Yan; Xiao-Man Li; Si-Yuan Qin; Nian-Yu Xue; Yang Zou; Jing-Hao Li; Xiao-Xuan Zhang; Hong-Bo Ni (Research in Veterinary Science, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Transfer of building retrofitting evaluations for data-scarce conditions: An empirical study for Sweden to China - Qingpeng Man; Haitao Yu; Kailun Feng; Thomas Olofsson; Weizhuo Lu (Energy and Buildings, 2024)

A simple molecular design strategy for efficient deep-red thermally activated delayed fluorescence emitter - Yu-Xin Jin; Huanling Liu; Yue Zhao; Zi-Qi Chen; Shengkai Hu; Kai Zhang; Man-Keung Fung; Dong-Ying Zhou; Liang-Sheng Liao; Jian Fan (Chemical Engineering Journal, 2024)

Breathable and washable MXene@gallic acid cross-linked textile assisted by borax for personal multi-protection wearables - Biaobiao Yan; Xiaoting Liao; Tianlei Sun; Leilei Wu; Zhenfei Guo; Man Zhou; Yuanyuan Yu; Qiang Wang; Chaobin He; Ping Wang (Chemical Engineering Journal, 2024)

Synergistic improvement of humus formation in compost residue by fenton-like and effective microorganism composite agents - Jun Zhuo Cai; Ying Lan Yu; Zhan Biao Yang; Xiao Xun Xu; Guo Chun Lv; Chang Lian Xu; Gui Yin Wang; Xin Qi; Ting Li; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Bioresource Technology, 2024)

Prediction of cytochrome P450-mediated bioactivation using machine learning models and in vitro validation - Xin-Man Hu; Yan-Yao Hou; Xin-Ru Teng; Yong Liu; Yu Li; Wei Li; Yan Li; Chun-Zhi Ai (Archives of Toxicology, 2024)

Meta-analysis of the global prevalence and risk factors of Enterocytozoon bieneusi infection in pigs from 1999 to 2021 - Xiao-Man Li; Xiang-Yu Wang; Yong-Jie Wei; Jing Jiang; Yanan Cai; Xiao-Xuan Zhang; Xing Yang; Hongwei Cao (Preventive Veterinary Medicine, 2024)

Predictive trajectory tracking control for the USV in networked environments with communication constraints - Tao Lei; Yuanqiao Wen; Yi Yu; Kang Tian; Man Zhu (Ocean Engineering, 2024)

Transcriptomic analysis and oxidative stress induced by sodium dichloroisocyanurate in the intestine of Phascolosoma esculenta - Peifen Hu; Huijing Peng; Xiao Man; Zenghou Xing; Chongyang Wang; Congyan Yu; Jiamin Xing; Xueyu Yan; Hong Zhang; Mengqing Zeng; Lei Bao; Jie Zou; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Enhanced fatty acid storage combined with the multi-factor optimization of fermentation for high-level production of docosahexaenoic acid in Schizochytrium sp. - Yu-Lei Jia; Ying Zhang; Lu-Wei Xu; Zi-Xu Zhang; Ying-Shuang Xu; Wang Ma; Yang Gu; Xiao-Man Sun (Bioresource Technology, 2024)

Human health risk assessment based on a total diet study of daily mercury intake in Chengdu, China - Jun Bo Liu; Ya Jun Zhou; Fang Zhou Du; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Environmental Geochemistry and Health, 2024)

Research on satellite data-driven algorithm for ground-level ozone concentration inversion: case of Yunnan, China - Weiqiang Yu; Tao Feng; Xingwei Man; Huan Lin; Haonan Zhang; Rui Liu (Earth Science Informatics, 2024)

Psychromicrobium Xiongbiense sp. nov., an Actinobacterium Isolated from Forest Soil - Ling Zhu; Yu-Chen Wang; Le-Le Li; Xian-Min Huang; Man Zhu; Xiu Gao; Jian Cai (Current Microbiology, 2024)

Insights into the molecular mechanisms underlying the different heat tolerance of the scleractinian coral Pavona decussata - Man Zhang; Shan Huang; Li Luo; Xiaopeng Yu; Hao Wang; Kefu Yu; Shengping Zhong (Coral Reefs, 2024)

Hair Heavy Metals and Food Consumption in Residents of Chengdu: Factors, Food Contribution, and Health Risk Assessment - Hong-Xin Zeng; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Biological Trace Element Research, 2024)

Ecological and human health hazards of soil heavy metals after wildfire: A case study of Liangshan Yi autonomous prefecture, China - Lin Rao; Chao Zheng; Jian-Bin Chen; Jun-Zhuo Cai; Zhan-Biao Yang; Xiao-Xun Xu; Guo-Chun Lv; Chang-Lian Xu; Gui-Yin Wang; Yu-Bon Man; Ming-Hung Wong; Zhang Cheng (Chemosphere, 2024)

Microplastics removal mechanisms in constructed wetlands and their impacts on nutrient (nitrogen, phosphorus and carbon) removal: A critical review - Shaochen Zhang; Cheng Shen; Fuhao Zhang; Kejun Wei; Shengdao Shan; Yaqian Zhao; Yu Bon Man; Ming Hung Wong; Jin Zhang (Science of The Total Environment, 2024)

Per- and polyfluoroalkyl substances (PFASs) in Chinese surface water: Temporal trends and geographical distribution - Jie Wang; Cheng Shen; Jin Zhang; Guangyu Lou; Shengdao Shan; Yaqian Zhao; Yu Bon Man; Yuliang Li (Science of The Total Environment, 2024)

A microfluidic concentration gradient colorimetric system for rapid detection of nitrite in surface water - Yan Man; Kaijia Yu; Huimin Tan; Xinxin Jin; Jing Tao; Ligang Pan (Journal of Hazardous Materials, 2024)

Ordered heterostructured aerogel for multi-spectra stealth in microwave, infrared and visible light bands - Yu Gao; Qiang Wu; Lining Pan; Xueheng Zhuang; Feng Tian; Xingjie Jia; Qikui Man; Baogen Shen (Chemical Engineering Journal, 2024)

Enhanced piezoelectric performance of PVDF nanofibers by biomimicking the Spider’s long liquid transport - Man-Yu Qian; Chun-Hui He; Ji-Huan He (Chemical Engineering Journal, 2024)

Integrated analysis of natural glycans using a versatile pyrazolone-type heterobifunctional tag ANPMP - Yuxia Liu; Tong Yang; Jinqiao Rong; Jinhang Yuan; Lijuan Man; Ming Wei; Jiangbo Fan; Yao Lan; Yinchuan Liu; Guiping Gong; Yu Lu; Xuezheng Song; et al. (Carbohydrate Polymers, 2024)

Effects of sodium selenite, yeast selenium, and nano-selenium on toxicity, growth, and selenium bioaccumulation in Lucilia sericata maggots - Chao Zheng; Ming Hung Wong; Yu Bon Man; Zhang Cheng (Environmental Science and Pollution Research, 2024)

Ganoderma spp. polysaccharides are potential prebiotics: a review - Miao Zheng; Xiaowen Pi; Hongxuan Li; Shasha Cheng; Yue Su; Yu Zhang; Chaoxin Man; Yujun Jiang (Critical Reviews in Food Science and Nutrition, 2024)

Functional differentiation of size-fractionated biomass in the mixotrophic mainstream UASB-anammox process - Ya-Fei Cheng; Shu-Yang Fang; Shi-Man Liang; Jia-Qi Zhou; Yu Zhang; Zheng-Zhe Zhang; Ren-Cun Jin (Journal of Water Process Engineering, 2024)

Unique ternary Pd/NH2-MIL-125/CdIn2S4 composite expands the absorption range of visible light and improves H2 evolution efficiency - Man Zhang; Kangzheng Li; Zhe Yin; Zhichao Zhang; Qingcheng Luo; Binglin Tang; Guoping Yu; Tianding Hu; Shaoyun Shan (Journal of Environmental Chemical Engineering, 2024)

Experimental study on the mass burning rate and flame tilt angle of annular pool fires under cross air flow - Ping Huang; Rui Zhang; Chunxiang Liu; Xinyue Wu; Shanshan Chen; Jinhao Li; Man Li; Longxing Yu (Fuel, 2024)

Natural deep eutectic solvent: A novel and green mordant for the natural dye - Zhe Jiang; Guolin Zheng; Yifan Cui; Wenda Wang; Xianqin Shang; Yimin Wei; Man Zhou; Ping Wang; Yuanyuan Yu; Qiang Wang (Chemical Engineering Journal, 2024)

A novel algorithm for full-coverage daily aerosol optical depth retrievals using machine learning-based reconstruction technique - Xinyu Yu; Man Sing Wong; Majid Nazeer; Zhengqiang Li; Coco Yin Tung Kwok (Atmospheric Environment, 2024)

Two new thymol derivatives from Eupatorium fortunei - Jing Shi; Yan-peng Dai; Min Yuan; Xiao-man Sun; Chuan-jie Song; Yu-guo Liu (Natural Product Research, 2024)

Atelocollagen Scaffold Enhances Cartilage Regeneration in Osteochondral Defects: A Study in Rabbits - Ji-Chul Yoo; Man Soo Kim; Sueen Sohn; Sang Hun Woo; Yu Ri Choi; Andrew S. Kwak; Dong Shin Lee (Tissue Engineering and Regenerative Medicine, 2024)

Identifying priorities under highly heterogeneous environments through species distribution models to facilitate orchid conservation - Xue-Man Wang; Ying Tang; Xue-Feng Peng; Juan Wang; Shi-Qi Zhang; Yu Feng; Pei-Hao Peng (Biodiversity and Conservation, 2024)

Electron transfer processes associated with structural Fe in clay minerals - Chenglong Yu; Ao Qian; Yuxi Lu; Wenjuan Liao; Peng Zhang; Man Tong; Hailiang Dong; Qiang Zeng; Songhu Yuan (Critical Reviews in Environmental Science and Technology, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Large particle size boosting the engineering application potential of functional biochar in ammonia nitrogen and phosphorus removal from biogas slurry - Haohao Bian; Minyan Wang; Junhao Huang; Ruting Liang; Jiada Du; Chaochu Fang; Cheng Shen; Yu Bon Man; Ming Hung Wong; Shengdao Shan; Jin Zhang (Journal of Water Process Engineering, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Design of bifunctional ultrathin MnO2 nanofilm with laccase-like activity for sensing environmental pollutants containing phenol groups - Sheng-Tao Wu; Hui-Qi Su; Qian-Xiang Xiao; Zhi-Yu Qiu; Gang-Qiang Huang; Man-Ni He; Yi Ge; Cong-Hui Wang; Ying-Wu Lin (Journal of Hazardous Materials, 2024)

Aspartic acid/arginine enhance the stability of gelatin emulsions - Hui-min Yan; Yu Song; Man-man Yu; Xiu-ning Yao; Wen-wen Zhang; Ying Xu; Xue-qing Li; Yu-qin Xu; Shun Fang; Jun Qi; Guo-yuan Xiong; Chao Li; et al. (Journal of Food Engineering, 2024)

Experimental study on the sintering characteristics of biomass ash - Hairui Wang; Tuo Zhou; Xuemei Tan; Nan Hu; Yu Wang; Hairui Yang; Man Zhang (Fuel, 2024)

Rapid photothermal antibacterial and antifungal textiles through dynamic disulfide bond-assisted in-situ deposition of SeNPs - Leilei Wu; Xueming Bao; Zirong Li; Yuanyuan Yu; Ying Liu; Bo Xu; Man Zhou; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Quaternary-ammonium chitosan, a promising packaging material in the food industry - Yu-Long Qiu; Yixi Li; Gong-Liang Zhang; Hongshun Hao; Hong-Man Hou; Jingran Bi (Carbohydrate Polymers, 2024)

Impact of mineral dust photocatalytic heterogeneous chemistry on the formation of the sulfate and nitrate: A modelling study over East Asia - Xiao Li; Zechen Yu; Man Yue; Yaman Liu; Kan Huang; Xuguang Chi; Wei Nie; Aijun Ding; Xinyi Dong; Minghuai Wang (Atmospheric Environment, 2024)

Genomic and co-expression network analyses reveal candidate genes for oil accumulation based on an introgression population in Upland cotton (Gossypium hirsutum) - Jianjiang Ma; Bing Jia; Yingying Bian; Wenfeng Pei; Jikun Song; Man Wu; Wenkui Wang; Kashif; Shahzad; Li Wang; Bingbing Zhang; Pan Feng; et al. (Theoretical and Applied Genetics, 2024)

A longitudinal study on the change in sleep across three waves of the COVID-19 outbreaks in Hong Kong - Denise Shuk Ting Cheung; Branda Yee-Man Yu; Simon Ching Lam; Doris Yin Ping Leung; Ka-Fai Chung; Fiona Yan-Yee Ho; Shu-Cheng Chen; Wing-Fai Yeung (Sleep and Biological Rhythms, 2024)

Delineation of LNAPL plumes in a clay-rich site in Gyeongsangnam-do Province, South Korea: integration of geophysical survey data with borehole data and soil sampling information - Bitnarae Kim; In Seok Joung; Huieun Yu; Juyeon Jeong; Seo Young Song; Jeong-sul Son; Youngchul Yu; Jehyun Shin; Ho Young Jo; Man Jae Kwon; Myung Jin Nam (Environmental Monitoring and Assessment, 2024)

Biochar reduces uptake and accumulation of polycyclic aromatic hydrocarbons (PAHs) in winter wheat on a PAH-contaminated soil - Jinfeng WANG; Huanyu BAO; Yu Bon MAN; Jun CAI; Jia LI; Benhua SUN; Fuyong WU (Pedosphere, 2023)

One-pot derivatization/extraction coupled with liquid chromatography-tandem mass spectrometry for furfurals determination - Di Chen; Bin Wang; Xin-Li Xu; Xin-Miao Bu; Man-Yu Zhang; Xia Xu; Lei Yu; Nian Shi (Food Chemistry, 2023)

Amino carboxymethyl chitosan//dialdehyde starch/polyvinyl alcohol double-layer film loaded with ε-polylysine - Xiaoxia Chen; Yixi Li; Yu-Long Qiu; Gong-Liang Zhang; Hongshun Hao; Hong-Man Hou; Jingran Bi (Food Chemistry, 2023)

Formononetin attenuates high glucose-induced neurotoxicity by negatively regulating oxidative stress and mitochondrial dysfunction in Schwann cells via activation of SIRT3 - Wen Jiang; Ting Hu; Chen Ye; Man Hu; Qingqing Yu; Lijuan Sun; Jichao Liang; Yong Chen (Food and Chemical Toxicology, 2023)

Optimized faster R-CNN for oil wells detection from high-resolution remote sensing images - Zhibao Wang; Lu Bai; Guangfu Song; Yu Zhang; Mingyuan Zhu; Man Zhao; Liangfu Chen; Mei Wang (International Journal of Remote Sensing, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

Near-infrared light-enhanced enzymatic activity of laccase-platinum nanoparticles as a biosensor for colorimetric and visible detection of ascorbic acid - Guolin Zheng; Zhe Jiang; Yifan Cui; Man Zhou; Yuanyuan Yu; Ping Wang; Qiang Wang (Chemical Engineering Journal, 2023)

Do local governments capitalise on the spillover effect in the housing market? Quasi-experimental evidence from house purchase restrictions in China - Qing Yu; Eddie Chi-Man Hui; Jianfu Shen (Land Use Policy, 2023)

Cr(VI) removal and mechanism from simulated polluted groundwater by Klebsiella variicola H12-CMC-FeS@biochar assisted permeable reactive barrier - Meilian Man; Runlan Yu; Xiao Jiang; Zhiru Liu; Weimin Zeng (Journal of Water Process Engineering, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

Superhydrophobic, photothermal, and UV-resistant coatings obtained by polydimethylsiloxane treating self-healing hydrophobic chitosan-tannic acid surface for oil/water separation - Guolin Zheng; Yifan Cui; Zhe Jiang; Man Zhou; Yuanyuan Yu; Ping Wang; Qiang Wang (Chemical Engineering Journal, 2023)

Bioremediation of zinc and manganese in swine wastewater by living microalgae: Performance, mechanism, and algal biomass utilization - Xiao-Ya Liu; Yu Hong; Man Liang; Qing-Yu Zhai (Bioresource Technology, 2023)

Climatic controls on stable carbon and nitrogen isotope compositions of temperate grasslands in northern China - Yuntao Wu; Xiaodong Zhang; Zhaoliang Song; Changxun Yu; Man Liu; Yidong Wang; Qian Hao; Qiang Li; Xiangwei Zhao; Lele Wu; Xia Wang (Plant and Soil, 2023)

Stability control measures for roof cutting and NPR supporting of mining roadways in fault areas of kilometre-deep coal mine - Xiao-ming Sun; Jian Wang; Yong Zhang; Wen-chao Zhao; Zhi-biao Guo; Man-chao He; Feng Chen; Cheng-yu Miao (Journal of Mountain Science, 2023)

AI-IoT integrated framework for tree tilt monitoring: A case study on tree failure in Hong Kong - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau (Agricultural and Forest Meteorology, 2023)

Ozone catalytic oxidation of toluene over triple perovskite-type catalysts modified with KMnO4 - Hsin Tzu Chuang; Run Yu Liu; Minh Man Trinh; Moo Been Chang (Environmental Science and Pollution Research, 2023)

Functional factors, nutritional value and development strategies of Cornus:A review - Zheng Liu; Yu Liu; Shuli Man; Lanping Guo; Xia Li; Wenyuan Gao (Trends in Food Science & Technology, 2023)

Assessing life-cycle GHG emissions of recycled paper products under imported solid waste ban in China: A case study - Huijing Deng; Dingfan Zhang; Huajun Yu; Yi Man; Yutao Wang (Science of The Total Environment, 2023)

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

An integrated approach for examining urban fragmentation in metropolitan areas: Implications for sustainable urban planning - Peiheng Yu; Esther H.K. Yung; Edwin H.W. Chan; Man Sing Wong; Siqiang Wang; Yiyun Chen (Journal of Cleaner Production, 2023)

Open space fragmentation in Hong Kong's built–up area: An integrated approach based on spatial horizontal and vertical equity lenses - Peiheng Yu; Edwin H.W. Chan; Esther H.K. Yung; Man Sing Wong; Yiyun Chen (Environmental Impact Assessment Review, 2023)

Gypenosides suppress hepatocellular carcinoma cells by blocking cholesterol biosynthesis through inhibition of MVA pathway enzyme HMGCS1 - Man-Yu Xiao; Fang-Fang Li; Peng Xie; Yan-Shuang Qi; Jin-Bo Xie; Wen-Jing Pei; Hao-Tian Luo; Mei Guo; Yu-Long Gu; Xiang-Lan Piao (Chemico-Biological Interactions, 2023)

Enhancing fengycin production in the co-culture of Bacillus subtilis and Corynebacterium glutamicum by engineering proline transporter - Geng-Rong Gao; Si-Yu Wei; Ming-Zhu Ding; Zheng-Jie Hou; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng; Ying-Jin Yuan (Bioresource Technology, 2023)

A Simple Fabrication Method of Chloride Sensor Based on Hot-Dipped Ag/AgCl@PVC for Water Quality Monitoring - Gyong Il Kim; Gum Chol Kim; Chol Man Choe; Song Chol Yu; Hyon Chol Kim (Water, Air, & Soil Pollution, 2023)

Coal and rock dynamic disaster prevention and control technology in the large mining face of a deep outburst mine - Jianguo Zhang; Man Wang; Hongwei Zhou; Dongming Zhang; Beichen Yu; Chongyang Wang; Yujie Wang (Frontiers of Earth Science, 2023)

Daphnane-type diterpenoids from Stellera chamaejasme L. and their inhibitory activity against hepatocellular carcinoma cells - Zhuo-Yang Cheng; Jing-Xian Ren; Xiao-Bian Xue; Man Wang; Xiao-Qi Yu; Bin Lin; Guo-Dong Yao; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Simulation of non-cohesive soil turning based on an SPH model - Dianlei Feng; Can Yi; Man Hu; Tao Gao; Yu Huang (Computers and Geotechnics, 2023)

Crop productivity and soil inorganic carbon change mediated by enhanced rock weathering in farmland: A comparative field analysis of multi-agroclimatic regions in central China - Fuxing Guo; Yanping Wang; Haoyong Zhu; Chuangye Zhang; Haowei Sun; Zhuling Fang; Jing Yang; Linsen Zhang; Yan Mu; Yu Bon Man; Fuyong Wu (Agricultural Systems, 2023)

Perylene diimide/iron phthalocyanine Z-scheme heterojunction with strong interfacial charge transfer through π-π interaction: Efficient photocatalytic degradation of tetracycline hydrochloride - Kaiyang Shi; Man Zhou; Fulin Wang; Xiangwei Li; Weiya Huang; Kangqiang Lu; Kai Yang; Changlin Yu (Chemosphere, 2023)

Arsenic exposure incurs hyperglycemia mediated by oxidative damage in urban adult population: A prospective cohort study with three repeated measures - Yongfang Zhang; Min Zhou; Ruyi Liang; Linling Yu; Man Cheng; Xing Wang; Bin Wang; Weihong Chen (Environmental Research, 2023)

A photothermal cellulose-based material for rapid anti-bacteria and HCHO removal via sequential formation of MnO2 coatings and amine-quinone networks - Xueming Bao; Leilei Wu; Yuanyuan Yu; Bo Xu; Li Cui; Man Zhou; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2023)

OsTST1, a key tonoplast sugar transporter from source to sink, plays essential roles in affecting yields and height of rice (Oryza sativa L.) - Man-Yu Yang; Xiu Yang; Zhen Yan; Qing Chao; Jie Shen; Guang-Hou Shui; Peng-Mei Guo; Bai-Chen Wang (Planta, 2023)

TIGAR Protects Cochlear Hair Cells against Teicoplanin-Induced Damage - Qiongmin Zhang; Zhiqun Yao; Fang Chen; Xue Wang; Man Wang; Junze Lu; Yu Meng; Lei Xu; Yuechen Han; Wenwen Liu; Haibo Wang (Molecular Neurobiology, 2023)
Teicoplanin is a glycopeptide antibiotic used to treat severe staphylococcal infections. It has been claimed that teicoplanin possesses ototoxic potential, although its toxic effects on cochlear hair cells (HCs) remain unknown. The TP53-induced glycolysis and apoptosis regulator (TIGAR) plays a crucial role in promoting cell survival. Prior research has demonstrated that TIGAR protects spiral ganglion neurons against cisplatin damage. However, the significance of TIGAR in damage to mammalian HCs has not yet been investigated. In this study, firstly, we discovered that teicoplanin caused dose-dependent cell death in vitro in both HEI-OC1 cells and cochlear HCs. Next, we discovered that HCs and HEI-OC1 cells treated with teicoplanin exhibited a dramatically decrease in TIGAR expression. To investigate the involvement of TIGAR in inner ear injury caused by teicoplanin, the expression of TIGAR was either upregulated via recombinant adenovirus or downregulated by shRNA in HEI-OC1 cells. Overexpression of TIGAR increased cell viability, decreased apoptosis, and decreased intracellular reactive oxygen species (ROS) level, whereas downregulation of TIGAR decreased cell viability, exacerbated apoptosis, and elevated ROS level following teicoplanin injury. Finally, antioxidant therapy with N-acetyl-L-cysteine decreased ROS level, prevented cell death, and restored p38/phosphorylation-p38 expression levels in HEI-OC1 cells injured by teicoplanin. This study demonstrates that TIGAR may be a promising novel target for the prevention of teicoplanin-induced ototoxicity.

Selenium toxicity and bioaccumulation in selenium-enriched fly (Chrysomya megacephala) maggots - Rui Jie Peng; Chao Zheng; Zhan Biao Yang; Xiao Xun Xu; Ming Hung Wong; Yu Bon Man; Zhang Cheng (Environmental Geochemistry and Health, 2023)

Failure mechanism and control countermeasures of surrounding rock at deep large section chamber intersection in the Wanfu Coal Mine - Xiao-ming Sun; Zhen-min Qi; Yong Zhang; Cheng-yu Miao; Cheng-wei Zhao; Man-chao He (Journal of Mountain Science, 2023)

Meta-analysis reveals cyanotoxins risk across African inland waters - Xu Zhao; Ying Liu; Yu-Ming Guo; Chi Xu; Liang Chen; Geoffrey A. Codd; Jun Chen; Ying Wang; Pu-Ze Wang; Li-Wei Yang; Long Zhou; Yan Li; et al. (Journal of Hazardous Materials, 2023)

Effect of low temperature on the resistance of Listeria monocytogenes and Escherichia coli O157:H7 to acid electrolyzed water - Man Yu; Chunling Jiang; Yuanyuan Meng; Fan Wang; Jiang Qian; Fulin Fei; Zhenjie Yin; Wei Zhao; Yong Zhao; Haiquan Liu (Food Research International, 2023)

The potential role of plasma miR-4301 in PM2.5 exposure-associated lung function reduction - Jiahao Song; Man Cheng; Bin Wang; Min Zhou; Zi Ye; Lieyang Fan; Linling Yu; Xing Wang; Jixuan Ma; Weihong Chen (Environmental Pollution, 2023)

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

MgFe-LDH@biochars for removing ammonia nitrogen and phosphorus from biogas slurry: Synthesis routes, composite performance, and adsorption mechanisms - Haohao Bian; Minyan Wang; Jialin Han; Xiaopiao Hu; Honglei Xia; Lei Wang; Chaochu Fang; Cheng Shen; Yu Bon Man; Ming Hung Wong; Shengdao Shan; Jin Zhang (Chemosphere, 2023)

Toxicity mechanism of peri-implantation pesticide beta-cypermethrin exposure on endometrial remodeling in early pregnant mice - Yong-Jiang Zhou; Qian-Feng Qiao; Li-Qing Wang; Tao-Yu Sheng; Man-Xue Cui; Qi-Duo Chen; Can-Yang Wang; Yun-Xiao Zhang (Toxicology, 2023)

Unexpected enrichment of antibiotic resistance genes and organic remediation genes in high-altitude lakes at Eastern Tibetan Plateau - Yiwei Lu; Man Wang; Chunyan Yu; Qiong Wu; Zhendu Mao; Huabing Li; Lijuan Ren; Jin Zeng; Peng Xing; Li-Jun Zhou; Shiqiang Wan; Qinglong L. Wu (Science of The Total Environment, 2023)

Effects of dietary supplementation with saccharicterpenin alleviates diarrhea of piglets - Man Wang; Bing Yu; Jun He; Jie Yu; Yuheng Luo; Junqiu Luo; Xiangbing Mao; Daiwen Chen (Livestock Science, 2023)

High-efficiency continuous-flow microwave heating system based on metal-ring resonant structure - Man Liu; Danfeng Zhou; Yu Peng; Zhengming Tang; Kama Huang; Tao Hong (Innovative Food Science & Emerging Technologies, 2023)

Analysis of texture properties and water-soluble fraction proteome of sea cucumber body wall with different boiling heating treatment - Min Zhang; Yu-Xin Liu; Zi-Xuan Wu; Guan-Hua Zhao; Liang Song; Peng-Fei Jiang; Man-Man Yu; Da-Yong Zhou (Food Chemistry, 2023)

The effects of pulsed electric fields treatment on the structure and physicochemical properties of dialdehyde starch - Ying Li; Jin-Hua Wang; Yu Han; Fu-Hao Yue; Xin-An Zeng; Bo-Ru Chen; Man-Qin Zeng; Meng-Wai Woo; Zhong Han (Food Chemistry, 2023)

Electronic and structural engineering of supported single atomic layer, low-nuclearity palladium catalysts for conversion of levulinic acid to 1,4-pentanediol - Xiaowen Lu; Tingting Luo; Mingyang Zhang; J Hugh Horton; Qiong Wu; Wei Wu; Man Qiao; Yu Wang; Zhijun Li (Chemical Engineering Journal, 2023)

Porous carbon nanofibers supported Zn@MnO sorbents with high dispersion and loading content for hot coal gas desulfurization - Yu Feng; Man Zhang; Yangjie Sun; Chunyan Cao; Jiancheng Wang; Mingzheng Ge; Weilong Cai; Jie Mi; Yuekun Lai (Chemical Engineering Journal, 2023)

Novel incomplete phase transition from α-Bi2O3 to γ-Bi2O3 constructing dual interfaces contacts with BaTiO3 for highly efficient degradation of antibiotics - Man Yu; Bangfu Ding; Jiawei Wu; Shun Zheng; Xin Qian; Lei Zhang; Shukai Zheng; Liang Mao; Junying Zhang (Chemical Engineering Journal, 2023)

Identifying the airport as a key urban VOC source in the Pearl River Delta, China - Bo Zhu; Li-Ming Cao; Shi-Yong Xia; Ying-Bo Niu; Han-Yang Man; Ke Du; Kuangyou Yu; Xiao-Feng Huang (Atmospheric Environment, 2023)

Lipid peroxidation mediates the association between iron overload and liver injury: cross-sectional and longitudinal analyses in general Chinese urban adults - Xing Wang; Bin Wang; Man Cheng; Linling Yu; Wei Liu; Xiuquan Nie; Mengyi Wang; Min Zhou; Weihong Chen (Environmental Science and Pollution Research, 2023)

Abiotic transformation of kresoxim-methyl in aquatic environments: Structure elucidation of transformation products by LC-HRMS and toxicity assessment - Yanli Man; Chi Wu; Bochi Yu; Liangang Mao; Lizhen Zhu; Lan Zhang; Yanning Zhang; Hongyun Jiang; Shankui Yuan; Yongquan Zheng; Xingang Liu (Water Research, 2023)

A new series of IDO1 inhibitors derived from microbial metabolites - Jingtong Zhu; Man Yu; Wenbin Shen; Xiao Ren; Haizhou Zheng; Yunlong Mu; Xinhua Lu; Lili Zhai (Phytochemistry Letters, 2023)

Overexpression of cotton Trihelix transcription factor GhGT-3b_A04 enhances resistance to Verticillium dahliae and affects plant growth in Arabidopsis thaliana - Haoming Mao; Wenqing Zhang; Junyuan Lv; Jiaxiang Yang; Shuxian Yang; Bing Jia; Jikun Song; Man Wu; Wenfeng Pei; Jianjiang Ma; Bingbing Zhang; Jinfa Zhang; et al. (Journal of Plant Physiology, 2023)

Immune response and protective efficacy of mannosylated polyethylenimine (PEI) as an antigen delivery vector, administered with a Streptococcus agalactiae DNA vaccine in Nile tilapia (Oreochromis niloticus) - Xin-Jin Chen; Man-Yu Huang; Eakapol Wangkahart; Jia Cai; Yu Huang; Ji-chang Jian; Bei Wang (Fish & Shellfish Immunology, 2023)

Offspring of metal contaminated saltmarsh (Juncus acutus) exhibit tolerance to the essential metal Zn but not the nonessential metal Pb - Md Rushna Alam; Mohammad Mahmudur Rahman; Richard Man Kit Yu; Geoff R. MacFarlane (Environmental Pollution, 2023)

Asymmetric coordinated single-atom Pd sites for high performance CO2 electroreduction and Zn–CO2 battery - Jiani Li; Li-Wei Chen; Yu-Chen Hao; Man Yuan; Jianning Lv; Anwang Dong; Shuai Li; Hongfei Gu; An-Xiang Yin; Wenxing Chen; Pengfei Li; Bo Wang (Chemical Engineering Journal, 2023)

Biological Characteristics of Listeria monocytogenes Following Deletion of TatD-like Protein Gene - Chuan Yu; Hefan Dong; Qi Li; Xiaoli Wang; Fuchao Mao; Man Qian; Junhui Niu; Xiangchao Cheng; Chengshui Liao (Current Microbiology, 2023)

Restored vegetation is more resistant to extreme drought events than natural vegetation in Southwest China - Ying Liu; Zhi Ding; Yanan Chen; Fengqin Yan; Pujia Yu; Weidong Man; Mingyue Liu; He Li; Xuguang Tang (Science of The Total Environment, 2023)

Differences in selenium concentration and bioavailability between paddy and dryland soils of China: A study based on literature collection and field sampling - Yuanzhe Ma; Nanchun Zhang; Yanan Li; Haolin Zhao; Fei Zhou; Mingyue Xue; Lihui Lyu; Jing Yang; Yu Ban Man; Fuyong Wu; Dongli Liang (Journal of Hazardous Materials, 2023)

An improved method of MgFe-layered double hydroxide/ biochar composite synthesis - Haohao Bian; Cheng Shen; Wanpeng Liu; Yu Bon Man; Ming Hung Wong; Peter Christie; Shengdao Shan; Minyan Wang; Jin Zhang (Journal of Cleaner Production, 2023)

Prediction of instantaneous yield of bio-oil in fluidized biomass pyrolysis using long short-term memory network based on computational fluid dynamics data - Hanbin Zhong; Zhenyu Wei; Yi Man; Shaowei Pan; Juntao Zhang; Ben Niu; Xi Yu; Yi Ouyang; Qingang Xiong (Journal of Cleaner Production, 2023)

Cross-domain landslide mapping from large-scale remote sensing images using prototype-guided domain-aware progressive representation learning - Xiaokang Zhang; Weikang Yu; Man-On Pun; Wenzhong Shi (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Wildfire activity driven by the 405-kyr orbital climate cycles in the Middle Jurassic - Zhihui Zhang; Dawei Lv; Man Lu; Zicheng Yu; Yuan Gao; Tiantian Wang; Jie Gao; Chengshan Wang (Global and Planetary Change, 2023)

Exploring the apparent properties and Q-markers for quality control of Cornus officinalis - Yu Liu; Yingfang Cui; Xv Liang; Shuli Man; Xia Li; Lorenzo Pecoraro; Giuseppe Venturella; Wenyuan Gao (Food Chemistry, 2023)

Impact of casein-to-whey protein ratio on gastric emptying, proteolysis, and peptidome profile of fermented milk during in vitro dynamic gastrointestinal digestion in preschool children - Hongyan Zhang; Sufang Duan; Yang Yu; Ren'an Wu; Jingjing Wang; Xiao Dong Chen; Ignatius Man-Yau Szeto; Peng Wu; Yan Jin (Food Chemistry, 2023)

Differences in texture and digestive properties of different parts in boiled abalone muscles - Man-Man Yu; Ying-Chen Fan; De-Yang Li; Yu-Xin Liu; Peng-Fei Jiang; Da-Yong Zhou; Bei-Wei Zhu (Food Chemistry, 2023)

A simulation-aided approach in examining the viability of passive daylighting techniques on inclined windows - Ya Hui Teo; Jun Hong Yap; Hui An; Nenggang Xie; Jie Chang; Simon Ching Man Yu; Wai Ching Poon; Limao Zhang; Kang Hao Cheong (Energy and Buildings, 2023)

Gas hydrate nucleation and growth in a micro-reactor: Effect of individual component separated from the crude oil in the South China Sea - Yu Feng; Man Li; Yuze Han; Qingping Li; Xin Lv; Jiafei Zhao; Lei Yang; Yanzhen Liu; Yongchen Song (Chemical Engineering Journal, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Involvement of purinergic P2Y1R in antidepressant-like effects of electroacupuncture treatment on social isolation stress mice - Lingling Yu; Yao Wang; Hong Zhang; Man Li; Guang Chen; Jiahuan Hao; Minjie Xie (Purinergic Signalling, 2023)

Fabrication of In–S-co-doped two-dimensional BiOCl coupling with surface hydroxylation toward simultaneously efficient charge separation and redox capability for photocatalytic water remediation - Tingfang Xie; Shaodong Sun; Yu Guo; Yongguang Luo; Man Yang; Bian Yang; Jie Cui (Chemosphere, 2023)

Simultaneous sludge minimization and membrane fouling mitigation in membrane bioreactors by using a microaerobic - Settling pretreatment module - Yi Zuo; Yanjun Shao; Lihua Wang; Yiyue Sun; Ying An; Lu-Man Jiang; Nan Yu; Rujie Hao; Chuanting Zhou; Jun Tao; Zhen Zhou (Journal of Environmental Management, 2023)

Lightweight chitosan-derived carbon/rGO aerogels loaded with hollow Co1-Ni O nanocubes for superior electromagnetic wave absorption and heat insulation - Yu Gao; Zhenkuang Lei; Lining Pan; Qiang Wu; Xueheng Zhuang; Guoguo Tan; Mingqiang Ning; Qikui Man (Chemical Engineering Journal, 2023)

Atomically dispersed single ruthenium sites anchored on bismuth tungstate with synergistic geometric and electronic effects for epoxidation of trans-stilbene - Xiuli Dong; Chun Wang; Mingyang Zhang; Siqi Ji; Leipeng Leng; J. Hugh Horton; Hongliang Dong; Man Qiao; Yu Wang; Jiangwei Zhang; Zhijun Li (Chemical Engineering Journal, 2023)

New (4 → 2)-abeo-clerodane diterpenoids from the Polyalthia laui and their chemotaxonomic significance - Zhang-Xin Yu; Xin-Ming Song; Mu-Yuan Li; Man-Man Zhang; Li-Zhu Huang; Xiao-Bao Li (Biochemical Systematics and Ecology, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Substituting fish meal with a bacteria protein (Methylococcus capsulatus, Bath) grown on natural gas: Effects on growth non-specific immunity and gut health of spotted seabass (Lateolabrax maculatus) - Man-han Yu; Xue-shan Li; Jia Wang; Matt Longshaw; Kai Song; Ling Wang; Chun-xiao Zhang; Kang-le Lu (Animal Feed Science and Technology, 2023)

Monitoring of tree tilt motion using lorawan-based wireless tree sensing system (IoTT) during super typhoon Mangkhut - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau; Kuan-Fu Liu; Billy Chi Hang Hau (Agricultural and Forest Meteorology, 2023)

Multi-spatiotemporal AOD trends and association with land use changes over the Guangdong-Hong Kong-Macao Greater Bay Area during 2001–2021 - Xinyu Yu; Man Sing Wong; Chun-Ho Liu (Environmental Science and Pollution Research, 2023)

Using fly larvae to convert food waste for growing Oujiang color common carps: health risk assessment of polycyclic aromatic hydrocarbons - Meng Gao; Zhan-Biao Yang; Xiao-Xun Xu; Jun-Ren Xian; Yuan-Xiang Yang; Song Yang; Yu-Bon Man; Zhang Cheng (Environmental Science and Pollution Research, 2023)

Efficiency analysis and evaluation of centrifugal variable-rate fertilizer spreading based on real-time spectral information on rice - Yinyan Shi; Man Chen; Xiaochan Wang; Haolin Yang; Haiming Yu; Xiangze Hao (Computers and Electronics in Agriculture, 2023)

Exploring the role of protein DJ-1 in quality of pale, soft and exudative (PSE) and red, firm and non-exudative (RFN) pork during post-mortem aging - Rui Liu; Keyue Li; Tianyi Yang; Lun Yang; Man Qin; Hai Yu; Mangang Wu; Qingfeng Ge; Wenbin Bao; Shenglong Wu (Food Chemistry, 2023)

Stitching electron localized heptazine units with “carbon patches” to regulate exciton dissociation behavior of carbon nitride for photocatalytic elimination of petroleum hydrocarbons - Qi Guo; Yuning Wu; Linhong Xia; Xue-Fang Yu; Kaisheng Zhang; Yujie Du; Lixue Zhang; Hua Tang; Jianbo Cheng; Jianpeng Shang; Yanhua Peng; Zhuo Li; et al. (Chemical Engineering Journal, 2023)

Plants boost pyrrhotite-driven nitrogen removal in constructed wetlands - Cheng Shen; Liti Su; Yaqian Zhao; Wenbo Liu; Ranbin Liu; Fuhao Zhang; Yun Shi; Jie Wang; Qiuqi Tang; Yan Yang; Yu Bon Man; Jin Zhang (Bioresource Technology, 2023)

5′-Nucleotidase is dispensable for the growth of Salmonella Typhimurium but inhibits the bactericidal activity of macrophage extracellular traps - Man Qian; Ke Xu; Mengke Zhang; Junhui Niu; Tianxiang Zhao; Xiaoli Wang; Yanyan Jia; Jing Li; Zuhua Yu; Lei He; Yinju Li; Tingcai Wu; et al. (Archives of Microbiology, 2023)

Aaptamine derivatives with CDK2 inhibitory activities from the South China Sea sponge Aaptos suberitoides - Qian-Qian He; Yu-Qing Man; Kun-Lai Sun; Li-Juan Yang; Yan Wu; Jing Du; Wei-Wei Chen; Juan-Juan Dai; Na Ni; Shuang Miao; Kai-Kai Gong (Natural Product Research, 2022)

Distribution characteristics and risk assessment of heavy metals in seawater, sediment and shellfish in the inner and outer Daya Bay, Guangdong - Xiaodong Yu; Lianpeng Sun; Xinzhe Zhu; Guojian Bian; Wen Zhou; Qian Cao; Man Hong (Frontiers in Marine Science, 2022)
We investigated the distribution, sources, and ecological risks of heavy metals (As, Hg, Zn, Cd, Pb, Cu, and Cr) in seawater, sediments, and shellfish in the inner and outer waters of Daya Bay. 42 seawater quality survey sites, 21 sediment survey sites and 21 biological survey sites were set up in the study area. Our results showed that Daya Bay’s seawater is both clean and has a high Cu exceedance factor. The sediment heavy metal potential ecological hazard indices are all less than 40, which indicates a minimal degree of risk. E RI in the bay (mean value of E RI is 25.43) and that outside the bay (mean value of 23.56) is lower than 150, so the potential impact on the ecosystem is relatively low. In the Bay, Hg and Zn are primarily from fossil fuel and coal combustion, which enter the ocean via dry and wet deposition or surface runoff. Outside the Bay, Cr, Cu, Zn and Pb are derived the combustion waste gases of ships that enter the ocean via atmospheric deposition. Concerningly, arsenic and lead level in shellfish organisms appear to be above the standard values.However, because THQ and TTHQ are less than 1, there is no potential risk to human health. The weekly assessed intakes (EWIs) of Hg, AS, Pb, and Cd in shellfish inside and outside Daya Bay were 0.093 (0.058 outside the Bay), 0.594 (0.534), 1.115 (1.489), and 0.201 (0.190), respectively, all of these values were lower than the provisional PTWI for humans established by WHO. This indicates that the probability of carcinogenic risk to the population from heavy metals in shellfish are all below unacceptable levels.

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Ozone catalytic oxidation of low-concentration formaldehyde over ternary Mn-Ce-Ni oxide catalysts modified with FeOx - Run Yu Liu; Minh Man Trinh; Hsin Tzu Chuang; Moo Been Chang (Environmental Science and Pollution Research, 2022)

Silencing Asian Seabass gab3 Inhibits Nervous Necrosis Virus Replication - Zituo Yang; Yepin Yu; Le Wang; Sek-Man Wong; Gen Hua Yue (Marine Biotechnology, 2022)

Combined Effects of Warming and Imidacloprid on Survival, Reproduction and Population Growth of Brachionus calyciflorus (Rotifera) - Ya Wen; Man-Man Cao; Zhi-Yu Huang; Yi-Long Xi (Bulletin of Environmental Contamination and Toxicology, 2022)

Recent advances in biotechnological production of polyunsaturated fatty acids by Yarrowia lipolytica - Yu-Lei Jia; Ling-Ru Wang; Zi-Xu Zhang; Yang Gu; Xiao-Man Sun (Critical Reviews in Food Science and Nutrition, 2022)

Influence of exogenous selenomethionine and selenocystine on uptake and accumulation of Se in winter wheat (Triticum aestivum L. cv. Xinong 979) - Ruifang Liu; Luhua Zhao; Jiao Li; Chuangye Zhang; Lihui Lyu; Yu Bon Man; Fuyong Wu (Environmental Science and Pollution Research, 2022)

Long-term straw return increases biological nitrogen fixation by increasing soil organic carbon and decreasing available nitrogen in rice–rape rotation - Huishan Fan; Shengqiang Jia; Man Yu; Xijing Chen; Alin Shen; Yao Su (Plant and Soil, 2022)

Effects of cervicothoracic postures on the stiffness of trapezius muscles - Hongying Liang; Suiqing Yu; Man Hao; Weixin Deng; Ming Lin; Zheng Zhang; Chunlong Liu (Medical & Biological Engineering & Computing, 2022)

The Super-large Ensemble Experiments of CAS FGOALS-g3 - Pengfei Lin; Bowen Zhao; Jilin Wei; Hailong Liu; Wenxia Zhang; Xiaolong Chen; Jie Jiang; Mengrong Ding; Wenmin Man; Jinrong Jiang; Xu Zhang; Yuewen Ding; et al. (Advances in Atmospheric Sciences, 2022)
A super-large ensemble simulation dataset with 110 members has been produced by the fully coupled model FGOALS-g3 developed by researchers at the Institute of Atmospheric Physics, Chinese Academy of Sciences. This is the first dataset of large ensemble simulations with a climate system model developed by a Chinese modeling center. The simulation has the largest realizations up to now worldwide in terms of single-model initial-condition large ensembles. Each member includes a historical experiment (1850–2014) and an experiment (2015–99) under the very high greenhouse gas emissions Shared Socioeconomic Pathway scenario (SSP5-8.5). The dataset includes monthly and daily temperature, precipitation, and other variables, requiring storage of 275 TB. Additionally, the surface air temperature (SAT) and land precipitation simulated by the FGOALS-g3 super-large ensemble have been validated and projected. The ensemble can capture the response of SAT and land precipitation to external forcings well, and the internal variabilities can be quantified. The availability of more than 100 realizations will help researchers to study rare events and improve the understanding of the impact of internal variability on forced climate changes.

Feeding behavior, microcystin accumulation, biochemical response, and ultramicrostructure changes in edible freshwater bivalve Corbicula fluminea exposed to Microcystis aeruginosa - Jingxiao Zhang; Miao Yu; Yunni Gao; Man Zhang; Jing Dong; Mei Li; Xuejun Li (Environmental Science and Pollution Research, 2022)

Exploring the R-ISS stage-specific regular networks in the progression of multiple myeloma at single-cell resolution - Ling Zhong; Xiao Yang; Yu Zhou; Jialing Xiao; Huan Li; Jiang Tao; Qian Xi; Chen Chu; Chenglong Li; Xi Yang; Chen Yang; Yi Zhang; et al. (Science China Life Sciences, 2022)

Use of an Effective Variance Chemical Mass Balance Model for Source Apportionment of Metal Elements in a Polluted River - Pei-Yuan Hsieh; Chi-Chang Ho; Gen-Shuh Wang; Yuan-Cheng Hsu; Di-Wen Wang; Yu-Man Shang; Chang-Fu Wu (Environmental Processes, 2022)

Dyadobacter diqingensis sp. nov., isolated from Baima snow mountain of Diqing Tibetan Autonomous Prefecture in Yunnan province, south-west China - Lei Ran; Man Peng; Wei-Qun Wang; Yu-Zhou Feng; Juan Wang; Yu Wang; Cui-Ying Li; Xin-Xing Liu; Wei-Xun Chunyu; Shu-Kun Tang (Archives of Microbiology, 2022)

Alleviating the Influence of Circadian Rhythms and Drug Properties to the Release of Paliperidone Gel Matrix Tablets with Compression Coating Technology and Microenvironment Shaping - Zherui Zhang; Shumin Chen; Man Wen; Haibing He; Yu Zhang; Tian Yin; Jingxin Gou; Xing Tang (AAPS PharmSciTech, 2022)

Association of caffeine and caffeine metabolites with obesity among children and adolescents: National Health and Nutrition Examination Survey (NHANES) 2009–2014 - Linling Yu; Hong Mei; Da Shi; Xing Wang; Man Cheng; Lieyang Fan; Yang Xiao; Ruyi Liang; Bin Wang; Meng Yang; Weihong Chen (Environmental Science and Pollution Research, 2022)

OsAPL controls the nutrient transport systems in the leaf of rice (Oryza sativa L.) - Zhen Yan; Man-Yu Yang; Biligen-Gaowa Zhao; Guo Li; Qing Chao; Feng Tian; Ge Gao; Bai-Chen Wang (Planta, 2022)

Statistical optimization of phytol and polyunsaturated fatty acid production in the Antarctic microalga Micractinium variabile KSF0031 - Eun Jae Kim; Hyunsik Chae; Man Hyung Koo; Jihyeon Yu; Hyunjoong Kim; Sung Mi Cho; Kwang Won Hong; Joo Young Lee; Ui Joung Youn; Sanghee Kim; Han-Gu Choi; Se Jong Han (Algae, 2022)
Polar microorganisms produce physiologically active substances to adapt to harsh environments, and these substances can be used as biomedical compounds. The green microalga Micractinium variabile KSF0031, which was isolated from Antarctica, produced phytol, a natural antimicrobial agent. Furthermore, several polyunsaturated fatty acids (PUFAs), including omega-3, exhibit antioxidant properties. Here statistical methods (Plackett-Burman design and Box- Behnken design) were used to optimize the culture medium of KSF0031 to improve biomass production, and K2HPO4, MgSO4·7H2O, and ammonium ferric citrate green (AFCg) were selected as significant components of the culture medium. Changes in the concentration of K2HPO4 and MgSO4·7H2O as positive factors and AFCg as a negative factor affected cell growth to a remarkable degree. The biomass production in a 100 L culture using the optimized medium for 24 d at 18°C was improved by 37.5% compared to that obtained using the original BG-11 medium. The quantities of PUFAs and phytol obtained were 13 mg g-1 dry cell weight (DCW) and 10.98 mg g-1 DCW, which represent improved yields of 11.70% and 48.78%, respectively. The results of this study could contribute to an improved production of phytol and fatty acids from Antarctic microalgae in the biomedical industry.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Identification and Phylogenetic Analysis of Chitin Synthase Genes from the Deep-Sea Polychaete Branchipolynoe onnuriensis Genome - Hyeongwoo Choi; Sang Lyeol Kim; Man-Ki Jeong; Ok Hwan Yu; Seongil Eyun (Journal of Marine Science and Engineering, 2022)
Chitin, one of the most abundant biopolymers in nature, is a crucial material that provides sufficient rigidity to the exoskeleton. In addition, chitin is a valuable substance in both the medical and industrial fields. The synthesis of chitin is catalyzed by chitin synthase (CHS) enzymes. Although the chitin synthesis pathway is highly conserved from fungi to invertebrates, CHSs have mostly only been investigated in insects and crustaceans. Especially, little is known about annelids from hydrothermal vents. To understand chitin synthesis from the evolutionary view in a deep-sea environment, we first generated the whole-genome sequencing of the parasitic polychaete Branchipolynoe onnuriensis. We identified seven putative CHS genes (BonCHS1-BonCHS7) by domain searches and phylogenetic analyses. This study showed that most crustaceans have only a single copy or two gene copies, whereas at least two independent gene duplication events occur in B. onnuriensis. This is the first study of CHS obtained from a parasitic species inhabiting a hydrothermal vent and will provide insight into various organisms’ adaptation to the deep-sea hosts.

Effects of Chemotherapy on Neuroinflammation, Neuronal Damage, Neurogenesis, and Behavioral Performance in Bone Marrow Transplantation Recipient Mice - Zhong-Yuan Yu; Man-Yu Xu; Zhi-Hao Liu; Gui-Hua Zeng; Huan Fan; Cheng-Rong Tan; Yun-Feng Tu; Xian-Le Bu; Yan-Jiang Wang (Neurotoxicity Research, 2022)

Parkin Inhibits Static Mechanical Pain by Suppressing Membrane Trafficking of Mechano-transducing Ion Channel TACAN - Yi Lei; Man-Xiu Xie; Xian-Ying Cao; Xi Zhang; Yi-Bin Xiao; Xiao-Yu Tian; Yuan-Xin Zhu; Xiao-Long Zhang (Neuroscience Bulletin, 2022)

Spatially-explicit quantitative relationship for a potential PES mechanism: Cascade hydropower development in Yarlung Zangbo River Basin, China - Xiao-kang Zhu; Bin Fu; Ramon Felipe Bicudo Da Silva; Ying-man Guo; Chan-yuan Qin; Ting Feng; Hai-bing Yu; Kuang Xiao (Journal of Mountain Science, 2022)

Bibliometric Review of Biodiversity Offsetting During 1992–2019 - Shuling Yu; Baoshan Cui; Chengjie Xie; Ying Man; Jing Fu (Chinese Geographical Science, 2022)

The significance of riparian communities in the energy flow of subtropical stream ecosystems - Yi-Chang Liao; An-Cheng Lin; Han-Ni Tsai; Yu-Ting Yen; Chyng-Shyan Tzeng; Man-Miao Yang; Hsing-Juh Lin (Aquatic Sciences, 2022)

White Matter “Matters” in Alzheimer’s Disease - Man-Yu Xu; Zhi-Qiang Xu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

3D Seismic Stability Analysis of Bench Slope with Pile Reinforcement - Sheng-yu Yang; Zhen Wang; Jia-man Wang; Ming-wei Gong; Jian-fei Li; Zhi-bin Sun (Geotechnical and Geological Engineering, 2022)

Shape stable poly(vinyl alcohol) hydrogels with immobilized metal hexacyanoferrates for cesium removal from waters - Po-Hsun Wang; Yin-Ru Chang; Man-Li Chen; Yu-Kuo Lo; Duu-Jong Lee (Environmental Science and Pollution Research, 2022)

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

Propioniciclava soli sp. nov., isolated from forest soil, Yunnan, China, and reclassification of the genus Brevilactibacter into the genus Propioniciclava, and Brevilactibacter sinopodophylli, Brevilactibacter flavus, and Brevilactibacter coleopterorum as Propioniciclava sinopodophylli comb. nov., Propioniciclava flava comb. nov., and Propioniciclava coleopterorum comb. nov., respectively - Le-Le Li; Jiang-Yuan Zhao; Yu Geng; Yu-Guang Zhou; Hui-Ren Yuan; Man Cai; Meng-Liang Wen; Ming-Gang Li; Shu-Kun Tang (Archives of Microbiology, 2022)

Laser ablation inductively coupled plasma mass spectrometry analysis of Chinese lead-barium glass: combining multivariate kernel density estimation and maximum mean discrepancy to reinterpret the raw glass used for producing lead-barium glass - Qian Ma; Rui Wen; Yifan Yu; Long Wang; Man Li; Luwu Cai; Li Ping; Zhiqiang Zhao; Dong Wang; Xiang Wang; Ruoyu Shi; A. Mark Pollard (Archaeological and Anthropological Sciences, 2022)

Neonatal Anesthesia by Ketamine in Neonatal Rats Inhibits the Proliferation and Differentiation of Hippocampal Neural Stem Cells and Decreases Neurocognitive Function in Adulthood via Inhibition of the Notch1 Signaling Pathway - He Huang; Chao Zhao; Qian Hu; Qiang Liu; Yi-Man Sun; Chen Chen; Hui Huang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2021)

Numerical investigation on the fatigue failure characteristics of water-bearing sandstone under cyclic loading - Chun Zhu; Man-chao He; Bei Jiang; Xin-zhan Qin; Qian Yin; Yu Zhou (Journal of Mountain Science, 2021)

Simultaneous adoption of diversification and agricultural credit to manage catastrophic risk for maize production in Bangladesh - K M Mehedi Adnan; Liu Ying; Swati Anindita Sarker; Man Yu; Riffat Ara Zannat Tama (Environmental Science and Pollution Research, 2021)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Special issue on contamination, remediation and health for pollutants in natural aquatic, soil, sediments and atmospheric environments - Kitae Baek; Daniel S. Alessi; Yu Bon Man; Eilhann E. Kwon (Environmental Geochemistry and Health, 2021)

Evaluation of soil microbial communities and enzyme activities in cucumber continuous cropping soil treated with spent mushroom (Flammulina velutipes) substrate - Hong-Wei Wang; Man Xu; Xiao-Yu Cai; Feng Tian (Journal of Soils and Sediments, 2021)

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Selection of reliable reference genes for analysis of gene expression in the rat placenta - Caiyun Ge; Pengxia Yu; Man Fang; Hui Wang; Yuanzhen Zhang (Molecular and Cellular Biochemistry, 2021)

Overexpression of T-type calcium channel Cav3.1 in oral squamous cell carcinoma: association with proliferation and anti-apoptotic activity - Rui-Fang Li; Qi-Wen Man; Jin-Yuan Liu; Yue-Yu Zheng; Xin Gao; Hai-Ming Liu (Journal of Molecular Histology, 2021)

Inhibition of the p38 MAPK pathway attenuates renal injury in pregnant rats with acute necrotizing pancreatitis - Jiacheng Zhang; Fangchao Mei; Liang Zhao; Teng Zuo; Yupu Hong; Man Li; Jia Yu; Weixing Wang (Immunologic Research, 2021)

Efficiency comparison of B6(Cg)-Tyrc−2j /J and C57BL/6NTac embryos as hosts for the generation of knockout mice - Yu’e Ma; Lei He; Lijie Xiang; Jie Zhang; Jing Wang; Wenjing Zhu; Wenni Cao; Yichen Zhu; Man Gao; Fei Zhou; Zhiwei Liu (Transgenic Research, 2021)
Careful selection of the host embryo is critical to the efficient production of knockout (KO) mice when injecting mouse embryonic stem (mES) cells into blastocysts. B6(Cg)-Tyr c−2j /J (B6 albino) and C57BL/6NTac (B6NTac) strains of mice are widely used to produce host blastocysts for such procedures. Here, we tested these two strains to identify an appropriate match for modified agouti C57BL/6N (JM8A3.N1) mES cells. When comparing blastocyst yield, super-ovulated B6NTac mice produced more injectable blastocysts per female than B6 albino mice (8.2 vs. 5.4). There was no significant difference in birth rate when injected embryos were transferred to the same pseudopregnant recipient strain. However, the live birth rate was significantly higher for B6NTac blastocysts than B6 albino blastocysts (62.7% vs. 50.2%). In addition, the proportion of pups exhibiting high-level and complete chimerism, as identified by coat color, was also significantly higher in the B6NTac strain. There was no obvious difference in the efficiency of germline transmission (GLT) when compared between B6NTac and B6 albino host embryos (61.5% vs. 63.3% for mES clones; 64.5% vs. 67.9% for genes, respectively), thus suggesting that an equivalent GLT rate could be obtained with only a few blastocyst injections for B6NTac embryos. In conclusion, our data indicate that B6NTac blastocysts are a better choice for the microinjection of JM8A3.N1 mES cells than B6 albino blastocysts.

Associations between SNP83 of phosphodiesterase 4D gene and carotid atherosclerosis in a southern Chinese Han population: a case–control study - Liu-yu Liu; Dong-can Mo; Jian-li Li; Yi-ying Jiang; Guo-qiu Zhou; Dong-dong Jiang; Li-jie Chen; Xiao-ju Wu; Jiao-xing Li; Man Luo (Mammalian Genome, 2021)

Global patterns in leaf stoichiometry across coastal wetlands - Yu‐Kun Hu; Xu‐Yan Liu; Nian‐Peng He; Xu Pan; Song‐Yuan Long; Wei Li; Man‐Yin Zhang; Li‐Juan Cui (Global Ecology and Biogeography, 2021)
Aim Coastal wetlands provide crucial ecosystem functions and services, such as coastal protection, nutrient retention and C sequestration. Despite the important roles in global C, N and P cycling, the global variation in leaf stoichiometry across coastal wetlands remains unclear. Location Global. Time period 1980–2018. Major taxa studied Vascular plants. Methods By compiling a global dataset of 698 data records in 205 sites, we carried out systematic analyses of the world‐wide trends and their determinants of leaf element contents and ratios of plants across coastal wetlands. Results Leaf N and P contents increased significantly, but C:N, C:P and N:P ratios decreased with increasing latitude in coastal wetlands. The mean annual temperature was the predominant driver of leaf N, P and C:N, whereas soil N:P was a good predictor of leaf C:P and N:P ratios. Furthermore, N increased faster with P in plant leaves of coastal wetlands compared with terrestrial ecosystems. Within coastal wetlands, herb‐dominated salt marshes had a significantly higher leaf P content, lower leaf N:P ratio and lower scaling exponent of leaf N to P than tree‐dominated mangroves. Main conclusions The similar latitudinal patterns of leaf stoichiometry in coastal wetlands compared with terrestrial ecosystems reflected the similar influences of temperature. However, different slopes of leaf P and N:P ratios and N and P scaling relationships between these two ecosystems suggested that different salinity and tidal inundation levels result in different strategies of N and P use in coastal wetland plants. These differences in leaf stoichiometry between ecosystems and between different types of coastal wetlands might need to be emphasized in future biogeochemical modelling owing to their different roles in global nutrient and carbon cycling.

Hormesis of low-dose inhibition of pAkt1 (Ser473) followed by a great increase of proline-rich inositol polyphosphate 5-phosphatase (PIPP) level in oocytes - Hang Yu; Wei Yong; Teng Gao; Man Na; Ye Zhang; Isaac Harlison Kuguminkiriza; Anyanyo Alexander Kenechukwu; Qingguo Guo; Guoli Zhang; Xin Deng (In Vitro Cellular & Developmental Biology - Animal, 2021)

Use of biochar as feed supplements for animal farming - Ka Yan Man; Ka Lai Chow; Yu Bon Man; Wing Yin Mo; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2021)

Effectiveness of Adding Antiplatelets to Oral Anticoagulants in Patients with Acute Ischemic Stroke with Atrial Fibrillation and Concomitant Large Artery Steno-Occlusion - Joon-Tae Kim; Ji Sung Lee; Beom Joon Kim; Jong-Moo Park; Kyusik Kang; Soo Joo Lee; Jae Guk Kim; Jae-Kwan Cha; Dae-Hyun Kim; Tai Hwan Park; Sang-Soon Park; Kyung Bok Lee; et al. (Translational Stroke Research, 2020)

Fetal growth, fetal development, and placental features in women with polycystic ovary syndrome: analysis based on fetal and placental magnetic resonance imaging - Qing Zhang; Zhong-kun Bao; Mei-xiang Deng; Qiong Xu; Dan-dan Ding; Man-man Pan; Xi Xi; Fang-fang Wang; Yu Zou; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2020)

TIAM1 Upregulation Confers NVP-BEZ235 Resistance to Breast Cancer Cells Through FGFR/STAT3 Pathway - Jingjing Qiao; Man Li; Na Li; Lingzhi Xu; Gena Huang; Jing Yu (Biochemical Genetics, 2020)

Chemical constituents from common vetch ( Vicia sativa L.) and their antioxidant and cytotoxic activities - Li-Fang Liu; Wen-Hai Li; Man-Yu Li; Xiao-Zhen Wu; Fan Yang; Jia-Nan Xu; Cheng-Shan Yuan (Natural Product Research, 2020)

Isopimarane-type diterpenoids from Croton laevigatus - Man-Yu Li; Zheng-Zhi Han; Li-Fang Liu; Xiao-Zhen Wu; Wen-Jun Huang; Kai Wang; Fan Yang; Cheng-Shan Yuan (Natural Product Research, 2020)

Direct and indirect effects of microplastics on bivalves, with a focus on edible species: A mini-review - Feng Zhang; Yu Bon Man; Wing Yin Mo; Ka Yan Man; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2020)

Aging exacerbates impairments of cerebral blood flow autoregulation and cognition in diabetic rats - Shaoxun Wang; Wenshan Lv; Huawei Zhang; Yedan Liu; Longyang Li; Joshua R. Jefferson; Ya Guo; Man Li; Wenjun Gao; Xing Fang; Ian A. Paul; Grazyna Rajkowska; et al. (GeroScience, 2020)

Overexpression of a Malus xiaojinensis WRKY transcription factor gene (MxWRKY55) increased iron and high salinity stress tolerance in Arabidopsis thaliana - Deguo Han; Zhengyi Zhou; Man Du; Tiemei Li; Xuemei Wu; Jing Yu; Peng Zhang; Guohui Yang (In Vitro Cellular & Developmental Biology - Plant, 2020)

Metabolomics Study of Flavonoids and Anthocyanin-Related Gene Analysis in Kiwifruit (Actinidia chinensis) and Kiwiberry (Actinidia arguta) - Min Yu; Yuping Man; Rui Lei; Xuemei Lu; Yanchang Wang (Plant Molecular Biology Reporter, 2020)
This study investigated the flavonoid compounds in Actinidia chinensis and Actinidia arguta fruits. A total of 125 flavonoids, including 9 anthocyanins, 12 catechins, 17 flavanones, 48 flavones (including 14 flavone C-glycosides), 29 flavonols, 6 isoflavones, and 4 proanthocyanidins, were identified in “Hongyang” kiwifruit (red flesh), “Jintao” kiwifruit, “Mini Amethyst” kiwiberry (purple flesh), and “Kuilv” kiwiberry. Thirty-nine metabolites showed significantly different contents between “Hongyang” and “Jintao,” and 38 of them showed higher content in “Hongyang,” whereas 39 metabolites showed significantly different contents between “Mini Amethyst” and “Kuilv,” and 31 of them showed higher content in “Mini Amethyst.” This result indicates the superior nutritional value of the pigmented kiwi cultivars in terms of flavonoids. Multivariate statistical analysis indicates that the variation in flavonoid profiles contributes to the pigmentation phenotypes of “Hongyang” and “Mini Amethyst.” Further comparative transcriptomic analysis revealed that structural genes in the anthocyanin synthesis pathway ( AcF3H , AcF3′H , AcDFR , AcUFGT ) and transcription factors ( AcMYB10 , AcbHLH5 ) may be involved in the pigmentation of the red-fleshed A. chinensis , whereas AaF3H , AaF3GT , and AaMYB110 may play important roles in the pigmentation of the purple-fleshed A. arguta . This study provides broader insight into the variation in flavonoid profiles among kiwifruit/berry, evaluates the flavonoid nutrition of the four cultivars, and provides additional evidence for the correlation between the genes and metabolites involved in flavonoid synthesis.

Heroin Abuse and/or HIV Infection Dysregulate Plasma Exosomal miRNAs - Xu Wang; Li Sun; Yu Zhou; Qi-Jian Su; Jie-Liang Li; Li Ye; Man-Qing Liu; Wang Zhou; Wen-Zhe Ho (Journal of Neuroimmune Pharmacology, 2020)

The comparison of transcriptomic response of green microalga Chlorella sorokiniana exposure to environmentally relevant concentration of cadmium(II) and 4-n-nonylphenol - Na Ding; Lu Wang; Yuan Kang; Kesong Luo; Diya Zeng; Yu Bon Man; Qiuyun Zhang; Lixuan Zeng; Jiwen Luo; Feng Jiang (Environmental Geochemistry and Health, 2020)

Discrimination of mine water-inflow sources based on the multivariate mixed model and fuzzy comprehensive evaluation - Jiuchuan Wei; Guanghui Li; Daolei Xie; Gongyishan Yu; Xiaoquan Man; Jie Wang (Arabian Journal of Geosciences, 2020)

Pseudomonas Saliphila sp. nov., a Bacterium Isolated from Oil-Well Production Water in Qinghai Oilfield of China - Xiao-Juan Zhang; Hong-Can Liu; Yu-Guang Zhou; Xiao-Lei Wu; Yong Nie; Qi-Rui Li; Mei-Zhu Wang; Liang Zhao; Man Cai; Ying-Qian Kang (Current Microbiology, 2020)

Genomic characterization of closely related species in the Rumoiensis clade infers ecogenomic signatures to non‐marine environments - Mami Tanaka; Daiki Kumakura; Sayaka Mino; Hidetaka Doi; Yoshitoshi Ogura; Tetsuya Hayashi; Isao Yumoto; Man Cai; Yu‐Guang Zhou; Bruno Gomez‐Gil; Toshiyoshi Araki; Tomoo Sawabe (Environmental Microbiology, 2020)
Summary Members of the family Vibrionaceae are generally found in marine and brackish environments, playing important roles in nutrient cycling. The Rumoiensis clade is an unconventional group in the genus Vibrio , currently comprising six species from different origins including two species isolated from non‐marine environments. In this study, we performed comparative genome analysis of all six species in the clade using their complete genome sequences. We found that two non‐marine species, Vibrio casei and Vibrio gangliei , lacked the genes responsible for algal polysaccharide degradation, while a number of glycoside hydrolase genes were enriched in these two species. Expansion of insertion sequences was observed in V . casei and Vibrio rumoiensis , which suggests ongoing genomic changes associated with niche adaptations. The genes responsible for the metabolism of glucosylglycerate, a compound known to play a role as compatible solutes under nitrogen limitation, were conserved across the clade. These characteristics, along with genes encoding species‐specific functions, may reflect the habit expansion which has led to the current distribution of Rumoiensis clade species. Genome analysis of all species in a single clade give us valuable insights into the genomic background of the Rumoiensis clade species and emphasize the genomic diversity and versatility of Vibrionaceae .

Ecological risks of heavy metals/metalloid discharged from two sewage treatment works to Mai Po Ramsar site, South China - Yu Bon Man; Kim Man Lei; Ka Lai Chow; Anna Oi Wah Leung; Wing Yin Mo; Ming Hung Wong (Environmental Monitoring and Assessment, 2020)

Preface - Yu Bon Man; Yuanyuan Tang; Ka Lai Chow; Tsz Fung Wong (Environmental Geochemistry and Health, 2020)

Numerical Investigation of NOx Emission Reduction in Non-Premixed Lean Reverse-Flow Combustor in a Micro Gas Turbine Engine - Jesline Joy; Peng Cheng Wang; Jeggathishwaran Panisilvam; Simon Ching Man Yu (Emission Control Science and Technology, 2020)

Screening for antagonistic bacteria against Fusarium oxysporum and their influence on the consecutive monoculture problem of Rehmannia glutinosa - Jia-fang Du; Xuan-zhen Li; Man-yu Liu; Zhong-yi Zhang; Mo Wang (Journal of Plant Pathology, 2020)

Circulating Selenium and Cardiovascular or All-Cause Mortality in the General Population: a Meta-Analysis - Shouyan Xiang; Zhe Dai; Changfeng Man; Yu Fan (Biological Trace Element Research, 2020)

Application of Spirulina in aquaculture: a review on wastewater treatment and fish growth - Feng Zhang; Yu Bon Man; Wing Yin Mo; Ming Hung Wong (Reviews in Aquaculture, 2020)
There is an urgent need to find alternatives to fish meal and fish oil in compound feeds due to their rapidly rising prices and the demand for sustainable fisheries. Spirulina, a filamentous blue‐green microalga, is an excellent source of plant protein and could replace expensive animal‐derived proteins in fish feed. Studies have evaluated the use of spirulina as a fish meal for different fish species. This paper reviews research on the effects of spirulina on the growth performance of various fish species. It is apparent that spirulina can be a highly important component of the diet of fish; it has a number of benefits, such as promoting the growth of tilapia ( Oreochromis niloticus ) and carp ( Labeo rohita ), improving the reproductive performance of yellow tail cichlid ( Pseudotropheus acei ) and enhancing the immune response of rainbow trout ( Oncorhynchus mykiss ). Recent studies have shown that spirulina can be used for treating wastewater, including effluent from fish culture activities, as it can efficiently metabolize the nutrients and remove the heavy metals contained in aquaculture effluent. Fish aquaculture could apply an integrated strategy of simultaneously treating aquaculture effluent while producing spirulina biomass to supplement fish diets.

Diversity Distributions and the Anthocyanin Associations of Fungal Endophytes in Different Colored Grapevine Leaves - Jing-Chao Chen; Man Yu; Fang Liu; Jin-Zhuo Qu; Xiao-Xia Pan; Han-Bo Zhang; Ming-Zhi Yang (Journal of Plant Biology, 2020)

Novel dammarane-type saponins from Gynostemma pentaphyllum and their neuroprotective effect - Shao-Fang Xing; Man Lin; Yu-Rong Wang; Tuo Chang; Wei-Ye Cui; Xiang-Lan Piao (Natural Product Research, 2020)

Optimizing the frequency ratio method for landslide susceptibility assessment: A case study of the Caiyuan Basin in the southeast mountainous area of China - Yi-xing Zhang; Heng-xing Lan; Lang-ping Li; Yu-ming Wu; Jun-hui Chen; Nai-man Tian (Journal of Mountain Science, 2020)

Impacts of the influx of e-waste into Hong Kong after China has tightened up entry regulations - Siyi Lin; Yu Bon Man; Ka Lai Chow; Chunmiao Zheng; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2020)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

Dietary exposure to chlorpyrifos inhibits the polarization of regulatory T cells in C57BL/6 mice with dextran sulfate sodium-induced colitis - Hsiao-Mei Huang; Man-Hui Pai; Sung-Ling Yeh; Yu-Chen Hou (Archives of Toxicology, 2020)

Analysis of the MIR160 gene family and the role of MIR160a_A05 in regulating fiber length in cotton - Guoyuan Liu; Ji Liu; Wenfeng Pei; Xihua Li; Nuohan Wang; Jianjiang Ma; Xinshan Zang; Jinfa Zhang; Shuxun Yu; Man Wu; Jiwen Yu (Planta, 2019)
Main conclusion The MIR160 family in Gossypium hirsutum and G. barbadense was characterized, and miR160a_A05 was found to increase cotton-fiber length by downregulating its target gene ( ARF17 ) and several GH3 genes. Abstract Cotton fiber is the most important raw material for the textile industry. MicroRNAs are involved in regulating cotton-fiber development, but a role in fiber elongation has not been demonstrated. In this study, miR160a was found to be differentially expressed in elongating fibers between two interspecific (between Gossypium hirsutum and G. barbadense ) backcross inbred lines (BILs) with different fiber lengths. The gene MIR160 colocalized with a previously mapped fiber-length quantitative trait locus. Its target gene ARF17 was differentially expressed between the two BILs during fiber elongation, but in the inverse fashion. Bioinformatics was used to analyze the MIR160 family in both G. hirsutum and G. barbadense . Moreover, qRT–PCR analysis identified MIR160a as the functional MIR160 gene encoding the miR160a precursor during fiber elongation. Using virus-induced gene silencing and overexpression, overexpressed MIR160a_A05 resulted in significantly longer fibers compared with wild type, whereas suppression of miR160 resulted in significantly shorter fibers. Expression levels of the target gene auxin-response factor 17 ( ARF17 ) and related genes GH3 in the two BILs and/or the virus-infected plants demonstrated similar changes in response to modulation of miR160a level. Finally, overexpression or suppression of miR160 increased or decreased, respectively, the cellular level of indole-3-acetic acid, which is involved in fiber elongation. These results describe a specific regulatory mechanism for fiber elongation in cotton that can be utilized for future crop improvement.

Vanadium compounds induced damage of human umbilical vein endothelial cells and the protective effect of berberine - Cong-Cong Hou; Hong-Yu Liang; Yi-Hui Pan; Man Wang; Li-Li Zhao; Yuan Bian; Duan-Yuan Cao; Ding Zhao (BioMetals, 2019)

QTL analysis and candidate gene identification for plant height in cotton based on an interspecific backcross inbred line population of Gossypium hirsutum × Gossypium barbadense - Jianjiang Ma; Wenfeng Pei; Qifeng Ma; Yanhui Geng; Guoyuan Liu; Ji Liu; Yupeng Cui; Xia Zhang; Man Wu; Xingli Li; Dan Li; XinShan Zang; et al. (Theoretical and Applied Genetics, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Antagonism of Ca2+-sensing receptors by NPS 2143 is transiently masked by p38 activation in mouse brain bEND.3 endothelial cells - Cing-Yu Chen; Mann-Jen Hour; Wen-Chuan Lin; Kar-Lok Wong; Lian-Ru Shiao; Ka-Shun Cheng; Paul Chan; Yuk-Man Leung (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Enhancement of Oral Bioavailability and Anti-hyperuricemic Activity of Isoliquiritigenin via Self-Microemulsifying Drug Delivery System - Kangyi Zhang; Qilong Wang; Qiuxuan Yang; Qiuyu Wei; Na Man; Michael Adu-Frimpong; Elmurat Toreniyazov; Hao Ji; Jiangnan Yu; Ximing Xu (AAPS PharmSciTech, 2019)

Electroacupuncture inhibits visceral pain via adenosine receptors in mice with inflammatory bowel disease - Tengfei Hou; Hongchun Xiang; Lingling Yu; Wen Su; Yang Shu; Hongping Li; He Zhu; Lixue Lin; Xuefei Hu; Shangdong Liang; Hong Zhang; Man Li (Purinergic Signalling, 2019)

Changes of non-protein thiols in root and organic acids in xylem sap involved in cadmium translocation of cadmium-safe rice line (Oryza Sative L.) - Qin Li; Jingyi Guo; Xizhou Zhang; Haiying Yu; Fu Huang; Lu Zhang; Man Zhang; Tingxuan Li (Plant and Soil, 2019)

Characterization of Cucurbita maxima Fruit Metabolomic Profiling and Transcriptome to Reveal Fruit Quality and Ripening Gene Expression Patterns - He-Xun Huang; Ting Yu; Jun-Xing Li; Shu-Ping Qu; Man-Man Wang; Ting-Quan Wu; Yu-Juan Zhong (Journal of Plant Biology, 2019)

Simulation study of the void space gas effect on slope instability triggered by an earthquake - Zhou Zhou; Xiao-qun Wang; Yu-feng Wei; Jun-hui Shen; Man Shen (Journal of Mountain Science, 2019)

Effect of tobacco stem-derived biochar on soil metal immobilization and the cultivation of tobacco plant - Jin Zhang; Jianyun Zhang; Minyan Wang; Shengchun Wu; Hailong Wang; Nabeel Khan Niazi; Yu Bon Man; Peter Christie; Shengdao Shan; Ming Hung Wong (Journal of Soils and Sediments, 2019)

Developing an electric vehicle urban driving cycle to study differences in energy consumption - Xuan Zhao; Jian Ma; Shu Wang; Yiming Ye; Yan Wu; Man Yu (Environmental Science and Pollution Research, 2019)

Ecological Offsetting in China’s Coastal Wetlands: Existing Challenges and Strategies for Future Improvement - Shuling Yu; Baoshan Cui; Chengjie Xie; Xu Ma; Ying Man; Zhonghua Ning (Chinese Geographical Science, 2019)

Microclimate regulation efficiency of the rural homegarden agroforestry system in the Western Sichuan Plain, China - Qin Liu; Pei-hao Peng; Yu-kuan Wang; Pei Xu; Ying-man Guo (Journal of Mountain Science, 2019)

Differentially expressed genes between two groups of backcross inbred lines differing in fiber length developed from Upland × Pima cotton - Man Wu; Longyun Li; Guoyuan Liu; Xihua Li; Wenfeng Pei; Xingli Li; Jinfa Zhang; Shuxun Yu; Jiwen Yu (Molecular Biology Reports, 2019)

SB203580 attenuates acute lung injury and inflammation in rats with acute pancreatitis in pregnancy - Yu Zhou; Hongmiao Xia; Liang Zhao; Fangchao Mei; Man Li; Yundong You; Kailiang Zhao; Weixing Wang (Inflammopharmacology, 2019)

Herpes zoster and the risks of osteoporosis and fracture: a nationwide cohort study - Shu-Man Lin; Chih-Yung Wang; Ying-Yu Chen; Jen-Hung Wang; Chung-Chao Liang; Huei-Kai Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2019)

Biowaste for environmental remediation and sustainable waste management - Yiu Fai Tsang; Eilhann E. Kwon; Hocheol Song; Jechan Lee; Yu Bon Man (Clean Technologies and Environmental Policy, 2018)

Immunization with Chlamydia psittaci plasmid-encoded protein CPSIT_p7 induces partial protective immunity against chlamydia lung infection in mice - Yuan Tan; Yumeng Li; Yang Zhang; Jian Yu; Yating Wen; Chuan Wang; Man Xu; Qian Chen; Chunxue Lu; Yimou Wu (Immunologic Research, 2018)

Molecular cloning of adipose triglyceride lipase (ATGL) gene from blunt snout bream and its expression after LPS-induced TNF-α factor - Yong-Jun Dai; Wen-Bin Liu; Xiang-Fei Li; Man Zhou; Chao Xu; Yu Qian; Guang-Zhen Jiang (Fish Physiology and Biochemistry, 2018)

Mechanical and Clinical Evaluation of a Shape Memory Alloy and Conventional Struts in a Flexible Scoliotic Brace - Wing-Yu Chan; Joanne Yip; Kit-Lun Yick; Sun-Pui Ng; Lu Lu; Kenneth Man-Chee Cheung; Kenny Yat-Hong Kwan; Jason Pui-Yin Cheung; Kelvin Wai-Kwok Yeung; Chi-Yung Tse (Annals of Biomedical Engineering, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Integrated analysis of mRNA-seq and miRNA-seq for host susceptibilities to influenza A (H7N9) infection in inbred mouse lines - Suying Bao; Lilong Jia; Xueya Zhou; Zhi-Gang Zhang; Hazel Wai Lan Wu; Zhe Yu; Gordon Ng; Yanhui Fan; Dana S. M. Wong; Shishu Huang; Kelvin Kai Wang To; Kwok-Yung Yuen; et al. (Functional & Integrative Genomics, 2018)

Integrated analysis of transcriptomic and metabolomic data reveals critical metabolic pathways involved in rotenoid biosynthesis in the medicinal plant Mirabilis himalaica - Li Gu; Zhong-yi Zhang; Hong Quan; Ming-jie Li; Fang-yu Zhao; Yuan-jiang Xu; Jiang Liu; Man Sai; Wei-lie Zheng; Xiao-zhong Lan (Molecular Genetics and Genomics, 2018)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Functional analysis of a regulator of G-protein signaling CgRGS1 in the rubber tree anthracnose fungus Colletotrichum gloeosporioides - Zhi-Qiang Liu; Man-Li Wu; Zhi-Jian Ke; Wen-Bo Liu; Xiao-Yu Li (Archives of Microbiology, 2018)

Verrucosispora rhizosphaerae sp. nov., isolated from mangrove rhizosphere soil - Qing-yi Xie; Xiao-dong Bao; Qing-yu Ma; Fan-dong Kong; Man-li Zhou; Bing Yan; You-xing Zhao (Antonie van Leeuwenhoek, 2018)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

Salidroside improved cerebrovascular vasodilation in streptozotocin-induced diabetic rats through restoring the function of BKCa channel in smooth muscle cells - Yu-Guang Ma; Jun-Wei Wang; Yin-Bin Zhang; Bao-Feng Wang; Zhi-Jun Dai; Man-Jiang Xie; Hua-Feng Kang (Cell and Tissue Research, 2017)

Low Serum Levels of Brain-Derived Neurotrophic Factor Were Associated with Poor Short-Term Functional Outcome and Mortality in Acute Ischemic Stroke - Jing Wang; Li Gao; Yan-Long Yang; Yu-Qian Li; Tao Chang; Ming-Hao Man; Xing-Ye Zhang; Shao-Chun Guo; Li-Hong Li (Molecular Neurobiology, 2017)

Asymmetric reduction of ketopantolactone using a strictly (R)-stereoselective carbonyl reductase through efficient NADPH regeneration and the substrate constant-feeding strategy - Man Zhao; Liang Gao; Li Zhang; Yanbin Bai; Liang Chen; Meilan Yu; Feng Cheng; Jie Sun; Zhao Wang; Xiangxian Ying (Biotechnology Letters, 2017)

mPGES-1-derived prostaglandin E2 stimulates Stat3 to promote podocyte apoptosis - Jing Yu; Yimei Wu; Lu Wang; Wen Zhang; Man Xu; Jiayu Song; Yu Fu; Yiyun Cui; Wei Gong; Shuzhen Li; Weiwei Xia; Songming Huang; et al. (Apoptosis, 2017)

Synthesis and evaluation of novel urea and amide derivatives of 2-amino-4-phenylthiazole as potential antibacterial agents - Zhi-Hua Zhang; Yu Chen; Xin-Jia Yan; Yao Sun; Xiao-Man Yang; Xiao-Yu Cai; Song You (Medicinal Chemistry Research, 2017)

Microsatellite records for volume 9, issue 3 - Aiguo Yang; Biao Wu; Chao Shen; Guangming Zhang; Hanmiao Liu; Hongying Guo; Jiaman Li; Jinliang Liu; Liqing Zhou; Longbing Rao; Man Yang; Mengdi Li; et al. (Conservation Genetics Resources, 2017)

Overexpression of Arabidopsis ICR1 gene affects vegetative growth and anthesis - Da-Hui Li; Man-Li Li; Xiao-Bo Yu; Di Wu; Huan Xi; Yi Lin; Yong-Ping Cai (Biologia, 2017)

Occupational risk factors for nasopharyngeal carcinoma in Hong Kong Chinese: a case-referent study - Shao-Hua Xie; Ignatius Tak-sun Yu; Lap Ah Tse; Joseph Siu Kie Au; June Sze Man Lau (International Archives of Occupational and Environmental Health, 2017)

Serratia bozhouensis sp. nov., Isolated from Sewage Samples of a Dairy Farm - Fei Shang; Ting Xue; Man Wang; Xiaolin Chen; Li Yu; Ming Zhang (Current Microbiology, 2017)

Therapeutic Hypothermia Enhances Cold-Inducible RNA-Binding Protein Expression and Inhibits Mitochondrial Apoptosis in a Rat Model of Cardiac Arrest - Lin Wu; He-liang Sun; Yu Gao; Kang-li Hui; Miao-miao Xu; Hao Zhong; Man-lin Duan (Molecular Neurobiology, 2017)

Profiling of Selected Functional Metabolites in the Central Nervous System of Marine Medaka (Oryzias melastigma) for Environmental Neurotoxicological Assessments - Elva Ngai-Yu Lei; Man-Shan Yau; Chi-Chung Yeung; Margaret B. Murphy; Ka-Leung Wong; Michael Hon-Wah Lam (Archives of Environmental Contamination and Toxicology, 2017)

Numerical simulation on the effects of drug-eluting stents with different bending angles on hemodynamics and drug distribution - Yu Chen; Yan Xiong; Wentao Jiang; Man Sang Wong; Fei Yan; Qingyuan Wang; Yubo Fan (Medical & Biological Engineering & Computing, 2016)

Canopy structure and light interception partitioning among shoots estimated from virtual trees: comparison between apple cultivars grown on different interstocks on the Chinese Loess Plateau - Wei-Wei Yang; Xi-Long Chen; Marc Saudreau; Xiao-Yun Zhang; Man-Rang Zhang; Hang-Kong Liu; Evelyne Costes; Ming-Yu Han (Trees, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Urinary 6β-Hydroxycortisol/Cortisol Ratio Most Highly Correlates With Midazolam Clearance Under Hepatic CYP3A Inhibition and Induction in Females: A Pharmacometabolomics Approach - Kwang-Hee Shin; Li Young Ahn; Man Ho Choi; Ju-Yeon Moon; Jieon Lee; In-Jin Jang; Kyung-Sang Yu; Joo-Youn Cho (The AAPS Journal, 2016)

Trans-Cinnamaldehyde, An Essential Oil in Cinnamon Powder, Ameliorates Cerebral Ischemia-Induced Brain Injury via Inhibition of Neuroinflammation Through Attenuation of iNOS, COX-2 Expression and NFκ-B Signaling Pathway - Yuh-Fung Chen; Yu-Wen Wang; Wei-Shih Huang; Ming-Ming Lee; W. Gibson Wood; Yuk-Man Leung; Huei-Yann Tsai (NeuroMolecular Medicine, 2016)

Review on Saussurea laniceps, a potent medicinal plant known as “snow lotus”: botany, phytochemistry and bioactivities - Qi-Lei Chen; Xi-Yu Chen; Lin Zhu; Hu-Biao Chen; Hing-Man Ho; Wing-Ping Yeung; Zhong-Zhen Zhao; Tao Yi (Phytochemistry Reviews, 2016)

A comparative transcriptome analysis of two sets of backcross inbred lines differing in lint-yield derived from a Gossypium hirsutum × Gossypium barbadense population - Wu Man; Liyuan Zhang; Xihua Li; Xiaobing Xie; Wenfeng Pei; Jiwen Yu; Shuxun Yu; Jinfa Zhang (Molecular Genetics and Genomics, 2016)

Effects of 4-methylbenzylidene camphor (4-MBC) on neuronal and muscular development in zebrafish (Danio rerio) embryos - Vincent Wai Tsun Li; Mei Po Mirabelle Tsui; Xueping Chen; Michelle Nga Yu Hui; Ling Jin; Raymond H. W. Lam; Richard Man Kit Yu; Margaret B. Murphy; Jinping Cheng; Paul Kwan Sing Lam; Shuk Han Cheng (Environmental Science and Pollution Research, 2016)

Reproductive responses of male Brandt’s voles (Lasiopodomys brandtii) to 6-methoxybenzoxazolinone (6-MBOA) under short photoperiod - Xin Dai; Lian Yu Jiang; Mei Han; Man Hong Ye; Ai Qin Wang; Wan Hong Wei; Sheng Mei Yang (The Science of Nature, 2016)

Procalcitonin Is a Stronger Predictor of Long-Term Functional Outcome and Mortality than High-Sensitivity C-Reactive Protein in Patients with Ischemic Stroke - Chao Wang; Li Gao; Zhi-Guo Zhang; Yu-Qian Li; Yan-Long Yang; Tao Chang; Long-Long Zheng; Xing-Ye Zhang; Ming-Hao Man; Li-Hong Li (Molecular Neurobiology, 2016)

Involvement of polyphosphate kinase in virulence and stress tolerance of uropathogenic Proteus mirabilis - Liang Peng; Qiao Jiang; Jia-Yun Pan; Cong Deng; Jing-Yi Yu; Xiao-Man Wu; Sheng-He Huang; Xiao-Yan Deng (Medical Microbiology and Immunology, 2016)

Food wastes as fish feeds for polyculture of low-trophic-level fish: bioaccumulation and health risk assessments of heavy metals in the cultured fish - Zhang Cheng; Cheung-Lung Lam; Wing-Yin Mo; Xiang-Ping Nie; Wai-Ming Choi; Yu-Bon Man; Ming-Hung Wong (Environmental Science and Pollution Research, 2016)

The use of food waste-based diets and Napier grass to culture grass carp: growth performance and contaminants contained in cultured fish - Zhang Cheng; Wing-Yin Mo; Xiang-Ping Nie; Kai-Bing Li; Wai-Ming Choi; Yu-Bon Man; Ming-Hung Wong (Environmental Science and Pollution Research, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Sleep education in Hong Kong - Ngan Yin Chan; Siu Ping Lam; Jihui Zhang; Mandy Wai Man Yu; Shirley Xin Li; Albert Martin Li; Yun Kwok Wing (Sleep and Biological Rhythms, 2016)

Heat stress impairs mice granulosa cell function by diminishing steroids production and inducing apoptosis - Man Luo; Lian Li; Cheng Xiao; Yu Sun; Gen-Lin Wang (Molecular and Cellular Biochemistry, 2016)

Fungal community dynamics and driving factors during agricultural waste composting - Man Yu; Jiachao Zhang; Yuxin Xu; Hua Xiao; Wenhao An; Hui Xi; Zhiyong Xue; Hongli Huang; Xiaoyang Chen; Alin Shen (Environmental Science and Pollution Research, 2015)

Effects of 3,5-Diiodotyrosine and Potassium Iodide on Thyroid Function and Oxidative Stress in Iodine-Excess Wistar Rats - Dan Liu; Xinying Lin; Fugui Yu; Man Zhang; Hongxia Chen; Wei Bao; Xia Wang (Biological Trace Element Research, 2015)

Use of food waste as fish feeds: effects of prebiotic fibers (inulin and mannanoligosaccharide) on growth and non-specific immunity of grass carp (Ctenopharyngodon idella) - Wing Y. Mo; Zhang Cheng; Wai M. Choi; Clare H. I. Lun; Yu B. Man; James T. F. Wong; Xun W. Chen; Stanley C. K. Lau; Ming H. Wong (Environmental Science and Pollution Research, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

Reproduction of the sedimentary disturbance phenomenon of the Diexi ancient landslide-dammed lake under earthquake - Yu-feng Wei; Xiao-qun Wang; Man Sheng; Zhou Zhou; Yong Yuan (Journal of Mountain Science, 2015)

Tobacco smoking, family history, and the risk of nasopharyngeal carcinoma: a case–referent study in Hong Kong Chinese - Shao-Hua Xie; Ignatius Tak-sun Yu; Lap Ah Tse; Joseph Siu Kie Au; June Sze Man Lau (Cancer Causes & Control, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

In vivo expression patterns of microRNAs of Gallid herpesvirus 2 (GaHV-2) during the virus life cycle and development of Marek’s disease lymphomas - Pu Zhao; Xiu-Jie Li; Man Teng; Lu Dang; Zu-Hua Yu; Jia-Qi Chi; Jing-Wei Su; Gai-Ping Zhang; Jun Luo (Virus Genes, 2015)

Response of daily stem radial growth of Platycladus orientalis to environmental factors in a semi-arid area of North China - Yuan Jiang; Bing-Qin Wang; Man-Yu Dong; Yong-Mei Huang; Ming-Chang Wang; Biao Wang (Trees, 2015)

The rice OsAMT1;1 is a proton-independent feedback regulated ammonium transporter - Shunying Yang; Dongli Hao; Yu Cong; Man Jin; Yanhua Su (Plant Cell Reports, 2015)

Genetic analysis and chromosome mapping of a thermo-sensitive genic male sterile gene in wheat - Zhen-Gang Ru; Li-Ping Zhang; Tie-Zhu Hu; Hong-Yu Liu; Qing-Kai Yang; Man-Li Weng; Bin Wang; Chang-Ping Zhao (Euphytica, 2015)

Elevated homocysteine levels and risk of cardiovascular and all-cause mortality: a meta-analysis of prospective studies - Hui-yong Peng; Chang-feng Man; Juan Xu; Yu Fan (Journal of Zhejiang University-SCIENCE B, 2015)

Environmental mercury concentrations in cultured low-trophic-level fish using food waste-based diets - Zhang Cheng; Wing Yin Mo; Yu Bon Man; Cheung Lung Lam; Wai Ming Choi; Xiang Ping Nie; Yi Hui Liu; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Shark fin, a symbol of wealth and good fortune may pose health risks: the case of mercury - Yu Bon Man; Sheng Chun Wu; Ming Hung Wong (Environmental Geochemistry and Health, 2014)

Phanerochaete chrysosporium inoculation shapes the indigenous fungal communities during agricultural waste composting - Jiachao Zhang; Guangming Zeng; Yaoning Chen; Jie Liang; Chang Zhang; Binbin Huang; Weimin Sun; Ming Chen; Man Yu; Hongli Huang; Yi Zhu (Biodegradation, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Synthesis, biological evaluation, and molecular docking studies of pyrazolyl-acylhydrazone derivatives as novel anticancer agents - Man Xing; Ting-Ting Zhao; Yu-Jia Ren; Na-Na Peng; Xian-Hui Yang; Xi Li; Hui Zhang; Gao-Qi Liu; Li-Rong Zhang; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Calibration of the Normal Cutoff Values of Systolic Dyssynchrony of the Left Ventricular Synchronicity in Normal Subjects Using Real-Time 3-Dimensional Echocardiography and the Effects of Age and Heart Rate - Chun-Yan Ma; Shuang Liu; Qing Zhang; Jun Yang; Li Tang; Gabriel Yip; Cheuk-Man Yu (Cell Biochemistry and Biophysics, 2014)

Prognostic significance of microRNA-141 expression and its tumor suppressor function in human pancreatic ductal adenocarcinoma - Zi-Man Zhu; Yue-Fang Xu; Qin-Jun Su; Jun-Dong Du; Xiang-Long Tan; Yu-Liang Tu; Jing-Wang Tan; Hua-Bao Jiao (Molecular and Cellular Biochemistry, 2014)

Human health risk assessment based on trace metals in suspended air particulates, surface dust, and floor dust from e-waste recycling workshops in Hong Kong, China - Winifred Ka Yan Lau; Peng Liang; Yu Bon Man; Shan Shan Chung; Ming Hung Wong (Environmental Science and Pollution Research, 2014)

Cloning and molecular characterization of a myosin light chain gene from Puccinia striiformis f. sp. tritici - Jie Liu; Li-Na Han; Qiong Zhang; Qiu-Ling Wang; Qing Chang; Hua Zhuang; Jia Liu; Man Li; Dan Yu; Zhen-Sheng Kang (World Journal of Microbiology and Biotechnology, 2014)

Direct analysis of tobacco-specific nitrosamine NNK and its metabolite NNAL in human urine by LC–MS/MS: evidence of linkage to methylated DNA lesions - Chiung-Wen Hu; Yu-Wen Hsu; Jian-Lian Chen; Lai-Man Tam; Mu-Rong Chao (Archives of Toxicology, 2014)

Amino Acid, Fatty Acid, and Metal Compositions in Edible Parts of Three Cultured Economic Crabs: Scylla paramamosain, Portunus trituberculatus , and Eriocheir sinensis - Ke-Ji Jiang; Feng-Ying Zhang; Yan Pi; Li-Li Jiang; Zhong-Li Yu; Dan Zhang; Man-Man Sun; Lu-Jiao Gao; Zhen-Guo Qiao; Ling-Bo Ma (Journal of Aquatic Food Product Technology, 2014)

Arsenic concentration in rice, fish, meat and vegetables in Cambodia: a preliminary risk assessment - Hong-Sheng Wang; Suthipong Sthiannopkao; Zhuo-Jia Chen; Yu-Bon Man; Jun Du; Guang-Hua Xing; Kyoung-Woong Kim; Mohamed Salleh Mohamed Yasin; Jamal Hisham Hashim; Ming-Hung Wong (Environmental Geochemistry and Health, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

Local synchronization and amplitude of the fluctuation of spontaneous brain activity in attention-deficit/hyperactivity disorder: a resting-state fMRI study - Li An; Qing-Jiu Cao; Man-Qiu Sui; Li Sun; Qi-Hong Zou; Yu-Feng Zang; Yu-Feng Wang (Neuroscience Bulletin, 2013)

Molecular characteristics and evolutionary analysis of field Marek’s disease virus prevalent in vaccinated chicken flocks in recent years in China - Zu-Hua Yu; Man Teng; Jun Luo; Xin-Wei Wang; Ke Ding; Le-Le Yu; Jing-Wei Su; Jia-Qi Chi; Pu Zhao; Bo Hu; Gai-Ping Zhang; Ju-Xiong Liu (Virus Genes, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Activation of Akt and cardioprotection against reperfusion injury are maximal with only five minutes of sevoflurane postconditioning in isolated rat hearts - Yuan-yuan Yao; Man-hua Zhu; Feng-jiang Zhang; Chuan-yun Wen; Lei-lei Ma; Wen-na Wang; Can-can Wang; Xian-bao Liu; Li-na Yu; Ling-bo Qian; Jian-an Wang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2013)

Identification of quantitative trait loci across interspecific F2, F2:3 and testcross populations for agronomic and fiber traits in tetraploid cotton - Jiwen Yu; Shuxun Yu; Michael Gore; Man Wu; Honghong Zhai; Xingli Li; Shuli Fan; Meizhen Song; Jinfa Zhang (Euphytica, 2013)

Reversal of ATP-binding cassette drug transporter activity to modulate chemoresistance: why has it failed to provide clinical benefit? - Man Yu; Alberto Ocana; Ian F. Tannock (Cancer and Metastasis Reviews, 2013)

A Rhodamine-Cyclen Conjugate as Chromogenic and Fluorescent Chemosensor for Copper Ion in Aqueous Media - Min Wang; Di Zhang; Man Li; Min Fan; Yong Ye; Yu-fen Zhao (Journal of Fluorescence, 2013)

Spatiotemporal change in the climatic growing season in Northeast China during 1960–2009 - Man-yu Dong; Yuan Jiang; Da-yong Zhang; Zheng-fang Wu (Theoretical and Applied Climatology, 2013)

PEGylated Multi-Walled Carbon Nanotubes for Encapsulation and Sustained Release of Oxaliplatin - Linlin Wu; Changjun Man; Hong Wang; Xiaohe Lu; Qinghai Ma; Yu Cai; Wanshan Ma (Pharmaceutical Research, 2013)

Mapping quantitative trait loci for lint yield and fiber quality across environments in a Gossypium hirsutum × Gossypium barbadense backcross inbred line population - Jiwen Yu; Ke Zhang; Shuaiyang Li; Shuxun Yu; Honghong Zhai; Man Wu; Xingli Li; Shuli Fan; Meizhen Song; Daigang Yang; Yunhai Li; Jinfa Zhang (Theoretical and Applied Genetics, 2013)

Tissue concentrations, bioaccumulation, and biomagnification of synthetic musks in freshwater fish from Taihu Lake, China - Xiaolan Zhang; Qing Xu; Shoukuan Man; Xiangying Zeng; Yingxin Yu; Yuping Pang; Guoying Sheng; Jiamo Fu (Environmental Science and Pollution Research, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

A review of the anticancer and immunomodulatory effects of Lycium barbarum fruit - Wai-Man Tang; Enoch Chan; Ching-Yee Kwok; Yee-Ki Lee; Jian-Hong Wu; Chun-Wai Wan; Robbie Yat-Kan Chan; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

Identification and differential expression of two isogenes encoding 1-deoxy-d-xylulose 5-phosphate reductoisomerase in Glycine max - Man Zhang; Kai Li; Jianyu Liu; Deyue Yu (Plant Biotechnology Reports, 2012)

An integrated cytogenetic and physical map reveals unevenly distributed recombination spots along the papaya sex chromosomes - Ching Man Wai; Paul H. Moore; Robert E. Paull; Ray Ming; Qingyi Yu (Chromosome Research, 2012)

The expression level of Rosa Terminal Flower 1 (RTFL1) is related with recurrent flowering in roses - Li-Na Wang; Yun-Feng Liu; Yu-Man Zhang; Rong-Xiang Fang; Qing-Lin Liu (Molecular Biology Reports, 2012)

Chronic intermittent hypoxia induces local inflammation of the rat carotid body via functional upregulation of proinflammatory cytokine pathways - Siu-Yin Lam; Yu Liu; Kwong-Man Ng; Chi-Fai Lau; Emily C. Liong; George L. Tipoe; Man-Lung Fung (Histochemistry and Cell Biology, 2012)

Functional analysis of the HS185 regulatory element in the rice HSP70 promoter - Yu-Man Zhang; Yu-Mei Zheng; Na Xiao; Li-Na Wang; Yao Zhang; Rong-Xiang Fang; Xiao-Ying Chen (Molecular Biology Reports, 2012)

Protein sequence analysis based on hydropathy profile of amino acids - Xiao-li Xie; Li-fei Zheng; Ying Yu; Li-ping Liang; Man-cai Guo; John Song; Zhi-fa Yuan (Journal of Zhejiang University-SCIENCE B, 2012)

Mutations in the NRG1 gene are associated with Hirschsprung disease - Clara Sze-Man Tang; Elly Sau-Wai Ngan; Wai-Kiu Tang; Man-Ting So; Guo Cheng; Xiao-Ping Miao; Thomas Yuk-Yu Leon; Brian Man-Chun Leung; Kenneth-Jeremy W. S. Hui; Vincent Hang-Chai Lui; Yan Chen; Ivy Hau-Yee Chan; et al. (Human Genetics, 2012)

Inhibitory Effect of Delphinidin on Monocyte–Endothelial Cell Adhesion Induced by Oxidized Low-Density Lipoprotein via ROS/p38MAPK/NF-κB Pathway - Chun-ye Chen; Long Yi; Xin Jin; Ting Zhang; Yu-jie Fu; Jun-dong Zhu; Man-tian Mi; Qian-yong Zhang; Wen-hua Ling; Bin Yu (Cell Biochemistry and Biophysics, 2011)

Overexpression of Jazf1 induces cardiac malformation through the upregulation of pro-apoptotic genes in mice - Ki Beom Bae; Myoung Ok Kim; Dong Hoon Yu; Mi Jung Shin; Hei Jung Kim; Hyung Soo Yuh; Young Rae Ji; Jae-Young Kim; Jin Man Kim; Byung Hwa Hyun; Hwi Cheul Lee; Won Kyong Chang; et al. (Transgenic Research, 2011)

Retinoic acid inducible gene-I and melanoma differentiation-associated gene 5 are induced but not essential for dengue virus induced type I interferon response - Cheng-Feng Qin; Hui Zhao; Zhong-Yu Liu; Tao Jiang; Yong-Qiang Deng; Xu-Dong Yu; Man Yu; E-De Qin (Molecular Biology Reports, 2011)

A novel rice calmodulin-like gene, OsMSR2, enhances drought and salt tolerance and increases ABA sensitivity in Arabidopsis - Guo-Yun Xu; Pedro S. C. F. Rocha; Man-Ling Wang; Meng-Liang Xu; Yan-Chun Cui; Luo-Ye Li; Yu-Xing Zhu; Xinjie Xia (Planta, 2011)

Major Pollutants in Soils of Abandoned Agricultural Land Contaminated by e-Waste Activities in Hong Kong - Brenda Natalia Lopez; Yu Bon Man; Yin Ge Zhao; Jin Shu Zheng; Anna Oi Wah Leung; Jun Yao; Ming Hung Wong (Archives of Environmental Contamination and Toxicology, 2011)

Oxymatrine reduces neuronal cell apoptosis by inhibiting Toll-like receptor 4/nuclear factor kappa-B-dependent inflammatory responses in traumatic rat brain injury - Xiao-Qiao Dong; Wen-Hua Yu; Yue-Yu Hu; Zu-Yong Zhang; Man Huang (Inflammation Research, 2011)

Rice Gene OsDSR-1 Promotes Lateral Root Development in Arabidopsis Under High-Potassium Conditions - Xu Ming Yin; Pedro S. C. F. Rocha; Man Ling Wang; Yu Xin Zhu; Luo Ye Li; Shu Feng Song; Xinjie Xia (Journal of Plant Biology, 2011)

Development of Chromosome-specific Cytogenetic Markers and Merging of Linkage Fragments in Papaya - Ching Man Wai; Ray Ming; Paul H. Moore; Robert E. Paull; Qingyi Yu (Tropical Plant Biology, 2010)

Integration of Genetic and Cytological Maps and Development of a Pachytene Chromosome-based Karyotype in Papaya - Wenli Zhang; Ching Man Wai; Ray Ming; Qingyi Yu; Jiming Jiang (Tropical Plant Biology, 2010)

Paclitaxel-Loaded, Folic-Acid-Targeted and TAT-Peptide-Conjugated Polymeric Liposomes: In Vitro and In Vivo Evaluation - Peiqi Zhao; Hanjie Wang; Man Yu; Shuzhen Cao; Fei Zhang; Jin Chang; Ruifang Niu (Pharmaceutical Research, 2010)

Genetic analysis of strains of Japanese Encephalitis Virus isolated from swine in central China - Jian-Ming Fan; Jun Luo; Lu Chen; Man Teng; Dan Bu; Fang-Yu Wang; Li Wang; Chuan-Qing Wang; Gai-Ping Zhang (Virus Genes, 2010)

Activation of cloned BKCa channels in nitric oxide-induced apoptosis of HEK293 cells - Yu-Guang Ma; Ling Dong; Xiao-Long Ye; Chang-Lei Deng; Jiu-Hua Cheng; Wen-Chao Liu; Jin Ma; Yao-Ming Chang; Man-Jiang Xie (Apoptosis, 2010)

Coexpression and characterization of the human large-conductance Ca2+-activated K+ channel α + β1 subunits in HEK293 cells - Jun Li; Chang-Lei Deng; Fang Gao; Jiu-Hua Cheng; Zhi-Bin Yu; Li Liu; Man-Jiang Xie (Molecular and Cellular Biochemistry, 2009)

Empirical Models to Predict Parsimoniously the Mass and Number Concentrations of Ultrafine Particulate in Ambient Atmosphere - Chia-Pin Chio; Man-Ting Cheng; Yu-Chi Lin; Chung-Min Liao (Bulletin of Environmental Contamination and Toxicology, 2009)

Improvement of chloroperoxidase stability by covalent immobilization on chitosan membranes - Li-Hua Zhang; Chao-Hong Bai; Ying-Song Wang; Yu-Cheng Jiang; Man-Cheng Hu; Shu-Ni Li; Quan-Guo Zhai (Biotechnology Letters, 2009)

Characterization of SARS-CoV-specific memory T cells from recovered individuals 4 years after infection - Yan-Ying Fan; Zi-Tong Huang; Li Li; Man-Hui Wu; Tao Yu; Richard A. Koup; Robert T. Bailer; Chang-You Wu (Archives of Virology, 2009)

Identification and characterization of class 1 DXS gene encoding 1-deoxy-d-xylulose-5-phosphate synthase, the first committed enzyme of the MEP pathway from soybean - Man Zhang; Kai Li; Chunhong Zhang; Junyi Gai; Deyue Yu (Molecular Biology Reports, 2009)

Interaction between SARS-CoV helicase and a multifunctional cellular protein (Ddx5) revealed by yeast and mammalian cell two-hybrid systems - Jin-Yan Chen; Wan-Nan Chen; Kwok-Man Vincent Poon; Bo-Jian Zheng; Xu Lin; Yong-Xiang Wang; Yu-Mei Wen (Archives of Virology, 2009)

Fruit Development, Ripening and Quality Related Genes in the Papaya Genome - Robert E. Paull; Beth Irikura; Pingfang Wu; Helen Turano; Nancy Jung Chen; Andrea Blas; John K. Fellman; Andrea R. Gschwend; Ching Man Wai; Qingyi Yu; Gernot Presting; Maqsudul Alam; et al. (Tropical Plant Biology, 2008)

Characterization of O-Acetylserine(Thiol)Lyase-Encoding Genes Reveals Their Distinct but Cooperative Expression in Cysteine Synthesis of Soybean [Glycine max (L.) Merr.] - Chunhong Zhang; Qingchang Meng; Man Zhang; Fang Huang; Junyi Gai; Deyue Yu (Plant Molecular Biology Reporter, 2008)

Numerical investigation and identification of susceptible sites of atherosclerotic lesion formation in a complete coronary artery bypass model - Jun-Mei Zhang; Leok Poh Chua; Dhanjoo N. Ghista; Simon Ching Man Yu; Yong Seng Tan (Medical & Biological Engineering & Computing, 2008)

Characteristics of Atmospheric Aerosol and Acidic Gases from Urban and Forest Sites in Central Taiwan - Man-Ting Cheng; Chuen-Liang Horng; Yu-Chi Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

Effect of acetylcholine on pain-related electric activities in hippocampal CA1 area of normal and morphinistic rats - Yu Xiao; Xiao-Fang Yang; Man-Ying Xu (Neuroscience Bulletin, 2007)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Do medical students in Hong Kong have enough sleep? - Lok-Lam E HUEN; Tze-Wai G CHAN; Wai-Man M YU; Yun-Kwok WING (Sleep and Biological Rhythms, 2007)

Apoptosis of leukocytes as a marker of neutrophil-endotheliocyte interaction in coronary heart disease - A. B. Salmina; V. A. Shul’man; S. Yu. Nikulina; L. V. Trufanova; A. A. Fursov; P. A. But’yanov; A. P. Kuskaev; E. V. Bol’shakova; M. Yu. Kotlovskii (Bulletin of Experimental Biology and Medicine, 2007)

Knockout of a starch synthase gene OsSSIIIa/Flo5 causes white-core floury endosperm in rice (Oryza sativa L.) - Nayeon Ryoo; Chul Yu; Cheon-Seok Park; Moo-Yeol Baik; In Myoung Park; Man-Ho Cho; Seong Hee Bhoo; Gynheung An; Tae-Ryong Hahn; Jong-Seong Jeon (Plant Cell Reports, 2007)

Burrow Architecture of the Ghost Crab Ocypode ceratophthalma on a Sandy Shore in Hong Kong - Benny Kwok Kan Chan; Karen Kit Yu Chan; Philip Cheuk Man Leung (Hydrobiologia, 2006)

Beta-amyloid peptides induces neuronal apoptosis via a mechanism independent of unfolded protein responses - Man-Shan Yu; Ka-Chun Suen; Nga-Sze Kwok; Kwok-Fai So; Jacques Hugon; Raymond Chuen-Chung Chang (Apoptosis, 2006)

Structure, evolution and expression of a second subfamily of protein phosphatase 2A catalytic subunit genes in the rice plant (Oryza sativa L.) - Richard Man Kit Yu; Minnie Man Lai Wong; Ralph Wilson Jack; Richard Yuen Chong Kong (Planta, 2005)

Sulfhydryl modification by 4,4?-dithiodipyridine induces calcium mobilization in human osteoblast-like cells - Soong-Yu Kuo; Chin-Man Ho; Wei-Chung Chen; Chung-Ren Jan (Archives of Toxicology, 2003)

Potential Shifts and Intracellular Signaling in Smooth Muscle and Exocrine Cells: Role of the Secretory Potential (a Working Hypothesis) - V. V. Man'ko; M. Yu. Klevets (Neurophysiology, 2003)

Common and Distinguishing Features of the Functioning of Smooth Muscle and Secretory Cells - M. Yu. Klevets; V. V Man'ko (Neurophysiology, 2003)

Two genes encoding protein phosphatase 2A catalytic subunits are differentially expressed in rice - Richard Man Kit Yu; Yan Zhou; Zeng-Fu Xu; Mee-Len Chye; Richard Yuen Chong Kong (Plant Molecular Biology, 2003)

RAPD markers in diversity detection and variety identification of Tibetan hulless barley - Zeng Yu; Lan Li-Qiong; Luo Huan; Bai Jie; Yang Man-Ye; Miao Chen; Cai Ying-Fan; Qiang Xiao-Lin; Chen Fang (Plant Molecular Biology Reporter, 2002)

The dynamic monitoring of horqin sand land using remote sensing - Yuan-man Hu; Yan Jiang; Yu Chang; Ren-cang Bu; Yue-hui Li; Chong-gang Xu (Chinese Geographical Science, 2002)

Attenuated "cross talk" between κ-opioid receptors and β-adrenoceptors in the heart of chronically hypoxic rats - Jian Shan; Xiao-Chun Yu; Man-Lung Fung; Tak-Ming Wong (Pflügers Archiv - European Journal of Physiology, 2002)

Estimation of atmospheric input of mercury to South Lake and Jingyue Pool - Feng-man Fang; Qi-chao Wang; Zhuang-wei Ma; Ru-hai Liu; Yu-hong Cao (Chinese Geographical Science, 2002)

Sedimentary cycles of trace elements in Salawusu River Valley since 150 ka BP - Yao Chun-xial; Li Bao-sheng; Jin He-ling; David Dian Zhang; Yan Man-cun; Zhu Yi-zhi; Li Hou-xin; Zhang Yu-hong; Luo Kai-li (Journal of Geographical Sciences, 2002)

CaCO3 cycles in salawusu river basin since 150ka B.P. - Kai-li Luo; Bao-sheng Li; Yi-zhi Zhu; He-ling Jin; David Dian Zhang; Man-cun Yan; Hou-xin Li; Chun-xia Yao; Yu-hong Zhang (Chinese Geographical Science, 2001)

Possible Mechanisms of Acquired Resistance to Anti-angiogenic Drugs: Implications for the Use of Combination Therapy Approaches - Robert S. Kerbel; Joanne Yu; Jennifer Tran; Shan Man; Alicia Viloria-Petit; Giannoula Klement; Brenda L. Coomber; Janusz Rak (Cancer and Metastasis Reviews, 2001)

Hyperproduction of polyesters consisting of medium-chain-length hydroxyalkanoate monomers by strain Pseudomonas stutzeri 1317 - Jianzhong Xi; Qiong Wu; Yongbin Yan; Zengming Zhang; Peter H.F. Yu; Man-ken Cheung; Riqing Zhang; Guo-Qiang Chen (Antonie van Leeuwenhoek, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Distribution, Serological Identification, and PCR Analysis of Bacillus thuringiensis Isolated from Soils of Korea - Ho San Kim; Dae Won Lee; Soo Dong Woo; Yong Man Yu; Seok Kwon Kang (Current Microbiology, 1998)

Methodical approaches to identification of transmembrane current of sodium-calcium exchange - V. V. Man'ko; M. Yu. Klevets; N. V. Fedirko (Neurophysiology, 1998)

Phylogenetic Analysis of Triple Gene Block Viruses Based on the TGB 1 Homolog Gene Indicates a Convergent Evolution - Sek-Man Wong; Kian-Chung Lee; Hai-Hui Yu; Wai-Fook Leong (Virus Genes, 1998)

Isolation and-analysis of focus-infiltrating lymphocytes in pulmonary tuberculosis - K. G. Zhestkov; A. Yu. Kiryukhin; M. I. Perel'man; V. M. Zemskov (Bulletin of Experimental Biology and Medicine, 1998)

Plant regeneration from callus cultures ofLithospermum erythrorhizon - Hee-Ju Yu; Soo Kyung Oh; Man-Ho Oh; Dong-Woog Choi; Young Myung Kwon; Sang-Gu Kim (Plant Cell Reports, 1997)

Plant regeneration from callus cultures of Lithospermum erythrorhizon - Hee-Ju Yu; Soo Kyung Oh; Man-Ho Oh; Dong-Woog Choi; Young Myung Kwon; Sang-Gu Kim (Plant Cell Reports, 1997)

Affinity purification of a 65-kilodalton parasporal protein from Bacillus thuringiensis PG-14 that shows mosquitocidal activity - Yong Man Yu; Michio Ohba; Keio Aizawa (Antonie van Leeuwenhoek, 1988)